Investigating the shared genetic architecture between inflammatory bowel disease and pancreatitis: a genome-wide cross-trait analysis - Hang-Ming Qi; Ting-Ting Liu; Jia-Yun Chen; Ya-Hui Wang; Xiao-Tong Mao; Yuan-Chen Wang; Jing Jin; Xi Lin; Jianfeng Yang; Wen-Bin Zou; Le Kang; Zhuan Liao (Molecular Genetics and Genomics, 2026)

Repeated recharge of primitive melts in the lower oceanic crust: Constraints from the Dongco ophiolite, Central Tibet - Xiao-Ni Li; Chuan-Zhou Liu; Wei-Qi Zhang; Tong Liu; Chang Zhang; Yin-Zheng Lin; Zhen Zhang (Lithos, 2026)

Sex peptide receptor modulates sex pheromone perception plasticity in female Galleria mellonella across mating status - Zhen-Ping Guo; Xu-Dong Pang; Li-Lin Luo; Ming-Qing Yu; Jun-Hong Linghu; Hua-Yan Xie; Guy Smagghe; Tong-Xian Liu; Shun-Hua Gui (Insect Biochemistry and Molecular Biology, 2026)

A dual mechanical tuning framework for rigid pillared elastic metamaterials: Geometric reconfiguration and controllable prestress - Zu Shao; Tong Cheng; Yi Zhang; Wei Zhong Jiang; Zhu Kun Mi; Xiang Jie Wei; Xin Guo; Wang Lin Xiong; Kai Hao Lin; Chuang Li; Shu Hao Song; Cheng Shen; et al. (Engineering Structures, 2026)

An auxetic trampoline metamaterial with tunable bandgap under prestrain - Tong Cheng; Gui Lei Chen; Wei Zhong Jiang; Yi Zhang; Xiang Jie Wei; Zhu Kun Mi; Xiao Ji; Lin Hua; Jia Hui Zhang; Shu Hao Song; Cheng Shen; Xin Ren (Engineering Structures, 2026)

Novel D-A1-A2-π-A self-assembled monolayer in suppressing the Voc deficit of the wide-bandgap perovskite solar cells - Dong-Tai Wu; Yu Hsuan Lin; Yi-Chen Lin; Hsin Li; Yu-Chen Liang; Yu-Tong Hung; Yi-Sheng Lin; Wei-Jia Qiu; Shi-Chun Liu; Yuan Jay Chang; Chieh-Ting Lin (Chemical Engineering Journal, 2026)

Injectable, adhesive, and ROS-responsive hydrogel loaded with curcumin and bFGF for enhanced oral ulcer healing - Yaru Zhang; Zengqi Ye; Chenhui Chen; Jiancheng Yu; Yihao Wu; Ziqi Yu; Yue Huang; Yangshuai Jin; Xian Tong; Li Zhu; Jixing Lin; Xiaojun Cai; et al. (Chemical Engineering Journal, 2026)

Reducing carbon mineralization and enhancing carbon storage in coastal earth aquaculture pond sediment using Spartina alterniflora-derived biochar - Ping Yang; Junwei Wang; Yongxin Lin; Hong Yang; Wenjing Liu; Qian Zhu; Chuan Tong; Dongyao Sun; Linhai Zhang; Kam W. Tang (Agriculture, Ecosystems & Environment, 2026)

Mesoscopic-scale simulation of structural changes during mineral dissolution in coal: Coupled phase-field method verified by X-ray CT - Jiahao He; Baiquan Lin; Tong Liu; Zhenyong Zhang; Yanchi Liu (Advances in Water Resources, 2026)

Prokaryotic Argonautes as programmable tools for foodborne biological hazards detection: mechanisms, applications, and prospects - Jing-bo Jiao; Cheng-long Zhao; Jiang-li Cao; Tong Lin; Qing Kang; Li-jun Wang; Nan Wang; Xin-jun Du; Shuo Wang (Critical Reviews in Food Science and Nutrition, 2026)

Broad-spectrum defluorination via electronic strain of carbon–fluorine bonds: a ‘fluorophilic’ zero-valent metal system - Lisha Yang; Tong Hu; Dong Zhang; Wenjun Zhou; Daohui Lin (Water Research, 2026)

Revealing spatiotemporal patterns of metro tidal ridership and their relationships with TOD features: A dual-sequence clustering and explainable machine learning approach - Rui An; Zhaomin Tong; Xiping Yang; Yaping Wang; Ying Jing; Yaolin Liu; Lin Luo; Jiayu Liu (Travel Behaviour and Society, 2026)

Integrated network pharmacology and experimental validation to elucidate the mechanism of WIN55,212–2 in mitigating sepsis-induced pulmonary fibrosis in mice - Quan He; Dei-xing Yang; Lin Duo; Tong-ling Shi; Yuan-wei Yang; Jie-cheng Li; Shu-ting Li; Shang-shang Zhu (Tissue and Cell, 2026)

Structure and bioactivity of protolimonoids from the root bark of Dictamnus dasycarpus Turcz. - Hua Yue; Zi-Xuan Li; Zi-Tong Hao; Dan Zeng; Jie Bao; Ling-Zhi Zhang; Xue-Man Lin; Hua Sun; Shu-Fang Li; Su-Juan Wang (Phytochemistry, 2026)

Recovery of acid-grade calcium fluoride from fluorine‑silicon-containing wastewater using ammonia solution desilication and calcium carbonate precipitation: Effects, dissociation mechanisms and application potential - Tong Zhao; Huifen Yang; Dong Lin; Yuhao Liang; Siqi Zhang; Guocui Li; Qiwei Sun (Journal of Water Process Engineering, 2026)

MOF-derived MgMn-C composites for catalytic ozonation of phenol: Preparation and performance evaluation - Meiyi Hu; Jiaxin Wang; Ziyi Zhang; Donghang Li; Kun-Yi Andrew Lin; Shaoping Tong (Journal of Water Process Engineering, 2026)

Connectivity and function determine whether ponds act as sources or sinks of nonpoint-source phosphorus - Xiaofen Bai; Chen Lin; Ke Song; Wenlan Feng; Junfeng Xiong; Siyu Ge; Wanqian Yu; Jianchun Chen; Yijun Tong (Journal of Hydrology, 2026)

Treatment of nitrogen micro-polluted wastewater using a new type of biological folded non-aerated filter (BFNAF): Performance, microbial community and machine learning optimization - Jie Han; Youzhao Wang; Mingdong Chang; Xiaoyan Dang; Shumin He; Xiaodi Huang; Yongguang Ma; Zhipeng Wang; Yaonan Zhu; Junnan Liu; Jinxiang Wang; Lin Zhai; et al. (Journal of Environmental Chemical Engineering, 2026)

NaOH-induced dual-vacancy engineering in ZnCdS solid solutions for enhanced photocatalytic hydrogen evolution - Rong Yan; Chunyan Du; Danlian Huang; Lin Shi; Hanbo Yu; Wenbo Xu; Yu Yang; Tian Ao; Tong Sun; Shasha Yi; Jingyi Jiang; Yiyi Deng (Journal of Environmental Chemical Engineering, 2026)

Development and application of a water-coupled shock wave experimental system based on equivalent reconstruction for reservoir fracturing and permeability enhancement - Yongzan Wen; Wei Yang; Zening Wei; Zhaoyang Zhang; Yunqing Wang; Tong Liu; Minghua Lin (International Journal of Rock Mechanics and Mining Sciences, 2026)

Molecular insights into gas-driven displacement of confined water in coal - Jiajia Zhao; Baiquan Lin; Ting Liu; Tong Liu; Shixiang Tian (Fuel, 2026)

Liupao tea alleviates high-fat diet-induced obesity by re-establishing metabolic homeostasis of short-chain fatty acids and chenodeoxycholic acid - Yuru Tan; Xuancheng Wang; Anlong Song; Song Xu; Xueting Lin; Bao Yang; Jichu Luo; Ying Tong; Mingsen Wen; Xuan Guan; Peiting Li; Zhe Luo; et al. (Food Research International, 2026)

An integrated litmus test platform for low-background detection and photothermal inactivation of Salmonella typhimurium via HCR-urease signal amplification - Qing Kang; Tong Lin; Jingbo Jiao; Xinjun Du; Shuo Wang (Food Chemistry, 2026)

Self-sustaining slab dynamics of the underthrusting Indian lithosphere shaping the giant Himalayan Orocline - Chunsen Li; Hengcheng Ying; Xiao Xu; Xiaoyu Guo; Xiaofei Tong; Lingyan Li; Hongcheng Shi; Zizhao Yuan; Yanqi Lin; Xinglang Yin; Huolong Xu; Xiaodong Lan (Earth-Science Reviews, 2026)

Multiply modulations of double-sided comb-like Ni@NiWO4@WO3@C composites enabling exceptional electromagnetic protective and thermal management properties - Junhao Ding; Baoxin Fan; Zhen Lin; Chenhao Sun; Liyan Xie; Zidong He; Guoxiu Tong; Wenhua Wu (Chemical Engineering Journal, 2026)

Synergistic alkaline etching and nitrogen lattice occupation strategy enables gradient defluorinated cathode for high-performance Li/CFx batteries - Hongwei Cai; Xiaoxiao Pan; Cong Li; Hao Luo; Menghan Lin; Mingyi Shang; Jiqiong Lian; Yanan Fu; Hongjun Yue; Huixin Chen; Xiaolong Li; Yujin Tong; et al. (Chemical Engineering Journal, 2026)

Surface-reconstructed manganese oxides for enhanced external-oxidant-free degradation of bisphenol A: A direct electron transfer mechanism - Dawei Wang; Yihan Zhu; Keyi Gao; Zhuang Liu; Tong Li; Lin Chen; Yilan Jiang (Chemical Engineering Journal, 2026)

In-situ interfacial C–S–Zn bonding in N/S co-doped hard carbon anchoring ZnS for durable and fast sodium storage - Lingling Liu; Chuanyue Yang; Tong Wang; Jingwen Sun; Xu Yao; Ning Sheng; Xiansen Tao; Lin Shi; Jingquan Sha (Chemical Engineering Journal, 2026)

Development of magnetic solid-phase extraction with magnetic graphene oxide composite nanospheres for sensitive determination of perfluoroalkyl substances in tea beverages - Xin-Li Song; Tong Sun; Ke-Chao Liao; Hui Lv; Pin-Pin Wang; Dong-Dong Wang; Yan Lu; Lin Li (Analytica Chimica Acta, 2026)

Sulfobutylether-(hydroxypropyl-β-cyclodextrin) bonded silica as stationary phase for enhancing chiral separation in liquid chromatography - Linna Xu; Ankang Li; Jialong Wang; Gaosheng Yang; Liqin Lin; Keer Yu; Huizhen Ni; Wentao Xu; Junchao Zhu; Dongping Cheng; Shengqiang Tong (Analytica Chimica Acta, 2026)

The Evaluation Method of Flow and Temperature Field for a Subsea Cage-Type Choke Valve - Wujun Tong; Yingying Wang; Zeqing Lin; Dingwen Huang; Haibo Li; Xinzhong Li (Journal of Marine Science and Engineering, 2026)
As a critical regulating component in subsea Christmas tree systems, the cage-type choke valve governs the overall production efficiency and operational reliability of offshore oil and gas exploitation owing to its unique internal flow field characteristics. In accordance with the in situ operating conditions of the target oilfield, this paper performs a numerical simulation and systematic analysis on the flow field behaviors of a cage-type choke valve. Based on the fundamental theories of computational fluid dynamics (CFD), a three-dimensional coupled flow and heat transfer numerical model for the target choke valve is constructed via the FLUENT solver. Flow parameters under diverse pressure difference conditions are measured, validating the accuracy and feasibility of the established numerical model. Corresponding model hypothesis criteria and boundary condition configuration schemes are explicitly defined. Spatial distribution characteristics of the internal temperature, velocity, and pressure fields of the choke valve under different operating conditions are obtained through numerical simulation. Ten monitoring nodes uniformly arranged along the fluid domain from the inlet to the outlet are selected for quantitative analysis. The research results clarify that lower seawater temperature intensifies heat dissipation, leading to the observed temperature decrement, and confirm that the cage orifice structure dominates the flow acceleration, with the pressure drop magnitude linearly correlating with the inlet–outlet differential pressure. The research methodology and numerical findings of this study can provide a reliable basis for structural optimization and operating condition matching of cage-type choke valves applied in subsea oil and gas production systems.

Targeting multidimensional nociceptor-tumor interactions to mitigate immune evasion of cancer - Aojia Jin; Jiaxing Pan; Jingyi Su; Shutong Lin; Xiaohan Shi; Yu Zhang; Jing Feng; Bruno De Geest; Twan Lammers; Tong Ji; Gang Jin; Zhiai Xu; et al. (Science Bulletin, 2026)

Global Freshwater Resistomes Reveal Environmental Signatures Associated with the Burden of Drug-resistant Tuberculosis - Tong Li; Jiahui Lv; Yunye Tu; Li Cheng; Hongjun Xiao; Yanping Sun; Jia-xin Li; Mingkun Lv; Jingkai Yang; Guanghui Wang; Zexi Tang; Yajie Liu; et al. (Environmental Pollution, 2026)

Influence of cutterhead cooling water on microwave-induced fracturing of hard rocks during microwave-TBM synchronous operation - Tianyang Tong; Xia-Ting Feng; Chengxiang Yang; Feng Lin; Shiping Li; Xiangxin Su (Tunnelling and Underground Space Technology, 2026)

Corrigendum to “Water-Land-Energy-Carbon nexus in cities: A dynamic model with evidence from Beijing” [Sustainable Cities and Society 148 (2026) 107579] - Yanning Gao; Guangjin Tian; Xiaowen Shi; Tong Lin (Sustainable Cities and Society, 2026)

Water-Land-Energy-Carbon nexus in cities: A dynamic model with evidence from Beijing - Yanning Gao; Guangjin Tian; Xiaowen Shi; Tong Lin (Sustainable Cities and Society, 2026)

Efficiently photocatalytic synthesis of a special dye intermediate with CO2 for preparing a disperse dye SCFM-ANCY suitable for supercritical coloration of bio-based fibers - Yang-Sheng Zhou; An-Tong Liu; Yi-Wei Shi; Lin Xie; Jia-Jie Long (Process Safety and Environmental Protection, 2026)

PSO-ACO metaheuristic ship-UAV collaborative scheduling for maritime emergency response under marine uncertainty - Godfred Ziedor; Bin Duo; Obed Tettey Nartey; Tong Liu; Jie Lin; Junsong Luo (Ocean Engineering, 2026)

Enhanced degradation of sunscreen additive through oxone activated by cobalt sulfide: Tailoring the nanostructure for boosting catalytic performance - Xin-Yu Jiang; Shaoping Tong; Ta Cong Khiem; Nguyen Nhat Huy; Wei-Jie Liu; Wei-Hsin Chen; Chechia Hu; Kun-Yi Andrew Lin (Journal of Water Process Engineering, 2026)

Fungal necromass dominates soil organic carbon accrual after decadal active restoration of alpine grassland - Shijie Zhou; Jinchao Gong; Keqi Fan; Abraham Allan Degen; Jingjing Wu; Xiongkui Lin; Tahmina Kausar; Yue Xiu; Linlin Li; Liang Tie; Ziwei Yang; Congyu Ma; et al. (Journal of Environmental Management, 2026)

Nonlinear prestack inversion method for the effective pore-fluid bulk modulus based on the Zoeppritz equations - Lin Zhou; Jingye Li; Jianping Liao; Xiaohong Chen; Tong Zhang; Ming Ouyang (Journal of Applied Geophysics, 2026)

Comparative roles of physicochemical properties in O2 oxidation and CO2 gasification of leached biomass chars - Jianfeng Cai; Zhimin Lu; Youxing Wei; Yulong Lin; Yanjiang Li; Tong Zhou; Shunchun Yao (Fuel, 2026)

Pickering emulsion stabilized by immobilized lipase for OPO synthesis and acyl migration inhibition - Ruichi Guo; Xiangyu Du; Lin Li; Liqi Wang; Na Zhang; Tong Wang; Dianyu Yu (Food Research International, 2026)

Self-powered trickling-filter bioelectro-Fenton removal of gaseous isopropanol using sulfur-modified Fe-biochar fillers and a melanin-modified cathode - Chi-Wen Lin; Yu-Sheng Yang; Shu-Hui Liu; Wei Tong Chen; Xiang-En Ke (Chemical Engineering Journal, 2026)

Experimental study and numerical simulation on a multi-stage counter-current continuous fluidized bed reactor for activating iron-based Fischer-Tropsch synthesis catalyst - Zhanqi Yang; Chengxiang Li; Yifeng Bu; Tao Wang; Ruili Tong; Hairui Lin; Yongmin Zhang; Zhuowu Men; Youwei Cheng (Chemical Engineering Journal, 2026)

An injectable thiolated alginate/oxidized dextran hydrogel with curcumin-copper nanoparticles for corneal neovascularization after alkali burn - Zhongwu Bei; Lin Ye; Shiyu Liang; Qi Tong; Xicheng Li; Jianan Li; Xiaorui Yu; Yujia Wei; Xuyue Liang; Tingyu Yang; Yun Yang; Longqian Liu; et al. (Carbohydrate Polymers, 2026)

Relationships between char CO2 gasification reactivity and char surface active sites from a suite of organic model compounds - Jianfeng Cai; Zhimin Lu; Youxing Wei; Yulong Lin; Yanjiang Li; Tong Zhou; Shunchun Yao (Biomass and Bioenergy, 2026)

Genomic mining of the terpene synthase family in magnoliids reveals novel clades - Fang Wang; Qiongqiong Lin; Zijian Zhang; Yunyang Yu; Mengxue Feng; Meixiu Lin; Yongjuan Ren; Liuming Luo; Xin Liu; Huan Liu; Sunil Kumar Sahu; Tong Wei; et al. (The Nucleus, 2026)

Establishment of an efficient Agrobacterium-mediated transformation system and CRISPR/Cas9-mediated genome editing of the OvPDS1 gene in Oxalis vulcanicola ‘Sunset Velvet’ - Wanli Tuo; Xuexuan Wang; Tong Wu; Shentao Zhang; Pingting Guo; Xinyun Lin; Qianyu Lin; Junwen Zhai; Shasha Wu (Planta, 2026)

Quercetin induces molecular hallmarks of immunogenic cell death and cGAS-STING pathway activation via mitochondrial DNA release in hepatocellular carcinoma cells - Tong Lin; Yifan Chen; Zhengrong Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Exosomal miR-21-5p from ectopic endometrial stromal cells drives fibrosis progression in endometriosis through direct VHL targeting - Jia-Hao Chen; Yi-Hong Lei; Dian-Chao Lin; Hua-Ying Zhang; Zhi-Xiong Huang; Ruo-Fan Huang; Pei-Tong Wei; Meng-Jie Yang; Xin-Yu Ding; Wei-Dong Zhou; Qiong-Hua Chen (Human Cell, 2026)

Discovery of a Novel Alloherpesvirus in Diseased Turbot in China - Wenli Liu; Qihang Tu; Yueqi Wu; Jing Li; Wei Lin; Fengjuan Tian; Wenguang Xu; Shan Xu; Yigang Tong (Journal of Fish Diseases, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Efficient recovery of Fe, Pb and Zn from jarosite residues via reduction roasting and in-situ sulfidation: CRITIC-weighted response surface optimization, mechanism and engineering potential - Tong Zhao; Huifen Yang; Dong Lin; Jiahong Li; Siqi Zhang; Guocui Li; Qiwei Sun (Process Safety and Environmental Protection, 2026)

Enhancing simulation accuracy of a semi-distributed conceptual hydrological model using satellite soil moisture products - Haotian Cai; Yi Nan; Rui Tong; Fuqiang Tian; Jingan Lin (Journal of Hydrology, 2026)

Occurrence and driving factors of microplastics in the surface water of a grassland river in China - Tong Lin; Zeyuan Liu; Qifeng Liu; Ruihong Yu; Haizhu Hu (Journal of Hydrology, 2026)

Turning ecological nuisance to environmental resource: Use of Spartina alterniflora-derived biochar to decrease N2O production potential and emission in coastal aquaculture pond sediment - Wenjing Tan; Kaiyuan Liu; Ping Yang; Kam W. Tang; Hong Yang; Chuan Tong; Wenjing Liu; Dongyao Sun; Junwei Wang; Yongxin Lin; Yifei Zhang (Journal of Environmental Chemical Engineering, 2026)

Machine learning based efficiency maximization of bio-Fenton SBR for enhanced antibiotic removal - Chenyang Lin; Tong Shen; Yuga Yoneyama; Yoshihiko Inagaki; Yutaka Sakakibara (Journal of Environmental Chemical Engineering, 2026)

Waterfowl's presence enhanced N2O emissions from restored coastal wetlands: Trade-offs between biodiversity and climate - Ping Yang; Wenting Liu; Yifei Zhang; Hong Yang; Siying Li; Wenjing Liu; Chuan Tong; Dongyao Sun; Yongxin Lin; Lihua Wang; Kam W. Tang (Journal of Environmental Management, 2026)

Trace volatile sulfur compounds in biogases from sanitary landfill site: emission level, toxicity, and mitigation measure - Tong Gao; Jinlong Li; Lin Li; Yanjie Wang; Jingyun Ge; Yunping Han (Journal of Cleaner Production, 2026)

Comparisons of CEAS, PC-CLD, and CRDS for NO2 measurements under a complex atmosphere in Chengdu, China - Jinzhao Tong; Renzhi Hu; Xin Li; Keding Lu; Yanan Cao; Shuguang Hu; Chuan Lin; Xiaoyan Liu; Pinhua Xie (Journal of Environmental Sciences, 2026)

Trophic state regulates nitrous oxide (N2O) emissions and associated indirect emission factors in coastal creeks - Qian Zhu; Ziyuan Chen; Ping Yang; Hong Yang; Wenjing Liu; Junwei Wang; Chuan Tong; Jujuan Gao; Dongyao Sun; Yongxin Lin; Kam W. Tang (Global and Planetary Change, 2026)

PM2.5 and constituents exacerbate decline of kidney function: The modification of glucose metabolism - Boxiang Wang; Lijuan Xu; Ren Lin; Hanxiang Cai; Yiman Zou; Yike Tong; Can Li; Feifei Liu (Environmental Research, 2026)

A quasi-zero stiffness locally resonant metamaterial with tunable low-frequency and wide bandgap - Haibin Ding; Chenghui Lin; Changjie Xu; C.W. Lim; Zhiyun Liu; Yitian Yu; Lihong Tong (Engineering Structures, 2026)

Engineering cellulose nanocrystal-regulated UiO-66 as a bifunctional platform for enhanced fluoroquinolone antibiotic removal - Dongdong Liu; Runkai Wang; Huiqin Wang; Kunlin Ke; Lin Li; Jiangyan Ji; Tong Wu; Xiaoli Zhu (Chemical Engineering Journal, 2026)

Dual-functional isoquercitin‑silver nanoparticles alleviate bacterial-induced excessive inflammation of wound infection and sepsis - Guowei Zhong; Qianfeng Xu; Aidi Tong; Fen Zou; Chunyi Tong; Yangjia Zhuo; Jundong Lin; Wenjie Xie; Jianheng Ye; Jianming Lu; Bin Liu; Huichan He; et al. (Chemical Engineering Journal, 2026)

Physical morphology of conductive carriers shapes anaerobic biofilm development and methanogenesis - Lu Zhang; Wen He; Zu-xiang Yan; Tong-yi Yang; Lin-zhi Zhai; Xiu-jie Wang; Qian-qian Jia; Ze-chong Guo (Bioresource Technology, 2026)

Modeling the ion-particle interactions and particle deposition due to Needle-point Bipolar Ionization (NPBI) - Wenfeng Huang; Tong Lin; Peter J. McKinney; Jianshun Zhang (Building and Environment, 2026)

Molecular phylogeny and taxonomy of Mus pahari (Rodentia: Muridae) - Qingfang Zou; Lin Gu; Tao Zhang; Chengxin Zhou; Xuming Wang; Tong Zhang; Keji Guo; Shaoying Liu; Shunde Chen (Mammalian Biology, 2026)

Glucomannan synthase genes DoCSLA6,7 promote polysaccharides accumulation in Dendrobium officinale under low phosphorus stress - Aiying Tong; Huimin Shen; Yue Tian; Yawen Li; Lin Liu (Horticulture, Environment, and Biotechnology, 2026)

TMT Exacerbates Selenium-Deficient Enteritis in Gallus by Mediating Pyroptosis Through ROS/ERS - Shize Wang; Yutian Lei; Yuting Dong; Kang Yang; Tong Xu; Hongjin Lin (Biological Trace Element Research, 2026)

Hydrothermal zircon recording multi-stage tectonic reworking in Permian volcaniclastic rocks of the Emeishan Large Igneous Province, Southwest China - Junlang Chen; Xiaohong Liu; Tong Lin; Mingyou Feng; Hongming Tang; Jie Tan; Weiwei Wang; Junxin Shang; Tenglong Hu; Yili Zhao (Mineralogy and Petrology, 2026)

A new sesterterpenoid with β -glucuronidase inhibitory activity from the Cordyceps -colonising fungus Aspergillus versicolour ZJUTE2 - Youmin Ying; Yixian Qiu; Jing Tang; Yuhao Lin; Sha Xu; Jiayue Ni; Yun Zhang; Cuiping Tong; Wei Mao (Natural Product Research, 2026)

PROMETHEUS clinical trial protocol: tailoring healthy ageing with lifestyle and nutraceuticals - Ajla Hodzic Kuerec; Lihuan Guan; Weilan Wang; Duarte Barros; Wejdan M. Alenezi; Jozo Grgic; Vanessa K. Wazny; Jordi Morwani-Mangnani; Mazzarine Dotou; Dingding Zhang; Tong Chen; Jiaqiu Wang; et al. (GeroScience, 2026)
The d emographic shift toward an older population is accelerating the prevalence of age-related diseases. Precision geromedicine represents a paradigm shift in targeting the biological processes of ageing to optimise health and healthspan, which likely requires multimodal tailored interventions. PROMETHEUS, as part of the XPRIZE healthspan semi-finalist competition, is an 8-week feasibility and exploratory study including 20 middle-aged-to-older participants who received a multimodal intervention comprising fundamental and augmented interventions. The fundamental interventions include sleep and dietary recommendations; supplementation with whey protein, creatine, and fucoidan; supervised exercise with an exergaming component (dual-task cognitive-physical training); motivational interviewing; and cognitive behavioural therapy. The augmented intervention is further personalised based on predefined gerotypes, reflecting individual ageing patterns beyond chronological age. At baseline, urolithin A, nicotinamide mononucleotide, and/or multivitamin-multimineral were prescribed to participants based on their muscle mass, VO 2 peak, and cognitive performance. At mid-intervention, interventions were adjusted based on individual response, including dose escalation and/or the addition of ergothioneine for inadequate improvement in cognition. Primary outcomes include measures of muscle strength and mass, immune function and cognitive performance, and feasibility indicators such as adherence and trial completion. Secondary outcomes include assessments of other biological, clinical, and digital biomarkers of ageing, as well as qualitative indicators of motivation and personal values. This study is aimed at investigating the recruitment feasibility, safety, adherence, and exploratory outcome trajectories of a multimodal, personalised precision geromedicine intervention protocol based on individual participant’s baseline characteristics and interim responses. These findings will also inform the design of a subsequent 12-month, randomised controlled trial evaluating personalised lifestyle and nutraceutical strategies with the potential to incorporate repurposed pharmacological agents to optimise age-related health outcomes.

Onshore U-OWC Wave Energy Converter: A Hydrodynamic Study of Its Capture Performance Impacted by Air-Compressibility Effects - Yi-Chih Chow; Hong-Yang Chang; Duy Tong Nguyen; Chen-Chou Lin (Journal of Marine Science and Engineering, 2026)
The distinct engineering advantages of Oscillating Water Column (OWC) systems have driven substantial academic interest lately. This work examines the onshore U-shaped OWC (U-OWC), selected for its cost-effective installation integrated with existing coastal infrastructure and its superior broadband response to diverse wave climates. Time-domain CFD simulations, incorporating the scaling-rematched approach, were conducted to quantify key hydrodynamic and air-compressibility coefficients, including the amplitude of the wave exciting force, fluid damping coefficient, added mass, absorption factor, and the effective PTO (power take-off) damping and air-compressibility coefficients. These parameters collectively elucidate the underlying hydrodynamics and how they are interwoven with the compressibility of the air in the plenum chamber, thereby impacting the U-OWC’s energy-capture performance under incident waves. A principal finding is the identification of a C+ interval wherein air compressibility enhances capture performance in the lower wave-period range examined (

Automated computer vision monitoring of black soldier fly larval growth using metaheuristic optimization for waste-to-feed bioconversion - Jui-Sheng Chou; Benjawan Phakdee; Zih-Tong Lin; Chang-Ping Yu; Pei-Hsun Wu; Cheng-jen Shih (Computers and Electronics in Agriculture, 2026)

Rockburst mitigation by microwave destressing in a deep drill-and-blast tunnel: thermal–damage–stress evolution with a slotted-wall coaxial applicator - Yuntan Ao; Xia-Ting Feng; Shiping Li; Xiaojun Zhang; Juan He; Tianyang Tong; Yifan Zhang; Feng Lin (Tunnelling and Underground Space Technology, 2026)

Tumor empowered binary macrophages regulate T cell interferon signaling to mediate immunotherapy resistance in gastric cancer - Tong Xie; Bohan Zhang; Lei Jiang; Wenwen Zhang; Boxin Liu; Yang Shi; Xiaotian Zhang; Jian Li; Yifan Zhang; Jun Zhou; Yanshuo Cao; Yakun Wang; et al. (Science Bulletin, 2026)

Quasi-Newton method based finite-time fuzzy tracking control for uncertain unmanned surface vehicles: Indirect and direct approaches - Min Ma; Zefeng Lin; Tong Wang; Tieshan Li (Ocean Engineering, 2026)

Corrigendum to “Circular RNA-mediated regulatory networks drive oxidative stress and metabolic dysregulation in broiler breast muscle under chronic heat stress” [J. Therm. Biol. 139 (2026) 104471] - Zhen Liu; Yingsen Liu; Tong Xing; Lin Zhang; Liang Zhao; Feng Gao (Journal of Thermal Biology, 2026)

Circular RNA-mediated regulatory networks drive oxidative stress and metabolic dysregulation in broiler breast muscle under chronic heat stress - Zhen Liu; Yingsen Liu; Tong Xing; Lin Zhang; Liang Zhao; Feng Gao (Journal of Thermal Biology, 2026)

Overwintering waterbirds are important reservoirs for the spread of antibiotic resistance genes (ARGs): Shared patterns at the waterbird-environment interface and the risk of horizontal transfer - Hongjia Li; Yuanyuan Xu; Tong Lin; Canshi Hu; Zhengxia Yang; Haijun Su (Journal of Hazardous Materials, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Cooperative LoRA with frequency priors for SAM2-Based multimodal remote sensing semantic segmentation - Hongwei Tong; Jingyan Huang; Lin Chai (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Sn-2 palmitate ameliorates dyslipidemia in high-fat-fed aged mice via bile acid-mediated gut-liver-adipose cross-talk - Lin Zhu; Mingzhe Deng; Hong Zhang; Zhenbo Xu; Peijin Tong; Jianchun Wan; Boyan Gao; Liangli (Lucy) Yu; Yaqiong Zhang (Food Bioscience, 2026)

Particle crushing of embedded carbonate sand within granular assemblies: A DEM analysis of stress path and particle shape effects - Zong-Lei Dong; Xian-Kang Liu; Chen-Xi Tong; Shi-Lin Luo; Ke-Chen Liu; Deng-Jie Zhang; Sheng Zhang (Computers and Geotechnics, 2026)

Bio-inspired functionalization of PA1012 into piezoelectric ionomers via molecular asymmetry and ion-cluster polarization - Guangmou Cao; Rong Li; Qi Liang; Jingwen Liu; Pengyuan Luo; Haomeng Ma; Yang Yu; Linyi Cui; Le Xu; Jingjing Ma; Tong Lin; Liuchun Zheng (Chemical Engineering Journal, 2026)

Relationships between char CO2 gasification reactivity and char physicochemical properties from biomasses with different leaching pretreatments - Jianfeng Cai; Zhimin Lu; Youxing Wei; Yulong Lin; Yanjiang Li; Tong Zhou; Shunchun Yao (Biomass and Bioenergy, 2026)

A one-tube RAA-PfAgo system for rapid and sensitive detection of Monkeypox virus - Na Zhao; Xuejian Zhang; Yulu Gan; Lin Li; Yunmin Wang; Tong Xu; Yao Pan; Kui Gu; Yu Zhao (Analytica Chimica Acta, 2026)

Twistors-based anti-unwinding control of spacecraft via the fully actuated system approach - Dongyan Jin; Shuqian Feng; Zefeng Lin; Wenqiang Ji; Tong Wang; Jianbin Qiu (Advances in Space Research, 2026)

Exploration and Development Site Selection of Marine Sand Resources Around Hainan Island, China: An Integrated Analysis Based on a Combination of Subjective and Objective Weights - Maogang Qin; Changliang Tong; Mingzhi Lin; Bo Chen; Jialin Wang; Jun Zhu; Mingkun Lin; Yu Zhu; Xing Huang (Natural Resources Research, 2026)

Mechanistic responses of coccolithophores to exposure to the marine pollutant atrazine - Xiang-Wu Chen; Yi-Tong Huang; Yue-Tao Song; Zhuo-Fan Li; Xue-Ling Huang; Da-Wei Li; Lin-Jian Ou (Water Research, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Engineering Mn-confined Fe0-carbon with isolated oxygen-containing groups breaks the bottleneck for concurrent self-driven Fenton degradation of antibiotics and heavy metals immobilization - Yujiang Huang; Dan Liu; Zhouyang Shi; Tong Hu; Huiwang Dai; Sicheng Pan; Wenjun Zhou; Fei Ge; Daohui Lin; Lizhong Zhu (Journal of Hazardous Materials, 2026)

Bimetallic synergy-driven S-scheme MIL-125(Ti)@Ce-Ni heterojunction for efficient visible-light photocatalytic degradation - Peiliang Xie; Xiaoyan Wu; Lin Lin; Ziyu Wang; Jie Xu; Yuli Ma; Jun Zhu; Qin Tong (Journal of Environmental Chemical Engineering, 2026)

Flame impingement to facilitate the stability of NH3-CH4 laminar diffusion flames: High-speed imaging and schlieren visualization - Yidu Tong; Chenyang Fan; Zheng Fu; Ye Liu; Huiyong Du; Bin Xu; Guorong Lin; Shuo Jin; Shuainan Yang; Mingliang Wei (Fuel, 2026)

Carrier-free immobilization of α-galactosidase using novel cross-linkers: Robust inclusion body-derived CLEAs for efficient hydrolysis of raffinose family oligosaccharides in soymilk - Tong Sun; Wenyue Sun; Shutong Lin; Yan Liu; Lili Lu (Food Chemistry, 2026)

Towards integrated pollution control in inland watersheds: addressing multiple challenges through watershed-scale technological systems and targeted control strategies - Mei-Yun Lu; Jie Ding; Xin-Lei Yu; Zi-Tong Zhao; Yi-Lin Zhao; Ji-Wei Pang; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Environmental Pollution, 2026)

Synergistic engineering of zincophilic sites and hierarchical porosity in lignin-derived carbon nanofiber networks for ultra-high energy density flexible zinc-ion hybrid capacitors - Lin-Xuan Wu; Bo Wang; Jia-Long Wen; Zhan-hui Yuan; Tong-Qi Yuan (Chemical Engineering Journal, 2026)

Biodegradable Mg-Sr-Zr-Ho alloy with multifunctional angiogenic, antibacterial, anti-inflammatory, and osteogenic properties for orthopedic fixation - Xian Tong; Qi Li; Yuxin Zhang; Yuncang Li; Chi Yang; Jixing Lin; Cuie Wen; Jisi Zheng; Yusen Dai (Chemical Engineering Journal, 2026)

Evaluation of the mechanism for enhanced particle and VOC removal using needlepoint bipolar ionization technology - Tong Lin; Wenfeng Huang; Beverly Guo; Peter J. McKinney; Jianshun Zhang (Building and Environment, 2026)

Transcarotid Artery Revascularization for Asymptomatic Carotid Stenosis: A Systematic Review and Meta-Analysis - Zhi-Cheng Jiang; Qi-Fei Hu; Jia-Ming Huang; Xian-Wei Wang; Tong Lin; Xi-Lin Gao; Jia-Wen Cui; Jing-Lin Zhao; Dong Chen; Shu-Peng Li (Translational Stroke Research, 2026)

Lactiplantibacillus Plantarum O126 Postbiotics Boost growth, Antioxidant levels, Disease resistance, and Gut Health in Sea Cucumber (Apostichopus japonicus) - Feng-Li Chen; Hui-Ting Zhao; Wei Gu; Zong-Xiu Wu; Jing-Wen Xiang; Qing Yang; Yu-Lin Yang; Lei Tan; Meng-Xia Sun; Wei Cong; Shu Li; Bin-Tong Yang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Doxorubicin-Induced Cardiotoxicity in Breast Cancer: Mechanistic Pathways, Pharmacogenomic Modifiers, and Translational Strategies - Chi-Tong Kuok; Hao-Wei Lee; Chen-Yu Huang; Yu-Che Cheng; Shih-Chang Lin; Jiun-Wen Guo (Cardiovascular Toxicology, 2026)

Pollution Characteristics, Potential Sources and Transport Pathways of O3 and VOCs in a Coastal City of East China - Yuan Xue; Yufei Ling; Lei Tong; Jiayong Feng; Huan Lin; Chunli Liu; Cenyan Huang; Hang Xiao (Bulletin of Environmental Contamination and Toxicology, 2026)

Stand age drives divergent microbial metabolic limitations and ecosystem multifunctionality between rhizosphere and bulk soils in subtropical Cryptomeria japonica plantations - Shanshan Huang; Yi Jian; Jing Li; Dengjie Zhou; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Lixia Wang; et al. (Soil Ecology Letters, 2026)

Three-dimensional hierarchical CuCoAl-layered double hydroxide/Ti3C2 Schottky heterojunction for efficient visible-light degradation of ciprofloxacin - Zifei Gao; Ye Liu; Deke Wang; Baoyu Zou; Xingkang Yu; Yu Dong; Qing Li; Juanjuan Ma; Lin Liu; Chao Liu; Zhiwei Tong; Jun Hu (Applied Clay Science, 2026)

Near-Surface Q-Factor Estimation Using a Non-Gaussian Energy Spectrum - Ze-lin Li; Jiang-nan Tong; Ya-nan Jiang; Tong Chen; Guo-fa Li (Applied Geophysics, 2026)

Sulfonate-mediated hydrogen-bond network modulation and proton enrichment at zerovalent iron-water interface for efficient hydrodechlorination reaction - Tong Hu; Zhendong Zhao; Lisha Yang; Huiwang Dai; Yuejin Zhang; Hao Li; Wenjun Zhou; Daohui Lin; Lizhong Zhu (Water Research, 2026)

Field data-based safety assessment and probabilistic deformation prediction of existing metro tunnels under adjacent excavation - Wei-Bin Chen; Hai-Tong Liu; Yue Chen; Xiang-Sheng Chen; Tao Xu; Jing-Song Bai; Lin-Shuang Zhao (Tunnelling and Underground Space Technology, 2026)

Reinforced stepwise dissociation of water molecules via U 5f-O 2p-Ti 3d gradient orbital coupling for photoelectrochemical water splitting - Xiaochuan Deng; Tong Liu; Xudong Wu; Qijue Lin; Hanlin Liu; Han Yang; Xun Yang; Maoyin Wang; Kaiguo Chen; Jiayu Dai; Tao Chen; Wenkun Zhu (Science Bulletin, 2026)

Deep eutectic solvent-based ultrasound extraction of bioactive flavonoids from Coreopsis tinctoria Nutt.: Process optimization, HPLC analysis, and preliminary bioactivity evaluation - Peng Wen-Yu; Lin Fang-Qi; Mo Hong-Bo; Hu Tong-Yi; Ou Hong (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Characterization of volatile flavor compounds and sensory profiles in braised thigh meat and soup between fast- and slow-growing chickens at marketable age - Li Liu; Xiaoming Wang; Shengyuan Guo; Yongjian Xia; Lin Zhang; Liang Zhao; Tong Xing; Feng Gao (Food Chemistry, 2026)

Intraspecific and interspecific cross-compatibility of floral morphs in Oxalis zeekoevleyensis - Jianchao Chang; Kaiyue Wang; Xinyun Lin; Tong Wu; Shengtao Zhang; Qiaoxian Xu; Junwen Zhai; Shasha Wu (Flora, 2026)

Synergistic piezo-triboelectricity in ultra-thick PVDF-PAN nanofiber membranes for high-power energy harvesting and intensive force sensing - Peng Jiang; Lu Peng; Hongxia Wang; Wenyu Wang; Xin Jin; Tong Lin (Chemical Engineering Journal, 2026)

Mechanisms by Which Humic Acid Reduces Copper Toxicity in Citrus Roots Based on Omics and Physiology - Wei-Tao Huang; Rong-Rong Xie; Liang-Yuan Tong; Tian-Tian Xia; Jiuxin Guo; Ning-Wei Lai; Zeng-Rong Huang; Lin-Tong Yang; Li-Song Chen (Journal of Plant Growth Regulation, 2026)

Cadmium exposure accelerates ovarian aging in broiler breeders through oxidative stress and inflammation - Peng Xu; Tong Xing; Lin Zhang; Liang Zhao; Feng Gao (Animal Reproduction Science, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Design and verification of a microbial consortium with an anchoring-interface enhancement strategy for efficient PAHs degradation in groundwater - Wang Kai Tong; Jiajun Hu; Chaomeng Dai; Jia Jie Zou; Han Tang; Piao Yi Jiang; Min-tian Gao; Jixiang Li; Xihua Wang; Yalei Zhang; Ken-Lin Chang; Kah Hon Leong; et al. (Water Research, 2026)

Electroplating parks as hidden sources of novel plastic additives: Occurrence, migration pathways, and ecological risks - Zi-Tong Li; Zecong Ding; Yingjie Chen; Kai Cui; Li Wang; Hai-Yan Zhang; Qian Jiang; Li-Qian Lin; Jian-Liang Zhao (Water Research, 2026)

Comparative study on the generation and migration characteristics of blasting dust and toxic gases in high-altitude tunnel: based on field measurements and CFD - Minglei Lin; Jianguo Liu; Mulati Jueraiti; Wen Nie; Linquan Tong; Jie Yu; Tianyue Wang; Shengnan Ou; Longzhe Jin (Tunnelling and Underground Space Technology, 2026)

Pericyte NNMT drives an immune-hostile vascular niche and restricts cancer immunotherapy - Sheng Wang; Geni Ye; Caiyun Zhang; Lin Tan; Zhang Zhang; Xi Xu; Xinhui Chen; Yiming Zhang; Xiaoling Xu; Jinghua Pan; Tong Lan; Junqiu Zhang; et al. (Science Bulletin, 2026)

Concomitant exposure to residential greenness, nitrogen dioxide, and outdoor light at night in association with incident anxiety - Jiayun Zhang; Yexiang Sun; Zihan Li; Lisha Xu; Jingjing Hu; Jie Qiu; Xinhan Zhang; Zongming Yang; Zhanghang Zhu; Yonghao Wu; Yixing Wang; Hongbo Lin; et al. (Landscape and Urban Planning, 2026)

Ponds greatly influence watershed ecosystem services value: An optimized InVEST model for large-scale - Xiaofen Bai; Chen Lin; Shenmin Wang; Junfeng Xiong; Jinduo Xu; Kun Xue; DanHua Ma; Yijun Tong; Jianchun Chen; Wenzhuo Cui (Journal of Hydrology, 2026)

Anthropogenic acids alter carbon sinks in a temperate karst catchment: Insights from multi-isotopic tracers - Jie Zhang; Lin Zhang; Shuangmei Tong; Jiejie Lyu; Jia Yuan; Menggui Jin (Journal of Hydrology, 2026)

Innovative design and separation performance study of an enhanced downhole oil-water separator based on hydrocyclonic-gravity synergistic - Lixin Zhao; Hui Lu; Xiaoguang Zhang; Lin Liu; Kangxing Dong; Yahong Wang; Shuang Zhang; Chenhao Qin; Tong Li (Journal of Environmental Chemical Engineering, 2026)

Facile fabrication of superhydrophobic covalent organic framework coating for highly efficient oil-water separation - Li-Hua Qi; Tong-He Zhang; Lin Wang; Zheng Wang (Journal of Environmental Chemical Engineering, 2026)

Urban-suburban-rural gradient variations in mortality associated with compound exposure to heat wave and ozone pollution: A case-crossover study using small-area assessment - Kang Ma; Fengman Fang; Xiuya Xing; Yuesheng Lin; Cheng He; Youru Yao; Fei Tong; Jingli Zhu; Huadong Wang; Feiyan Zhang; Ruoxi Li (Journal of Environmental Management, 2026)

A two-stage liquefaction approach based on the bond cleavage characteristics and interactive behavior of vitrinite and inertinite in Shangwan coal - Yuanzhe Wang; Lei Shi; Zhenyu Liu; Tong Zhao; Lin Lin; Qingya Liu; Yuxin Yan; Jianli Wang; Shansong Gao; Runze Zhao (Fuel, 2026)

Untargeted metabolomics analysis of foxtail millet fermented with Pleurotus geesteranus: Insights into the nutritional and antioxidant profiles - Tong Lin; Ziwei Zhang; Ruolin Shi; Gongjian Fan; Chunyan Xie (Food Chemistry, 2026)

16S rDNA sequencing combined with non-targeted metabolomics profiling reveals the mechanism of simulated digestion ultra-sound pea protein isolate in vitro - Xinyu Zhao; Xuemei Dong; Jianke Fang; Chun Li; Lin Zhao; Guofang Zhang; Peng Du; Tong Zhang; Xinyao Sun; Libo Liu; Wenkui Guo (Food Bioscience, 2026)

Synergistic water-electricity cogeneration enabled by topology engineering hierarchical MoS2 decorated hollow carbon heterostructures for enhanced solar energy utilization - Tong Wu; Lin Li; Runkai Wang; Weiping Wu; Fenghua Liu (Desalination, 2026)

Selenium regulates pyroptosis through the ROS-mtDNA-cGAS-STING axis to alleviate trimethyltin chloride-induced inflammation in chicken kidneys - Huiling Zheng; Xinyu Huo; Wenwen Zhang; Shuang Lou; Mingyue Li; Chenxi Huang; Kang Yang; Tong Xu; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Novel bio-inspired metamaterials for athletes to achieve high energy absorption and sensing under sports-specific load - Zehao Tong; Cheng Lin; Liwu Liu; Yanju Liu; Jinsong Leng (Chemical Engineering Journal, 2026)

Stable yet hydrophilic graphene oxide nanomembranes by zwitterionic reduction for dye desalination - Sagnik Das; Ziwen Zhang; Erda Deng; Emmanuel M. Nsengiyumva; Ruveen Dias; Shixian Ha; Xiao Tong; Gbassey S.A. Oteme; Shweta Singh; Kai Chen; Prathima C. Nalam; Chang-Yong Nam; et al. (Chemical Engineering Journal, 2026)

Adaptive strategies of halophytes to saline and freshwater drip irrigation: a focus on transcription factors and metabolic pathways - Haitao Dou; Qiao Xu; Tao Lin; Zewen Tong; Aishajiang Aili; Hailiang Xu (Plant Cell Reports, 2026)

Influence of scCO2–H2O Medium on the Pore and Fracture Structure of Coal at the Time Scale - Zhenyong Zhang; Baiquan Lin; Tong Liu; Ting Liu (Natural Resources Research, 2026)

Restoring aquaculture ponds to coastal wetlands using native vegetation reduces methane (CH4) production and emissions - Wenjing Liu; Hong Yang; Ping Yang; Qitao Xiao; Jujuan Gao; Lihua Wang; Chuan Tong; Yingzi Wang; Pingping Guo; Dongyao Sun; Yongxin Lin; Kam W. Tang (Agriculture, Ecosystems & Environment, 2026)

Calculating flow rate for ceramic emitters in subsurface infiltration irrigation under various soil types based on fractal capillary bundle model - Xuanyue Tong; Pute Wu; Lin Zhang; Xufei Liu; Shoujun Wu (Computers and Electronics in Agriculture, 2026)

QSAR-enhanced machine learning for mechanistic insights and real-time prediction of DBPs in drinking water distribution systems - Dai-Xu Zhang; Tian-Yang Zhang; Zhen-Ning Luo; Zhu Peng; Zheng-Xiong Zheng; Yun-Qiao Zeng; Qi Fu; Ling Hu; Bing Geng; Chao-Yi Tong; Yu-Lin Tang; Bin Xu (Water Research, 2026)

Seismic design and performance of steel boiler-supporting frame with resilient variable friction beam - Yongwei Wang; Lin Yang; Hao Liang; Xiaogang Huang; Chao Tong (Soil Dynamics and Earthquake Engineering, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Oxygen-rich torrefaction of bamboo: Multivariate process optimization and environmental assessment - Wei-Hsin Chen; Yi-Tong Lin; Partha Pratim Biswas; Eilhann E. Kwon; Ting-Chun Tung; Chia-En Lee; Jiří Ryšavý; Jakub Čespiva (Process Safety and Environmental Protection, 2026)

Breaking the trade-off: Trichoderma effector Tahfb1 dual-targets growth and defense pathways via Hsp70L - Yaping Yin; Yuhang Fu; He Wu; Liping Feng; Lijuan He; Runmao Lin; Rui Wang; Zhengbin Tang; Baoping Zhu; Jumei Hou; Jing Zhao; Tong Liu (Pesticide Biochemistry and Physiology, 2026)

Recovery of Fe, Pb, and Zn from jarosite residues and realization of clean production through reduction roasting–grinding magnetic separation–tailings backfilling: effects, mechanisms, and applications - Tong Zhao; Huifen Yang; Dong Lin; Siqi Zhang; Qiwei Sun; Guocui Li (Journal of Cleaner Production, 2026)

Inhibition of cadmium accumulation in wheat from alkaline soil using citric and malic acids - Lu Lin; Fei Tong; Yaoyao Wang; Dongmei Zhou; Xueyuan Gu (Journal of Environmental Sciences, 2026)

The contribution of physical-chemical effects of abandoned mine water to the deterioration of Mode-I fracture toughness- based on CT-DEM integrated modeling - Yang Shen; Baiquan Lin; Minghua Lin; Ting Liu; Tong Liu; Zhiyong Hao; Wei Yang (Geomechanics for Energy and the Environment, 2026)

Enhancing L-aspartate biosynthesis in Escherichia coli through combined pathway engineering and release of feedback inhibition - Daobin Wang; Tong Mu; Jingwen Yang; Xinran Ni; Xiyao Cheng; Jidong Liu; Ying Lin; Ning Li (Food Bioscience, 2026)

Smartphone-assisted portable colorimetric detection of Salmonella based on a dual signal amplification mediated nanozyme cascade aptasensor - Qing Kang; Chenjing Ma; Yidi Liu; Xin Yu; Tong Lin; Jingbo Jiao; Yukun Huang; Shuo Wang; Xinjun Du (Food Bioscience, 2026)

Three-stage neural network modal parameter identification method incorporating physical constraints and its application in concrete dams - Kun Tian; Lin Cheng; Jie Yang; Fei Tong; Chunhui Ma; Zhuolin Li; Bo Li (Engineering Structures, 2026)

Synergistic effect of hydroxyl and superoxide radicals-driven by highly dispersed FeCo-NC dual active sites in singlet oxygen generation in heterogeneous electro-Fenton systems - Xianpeng Li; Tong Zhu; Xianguo Ji; Hao Lin; Zhirong Sun (Chemical Engineering Journal, 2026)

Repairing osteoporotic bone defects under iron overload: A chitosan-hyaluronic acid hydrogel via synergistic iron chelation and ROS responsiveness - Tong Lin; Ziyi He; Tianhao Zhao; Qiaochu Fan; Ruibo Hu; Junhui Jiang; Junbo Dang; Mei Zhang; Dahui Sun (Carbohydrate Polymers, 2026)

Polycyclic aromatic hydrocarbons-induced suppression of the PPARα/ACAA1 axis drives hepatic steatosis: Integrating epidemiology, network toxicology, and experimental validation - Haonan Cui; Peng Zou; Wang Yang; Shijun He; Jinyuan Shi; Ting Sun; Mengge Wang; Zhiyong Song; Hanni Guan; Tong Wang; Lei Sun; Qing Chen; et al. (Chemico-Biological Interactions, 2026)

Microfibril orientation and compositional heterogeneity in fiber and vessel cell walls of poplar xylem studied by AFM-IR and SFG spectroscopy - Jongcheol Lee; Juseok Choi; Yen-Ting Lin; Fangxin Qian; Botong Tong; Quanzi Li; Seong H. Kim (Planta, 2026)
Main conclusion This study demonstrates the use of photothermal AFM-IR and vibrational SFG microscopy to investigate nanoscale chemical heterogeneity and mesoscale cellulose microfibril orientation in hybrid poplar xylem, revealing differences in cellulose microfibril (CMF) orientation between fiber and vessel cell walls that are consistent with their mechanical support and hydraulic functions. Abstract Understanding the structural organization of cellulose microfibrils (CMFs) within individual plant cell walls is essential for connecting cell wall architecture to its mechanical and physiological functions. However, due to the complex hierarchical structure and nanoscale heterogeneity of cell walls, it remains technically challenging to resolve detailed compositional and orientational information at subcellular levels of individual cell walls. This study investigates the internal 3D structure, chemical composition, and sublayer organization of fiber and vessel cell walls in the xylem tissue of a two-year-old field-grown hybrid poplar tree ( Populus alba × P. glandulosa ) using photothermal atomic force microscopy coupled with infrared spectroscopy (AFM-IR) and sum frequency generation (SFG) hyperspectral microscopy. AFM-IR provided nanoscale chemical imaging, revealing localized compositional heterogeneity, including variations between adjacent cell walls and transitional layers beyond the traditional S1, S2, and S3 sublayers. SFG microscopy revealed that CMFs in fiber walls are highly aligned along the stem axis, consistent with their role in mechanical support, while vessel cell walls exhibited slightly tilted CMFs, reflecting their function in hydraulic transport. Together, these results offer new insights into cell-type-specific CMF organization and compositional gradients in hybrid poplar xylem. These findings highlight the structural and chemical complexity of secondary cell walls in woody plants and demonstrate the value of AFM-IR and SFG spectroscopy in elucidating plant cell wall architecture. Graphical abstract .

A review of Potentilla discolor Bunge: ethnomedicinal uses, phytochemistry, and pharmacology - Tong Shen; Jia-Cheng Xie; Yi-Lin He; Hong-Ying Yang (Advances in Traditional Medicine, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Investigation on the Fracture Characteristics and Mechanism of Hard Rock by Microwave Irradiation in Underwater Environment - Feng Lin; Xia-Ting Feng; Tian-Yang Tong; Zhen-Yu Yang; Zi-Yang Wang; Yu-Xi Liu (Rock Mechanics and Rock Engineering, 2026)

Development and Validation of a Multienzyme Isothermal Rapid Amplification Combined with Lateral-Flow Dipstick (MIRA-LFD) Assay for Trypanosoma Strains Circulating in Large Yellow Croaker (Larimichthys crocea) - You Zuo; Bichai Liao; Luoxuan Lin; Tong Wu; Jiahao Yuan; Qianxi Xue; Haiyun Wei; Shuming Liu; Guangliang Huang; Xinhua Chen; Pan Qin (Fishes, 2026)
Trypanosomiasis, caused by flagellated protozoa of the genus Trypanosoma, has recently emerged as a major threat to aquaculture in China, particularly in farmed large yellow croaker (Larimichthys crocea). Outbreaks lead to high mortality rates and severe economic losses. Conventional diagnostic tools, such as blood-smear microscopy and molecular assays including polymerase chain reaction or quantitative polymerase chain reaction (qPCR), are often limited by low sensitivity during early infection or by their dependence on sophisticated instruments and trained personnel, restricting their utility in field conditions. To address these challenges, a multienzyme isothermal rapid amplification (MIRA) assay coupled with a lateral-flow dipstick (LFD) was developed for the rapid detection of trypanosoma strains circulating in L. crocea targeting the 18S ribosomal ribonucleic acid gene. After optimizing primer-probe sets, the assay performance was evaluated using plasmid standards and a panel of common aquaculture pathogens. The MRA-LFD assay consistently detected plasmid DNA at concentrations as low as 0.01 fg/µL (≈2.1 copies/µL) and demonstrated no cross-reactivity with other pathogens. Using clinical DNA samples positive for Trypanosoma, the detection limit was 100 fg µL−1. Validation with 150 tissue samples from fish with and without clinical symptoms demonstrated high diagnostic consistency (94%) with qPCR results, confirming the reliability of the assay. This MIRA-LFD platform provides a sensitive, specific and portable diagnostic tool for early detection of Trypanosoma infections in large yellow croaker, offering valuable support for surveillance and disease management in aquaculture.

A novel phage and its protective effects against Hafnia paralvei in Cyprinus carpio Koi - Lingting Pan; Chenxin Qu; Wencai Liu; Long Tan; Xiaoying Jing; Jinpeng Xu; Wei Lin; Dengfeng Li; Yigang Tong (Aquaculture, 2026)

More frequent precipitation during the maize growth period offsets the yield increasing effect of straw mulching in China: A meta-analysis - Xuanyue Tong; Xufei Liu; Pute Wu; Yuqing Hang; Lin Zhang; Bokun Jia; Jiasen Zhang; Peishen Cai (Soil and Tillage Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Vertical distribution of different phase particles in summer topographic clouds over Liupan Mountain - Tong Lin; Zhiliang Shu; Peiyun Deng; Lei Tian; Yanqiao Sun; Le Jia; Ning Cao; Hanbing Bai (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Associations of concomitant exposure to outdoor light at night, air pollution, and greenness with metabolic syndrome: A cohort study in China - Lisha Xu; Yexiang Sun; Zihan Li; Jiayun Zhang; Yichao Dai; Ye Jiao; Zhanghang Zhu; Jingjing Hu; Jie Qiu; Yixing Wang; Hongbo Lin; Liming Shui; et al. (Environmental Research, 2026)

Insight into the internal microscopic structure and composition of aerobic granular sludge under high salinity based on high-resolution Micro-CT technology - Yuhao Tong; Aqiang Ding; Jun Liu; Lin Quan; Hao Liu; Fuzhong Song; Demin Yang; Daijun Zhang; Peili Lu (Environmental Research, 2026)

Bio-based TEMPO-CNC reinforced Fe-doped UiO-66 with hierarchical porosity for efficient enrofloxacin removal - Dongdong Liu; Shun-xin Chen; Runkai Wang; Lin Li; Jiangyan Ji; Tong Wu; Kunlin Ke; Fei Chai (Environmental Research, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Multiscale modeling and swelling behaviors of Wyoming sodium montmorillonite systems - Zhi-jun Zhang; Jin-xiang Deng; Chang-fu Wei; Ya-kun Tian; Lin Hu; Min Wang; Ling-ling Wu; Kai-wen Tong (Computers and Geotechnics, 2026)

Amplified radiative effects of coated black carbon aerosols over the Tibetan Plateau - Jie Sun; Gang Zhao; Jinyuan Yu; Weili Lin; Yi Chen; Chunxiang Ye; Wenxu Fang; Wenhao Zhou; Baifeng Zhu; Jiawei Yang; Zhijun Wu; Tong Liu; et al. (Atmospheric Research, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

Screening of active constituents in camellia oil against atopic dermatitis via molecular docking and experimental validation: elucidation of the underlying molecular mechanism - Xin Chen; Quanchen Shen; Runcheng Zhou; Yueqiao Lin; Tong Zhou; Kecan Chen; Pengxue Wang; Yanman Chen; Hui Liu; Anping Yang (Inflammopharmacology, 2026)

Soil microbiomes in urban green spaces: Foundation of ecosystem functions and human health - Xiao-Tong Zhu; Xi-Lin Yuan; Pin Li; Congcong Shen (Soil Ecology Letters, 2026)

Polyamide microplastic pollution modifies the sediment fungal structures associated with different submerged plant species: An insight from aquatic mesocosm experiment - Tong Wang; Jingwen Zhang; Xue Yang; Yinuo Zhu; Lin Qi; Mingyan Li; Xiao Guo; Hongwei Yu; Haifang Li (Applied Soil Ecology, 2026)

Design of asymmetric combined flow-guiding valve core structure in hydraulic spool valve - Zhao-tong Wang; Wen-qing Li; Xu-han Wang; Tong An; Zhen-hao Lin; Zhi-jiang Jin; Jin-yuan Qian (Annals of Nuclear Energy, 2026)

Carbon mineralization and temperature sensitivity of particulate versus mineral associated organic matter in a 56-year long-term no-till Vertisol - Cong He; Ram C. Dalal; Tong Li; Hai-Lin Zhang; Yash Pal Dang (Agriculture, Ecosystems & Environment, 2026)

Dynamics and control of geocentric displaced orbits for graphene-reinforced solar sails - Yunan Tong; Jixin Ding; Lin Chen; Ming Xu (Advances in Space Research, 2026)

Two new clerodane diterpenoids and their anti-inflammatory activity from Callicarpa integerrima - Muhammad Aurang Zeb; Xiao-Ying Ruan; Xing-Jie Zhang; Yu-Tong Xing; Meng-Ru Wang; Yuan-Lin Kong; Xiao-Li Li; Kai Jiang; Wei-Lie Xiao (Natural Product Research, 2026)

Post-cyclic undrained behaviour of marine soft clay under cyclic loading with variable confining pressure - Junhao Tong; Dongyang Yuan; Changjun Li; Haozheng Wang; Dingyu Ni; Ke Wu; Pixian Si; Qiang Wang; Lin Guo (Marine Georesources & Geotechnology, 2026)

Identification and transcriptomic analysis of a new pathogen, Photobacterium damselae SCXP, associated with sea cucumber skin ulceration syndrome - Linwei Yang; Shuming Liu; Hui Lv; Haiyun Wei; Tong Wu; Bilian Lou; Jingsong Yang; Qingmei Huang; Yuxin Shi; Tongxin Lin; Zhengwei Cui; Xinhua Chen; et al. (Aquaculture, 2026)

Optimising light intensity and ammonium enrichment enhances ex-situ growth and survival of the cultured boring Giant clam, Tridacna crocea - Li Keat Lee; Teresa S. Tay; H.R. Samuel Lee; K.E. Kayden Tong; M.Y. Beryl Chean; Yuchen Sun; Mei Lin Neo (Aquaculture, 2026)

Enhancing oil-water separation via droplet coalescence regulated by particle self-rotation in swirling fields - Wei Zhao; Ao-song Wei; Shu Zhu; Tong Zhang; Peng-bo Fu; Jian-ping Li; Xue-jing Yang; Hua-lin Wang (Water Research, 2026)

Fatigue investigation of tubing string caused by fluid-structure interaction in three-high gas wells - Tong Luo; Yao Liu; Tiejun Lin; Zhanghua Lian; Dingjiang Xu; Bo Pan (Ocean Engineering, 2026)

Material, microbial and metabolism pathway perspectives on understanding the nitrogen/iron co-doped biochar enhanced methane production in brewery wastewater anaerobic digestion - Junguo He; Yili Wang; Yuanyi Zhao; Heliang Pang; Lin Li; Yunlong Liu; Xinxin Cui; Tong Wei; Suiyin Yu (Journal of Water Process Engineering, 2026)

Methanogenic efficiency of anaerobic digestion under sulfaquinoxaline sodium (SQ-Na) stress: Insights from enzyme, microbial community and metagenome analyses - Junguo He; Yuanyi Zhao; Heliang Pang; Yili Wang; Lin Li; Yunlong Liu; Xinxin Cui; Tong Wei; Shengye Duan; Suiyin Yu (Journal of Water Process Engineering, 2026)

Simultaneous immobilization of arsenic and cadmium in paddy soil with co-application of birnessite and lime - Jianyu Lin; Fei Tong; Wanli Chen; Xinyue Hu; Dongmei Zhou; Xueyuan Gu (Journal of Hazardous Materials, 2026)

Diffusion behavior and potential risk of intestinal pathogenic bacteria and chemicals in aerosols from outdoor desilting basin of six urban sewage treatment plants - Tong Gao; Wenwen Wang; Lin Li; Jianwei Liu (Journal of Hazardous Materials, 2026)

Ammonia emission from real-world in-use vehicle fleets in a megacity in China - based on tunnel measurement - Jiliang Guo; Jinsheng Zhang; Ainan Song; Hui Tong; Jingchun Tang; Ning Yang; Zhuofei Du; Qijun Zhang; Ting Wang; Lin Wu; Jianfei Peng; Hongjun Mao (Journal of Environmental Sciences, 2026)

Method for predicting the microwave heating sensitivity of hard rocks: Application to microwave-mechanical excavation and microwave stress release in tunnels - Shiping Li; Xia-ting Feng; Chengxiang Yang; Feng Lin; Xiangxin Su; Tianyang Tong; Jiuyu Zhang (Journal of Applied Geophysics, 2026)

Bioaerosols from outdoor wastewater treatment facilities: dispersal behavior, exposure risks and protection strategies - Jingyun Ge; Tong Gao; Huili Li; Zhongcai Lun; Changren Yan; Caixia Li; Yanjie Wang; Lin Li (International Journal of Hygiene and Environmental Health, 2026)

Amplifying 2′3′-cGAMP with “open source throttling” strategy: Intelligent nanoreactors enhance immunotherapy in HNSCC via cascade activation of the cGAS-STING pathway - Tong Sha; Ze Wang; Jinwei Li; Yahong Wu; Xiaoyi Yu; Jinbiao Qiang; Annan Liu; Hao Liang; Zunxuan Xie; Yijun Zhou; Hongchen Sun; Andrew K. Whittaker; et al. (Chemical Engineering Journal, 2026)

Techno-economic analysis of offshore green methanol production in South China Sea - Dong Lin; Liyu Zhang; Chenxi Pan; Haitao Hu; Jia Yang; Bo Tong; Zhiyu Li; Xin Zhang (Chemical Engineering Journal, 2026)

Mechanisms of bioelectrochemistry enhanced saline aerobic granular sludge: From EPS monomers to microbial metabolism - Aqiang Ding; Shikang Li; Wenkai Yao; Yuhao Tong; Lin Quan; Chun Yang; Fuzhong Song; Daijun Zhang; Peili Lu (Chemical Engineering Journal, 2026)

Unveiling the effects of reactor configurations on the performance of lignin removal in the ozone micro-nano-bubble system - Yin Lu; Xuyin Yuan; Haiming Kan; Chi Zhang; Lin Chen; Alessandro Gottuso; Francesco Parrino; Tong Li; Shishu Zhu; Dawei Wang (Chemical Engineering Journal, 2026)

Moisture-driven cracking triggers gully sidewall collapse: identifying critical thresholds in frozen Mollisols - Bao Liu; Yanru Wen; Litao Lin; Seyed Hamidreza Sadeghi; Tong Zhou; Xinhua Peng (CATENA, 2026)

Walkability, fine particulate matter and risk of Osteoporosis: A cohort study in China - Jie Qiu; Peng Shen; Jingjing Hu; Zhanghang Zhu; Lisha Xu; Jiayun Zhang; Zihan Li; Hongbo Lin; Liming Shui; Feng Tong; Kun Chen; Jianbing Wang (Atmospheric Environment, 2026)

Esculin Alleviated NLRP3 Inflammasome Activation by Inducing PINK1/Parkin-Mediated Mitophagy in Cerebral Ischemia–Reperfusion Injury - Jinyu Lin; Bowen You; Xin Yang; Xue Li; Wenjuan Sun; Zhongyu Xu; Yi Zhang; Xuhui Tong; Shuying Dong (Molecular Neurobiology, 2026)

3-n-Butylphthalide Protects SH-SY5Y Cells from Ferroptosis by Inhibiting ACSL4-Mediated Lipid Peroxidation - Huanhuan Wei; Yiyin Zhang; Qianqian Ju; Bolin Lian; Tong Gao; Haiqin Duan; Xiang Yin; Yongqi Lin; Jianhong Shen; Qiuhong Ji; Cheng Sun; Lihua Shen (Molecular Neurobiology, 2026)

Enhanced spring precipitation in central Asia induced by ENSO under global warming - Lin Sun; Yanting Zhang; Xiao-Tong Zheng (Climate Dynamics, 2026)

Rapid nitrogen removal in sandy beaches driven by periodic tidal inundations - Lin Wei; Pinghe Cai; Qingquan Hong; Tong Wu; Wei Liu; Yilin Cheng; Pingping Mi (Limnology and Oceanography, 2026)
Sandy beaches are an important passage for the transport of various forms of nitrogen from land to sea. However, export fluxes of these forms of nitrogen and the mechanisms controlling their transformation remain elusive. Using the 224 Ra/ 228 Th disequilibrium approach, we estimated export fluxes of dissolved inorganic carbon and dissolved inorganic nitrogen at three intertidal sandy beaches with distinct slopes along the southeast China's coast. We identified that sandy beaches are a hotspot of nitrogen loss in the coastal ecosystem, with nitrogen removal rates reaching up to 87.1 mmolN m −2 d −1 and removal efficiencies varying between 7% and 82%. Notably, nitrogen removal rates peaked at intermediate seawater percolation fluxes, reflecting the optimal balance of oxygen consumption, marine organic matter remineralization, and nitrate production for fueling denitrification in the beach's interior. In addition, total nitrogen removal increased with beach slopes. This is likely due to the fact that steeper beaches facilitate seawater to percolate more efficiently into the beach's interior and travel along a longer flow path before it drains out, thus allowing denitrification to prevail. Overall, our field observations reveal that instead of the surface “skin circulation,” the “body circulation” system within an intertidal beach governs fluid transport and solute exchange between land and sea. We conclude that intertidal sandy beaches function as an efficient biogeochemical reactor, which attenuates anthropogenic nitrogen inputs to the coastal ocean.

Two new phenylethanol glycosides from the roots of eleutherococcus senticosus (rupr. et maxim.) maxim - Jia-Tong Wu; Ke Xiao; Hao-Lin Yang; Hui-Chen Zhu; Si-Yi Wang; Juan Pan; Meng-Meng Li; Wei Guan; Hai-Xue Kuang; Yan Liu (Natural Product Research, 2025)

Tunable surface potential nanomaterials for enhanced environmental nucleic acid extraction and surveillance - Jiahui Lv; Tong Li; Ying Liu; Bing Li; Peng Jia; Chuwei Ma; Hongjun Xiao; Guanghui Wang; Li Cheng; Jingkai Yang; Ziyi Xu; Xuan Tan; et al. (Water Research, 2025)

A novel carbon-negative side-stream MBMBR process for municipal wastewater reclamation driven by biopolymer and nutrient recovery - Haifeng Zhang; Yi Zhang; Lin Li; Changqing Liu; Shujuan Huang; Tong Yu; Dong-Hoon Kim; Seoktae Kang; Boyan Xu; Xueqing Shi; How Yong Ng (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Characterisation of the evolution of the main controlling factors of methane time-domain diffusion in porous media coals: Theoretical model and experimental verification - Kai Wang; Lin Guo; Chao Xu; Wenjing Wang; Tong Yang; Yongwang Yuan; Yuanyuan Hu (Process Safety and Environmental Protection, 2025)

Labdane-type diterpenoids from Hypoestes phyllostachya inhibit pancreatic cancer stem cells - Tong Yan; Lin-Fen Ding; Ya Chen; Guo-Xian Hu; Lu Qu; Ming Hu; Ya-Xuan Ma; Rong-Qing Yuan; Lin Jia; Mei-Ju Zhao; Liu-Dong Song; Jia Su; et al. (Phytochemistry, 2025)

Model tests of hydrodynamic derivatives of a polygonal semi-submersible floating platform - Tong-Lin Chen; Chen-I Lee; Tsung-Yueh Lin (Ocean Engineering, 2025)

Intra-oceanic arc subduction within the Meso-Tethys Ocean constrained by arc crust remnants in the Lagkorco ophiolite, Central Tibet - Wei-Qi Zhang; Chuan-Zhou Liu; Tong Liu; Xiao-Ni Li; Chang Zhang; Zhen-Yu Zhang; Zhen Zhang; Yin-Zheng Lin (Lithos, 2025)

Groundwater modulates nutrient dynamics in a freshened saltmarsh tidal creek - Jianan Liu; Xueqing Yu; Tong Peng; Xinyi Lin; Jinzhou Du (Marine Chemistry, 2025)

Perinatal maternal lead exposure induces intergenerational neurotoxicity via mitochondrial dysfunction and mediation by perturbation of thyroid function - Lin Zhang; An-Xin Lu; Ling Li; Qian Wei; Yin Lin; Jun-Xia Liu; Li Ma; Ren-Tong Chen; Bin Luo; Chong-Huai Yan (Journal of Hazardous Materials, 2025)

Color-categorized microplastics in rivers and lakes: Global distribution, driving mechanisms, and ecological risks unveiled by interpretable machine learning - Tianqi Jiang; Guangshuo Chai; Qiong Guo; Haoran Peng; Yuexia Guo; Xiaohui Zhang; Yan Lin; Hongyang Cui; Xiaoyu Cui; Yindong Tong (Journal of Environmental Chemical Engineering, 2025)

Mechanism of piezoelectric field-enhanced electron transfer during peroxymonosulfate activation with MoS2/PVDF-HFP films - Tingting Cao; Liping Lin; Yanan Li; Wangshu Tong (Journal of Environmental Chemical Engineering, 2025)

Non-homogeneous characterisation of nanopore structures in low-, medium- and high-rank coals based on gas adsorption and multifractal theory - Chao Xu; Wenjing Wang; Kai Wang; Lin Guo; Tong Yang; Zishuo Nie; Yongbo Shi (Fuel, 2025)

Nanoparticles-based lateral flow immunochromatographic strip for detection of foodborne pathogen: A review - Silu Hou; Tong Lin; Ziyi Ding; Shuxin Cui; Yafei Cao; Jingbo Jiao; Qing Kang; Xinjun Du (Food Chemistry, 2025)

Ultrathin NiSe2/Co3Se4 heterojunction nanosheets for electrochemical detection of foodborne formaldehyde - Yiting Yan; Fanghua Liu; Zihan Liu; Lin Yang; Miao Hu; Jun Zhang; Tong Xu; Yongjian Ai; Xue Jiang (Food Chemistry, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Functional characterization of the heat shock protein gene hsp78 in regulating carotenoid biosynthesis in the edible-medicinal fungus Cordyceps militaris - Zi-Qing Liang; Yi Zhao; Yong-Zhi Tan; Jie Wang; Yi-Lu Shao; Qian-Wang Zheng; Yuan Zou; Jun-Fang Lin; Mou-Tong Chen; Zhi-Wei Ye (Food Bioscience, 2025)

LPS disrupts erythroid-myeloid balance in zebrafish via Jak2/Stat3-Hif1a signaling - Hai-Chuan Yu; Meng-Yao Chen; Shuang-Ling Zhang; Fang-Chao Tong; Fan-Ping Wang; Lin Wang; Jia-Long Zhang; Jiao-Jie Guo; Bing-Yang Zhang; Jia-Qi Tian; Jiao Wu (Fish & Shellfish Immunology, 2025)

Mechanical performance of an assembled 3D auxetic hybrid structure under eccentric and axial compression - Jia Shuo Liu; Yi Zhang; Xiang Jie Wei; Wei Zhong Jiang; Meng Li Xue; Yi Chao Qu; Tao Ding; Jia Hui Zhang; Lin Hua; Tong Cheng; Xin Ren (Engineering Structures, 2025)

Interaction between layered mantle flow and progressively thinned lithosphere beneath the Armenia Volcanic Highland: Evidence from seismic azimuthal anisotropy - Jing-Hui Tong; Tai-Lin Tseng; Pei-Ying Patty Lin; Khachatur Meliksetian; Shuo-Fen Chang; Bor-Shouh Huang; Elya Sahakyan; Mikayel Gevorgyan; Lilit Sargsyan (Earth and Planetary Science Letters, 2025)

Fungal mycelial pellet as a biosponge for bacterial immobilization: A novel biocarrier for synergistic adsorption-degradation of PAHs - Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Wang Kai Tong; Hong Cheng Zhang; Min-tian Gao; Yalei Zhang; Zhi Li; Kah Hon Leong; Lang Zhou; Ken-Lin Chang; Swee Pin Yeap (Chemical Engineering Journal, 2025)

An enhanced nanoenzyme for remodeling the inflammatory microenvironment and low-temperature photothermal cascade therapy for rheumatoid arthritis - Sui Zhou; Yong Li; Yi-Tong Zhou; Meng-Wen Ma; Kai-Lin He; Kai Cheng; Jin-Xuan Fan; Bo Liu; Ling-Li Dong; Yuan-Di Zhao; Xin Liu (Chemical Engineering Journal, 2025)

Novel compound bacterial agent effects on pig farm wastewater denitrification and nitrogen transformation - Rong Gao; Zhuangzhuang Liu; Weikun Li; Liu Lou; Tong Xu; Lin Shi; Jie Cao; Jun Fang; Gang Liu (Bioresource Technology, 2025)

Temporal variations in the long–term effects of ambient PM2.5 components on pulmonary tuberculosis incidence in mainland China during 2004–2018 - Kang Ma; Fengman Fang; Yuesheng Lin; Xiuya Xing; Youru Yao; Fei Tong (Atmospheric Pollution Research, 2025)

Body Composition-Derived Subtypes in Tibetan Adults Residing at Qinghai-High Plateau and Their Associations with Distinct Metabolite Profiles and Cardiometabolic Outcomes - Tiemei Li; Lin Shi; Qingxia Huang; Ruijie Xu; Bin Zhang; Dan Zhang; Qi Wang; Haijing Wang; Li Tong; Huiru Tang; Youfa Wang; Wen Peng (Phenomics, 2025)

SOX11-mediated CBLN2 Upregulation Contributes to Neuropathic Pain through NF-κB-Driven Neuroinflammation in Dorsal Root Ganglia of Mice - Ling-Jie Ma; Tian Wang; Ting Xie; Lin-Peng Zhu; Zuo-Hao Yao; Meng-Na Li; Bao-Tong Yuan; Xiao-Bo Wu; Yong-Jing Gao; Yi-Bin Qin (Neuroscience Bulletin, 2025)
Neuropathic pain, a debilitating condition caused by dysfunction of the somatosensory nervous system, remains difficult to treat due to limited understanding of its molecular mechanisms. Bioinformatics analysis identified cerebellin 2 (CBLN2) as highly enriched in human and murine proprioceptive and nociceptive neurons. We found that CBLN2 expression is persistently upregulated in dorsal root ganglia (DRG) following spinal nerve ligation (SNL) in mice. In addition, transcription factor SOX11 binds to 12 cis -regulatory elements within the Cbln2 promoter to enhance its transcription. SNL also induced SOX11 upregulation, with SOX11 and CBLN2 co-localized in nociceptive neurons. The siRNA-mediated knockdown of Sox11 or Cbln2 attenuated SNL-induced mechanical allodynia and thermal hyperalgesia. High-throughput sequencing of DRG following intrathecal injection of CBLN2 revealed widespread gene expression changes, including upregulation of numerous NF-κB downstream targets. Consistently, CBLN2 activated NF-κB signaling, and inhibition with pyrrolidine dithiocarbamate reduced CBLN2-induced pain hypersensitivity, proinflammatory cytokines and chemokines production, and neuronal hyperexcitability. Together, these findings identified the SOX11/CBLN2/NF-κB axis as a critical mediator of neuropathic pain and a promising target for therapeutic intervention.

Predicting internal carotid artery system risk based on common carotid artery by machine learning - Yuhao Tong; Qingyi Zhang; Feng Zhang; Weidong Mu; Steven W. Su; Lin Liu (Medical & Biological Engineering & Computing, 2025)

The epidemiological trends of inflammatory bowel disease among women of reproductive age: a global analysis from 1990 to 2021 - Zhenzhen Fan; He Zhou; Lianlian Tian; Tong Wu; JiaQi Zhang; Junchao Lin; Chen Wang; Jindan He; LiuQing Zhao; Jie Chen; Jie Liang (Immunologic Research, 2025)

Controls over soil water-extractable organic matter quantity and biodegradability in alpine coniferous forests of Southwest China - Le-Lin Yu; Qi-Tong Wang; Hua-Jun Yin; Rong Mao (European Journal of Forest Research, 2025)

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Submarine groundwater discharge governs dissolved carbon cycling: Multi-scale evidence from a large river-dominated groundwater-saltmarsh-estuary system - Jianan Liu; Liying Lin; Xueqing Yu; Xiaogang Chen; Tong Peng; Xinyi Lin; Xunchi Zhu; Jinzhou Du (Marine Pollution Bulletin, 2025)

Cetyltrimethyl ammonium bromide-assisted construction of ferrous oxalate-derived graphitic carbon confined iron-based nanocluster materials for persulfate activation - Hao Sun; Wenyu Xu; Yida Wang; Chenyunuo Zhu; Jawaria Fatima; Kun-Yi Andrew Lin; Shaoping Tong (Journal of Water Process Engineering, 2025)

Maximizing removal efficiency via magnetite dosage in bio-Fenton SBR - Chenyang Lin; Tong Shen; Yuga Yoneyama; Yoshihiko Inagaki; Yutaka Sakakibara (Journal of Water Process Engineering, 2025)

Community and functional succession of corrosive microorganisms during flowback and produced water management in Sichuan Basin - Jiayi Qing; Aqiang Ding; Zhengming Hou; Lin Quan; Yuhao Tong; Junou Pan; Xiong Li; Peili Lu (Journal of Water Process Engineering, 2025)

Evaluating impacts of hydrology and pollution loadings on low dissolved oxygen in an urbanized tidal river network using modeling and monitoring - Heng Zhang; Jiahuan Liu; Tong Li; Siyu Zhang; Zhongyuan Lin; Zhengbo Jia; Wenping Gong; Guang Zhang (Journal of Hydrology, 2025)

Ecological restoration in plateau pika-disturbed alpine meadows: Soil-microbe-enzyme stoichiometry and microbial adaptations during vegetation recovery of bare patches - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Journal of Environmental Management, 2025)

Anthropogenic disruption of sediment connectivity by embankment dams in the fast-eroding badland basin - Ci-Jian Yang; Cheng-Hua Tsai; Ying-Tong Lin (Geomorphology, 2025)

Association of compound exposure to heat wave and ozone pollution with cause-specific cardiopulmonary mortality: A space-time-stratified case-crossover study - Kang Ma; Fengman Fang; Yuesheng Lin; Fei Tong; Cheng He; Youru Yao; Jingli Zhu; Huadong Wang; Xiuya Xing; Feiyan Zhang; Ruoxi Li (Environmental Research, 2025)

VOCs emission from landfills co-disposed of rural solid waste and sewage sludge: Identification, diffusion, and impact - Tong Gao; Chen Wang; Fengguang Chai; Tianlong Zheng; Lin Li (Environmental Research, 2025)

An equivalent spring model for evaluating the wind-resistance capacity of low-vertical 360° standing seam metal cladding systems - Min Liu; Changhong Tong; Shidong Nie; Qisheng Liang; Shuitao Gu; Qingshan Yang; Shihua Chen; Zuoyong Lin (Engineering Structures, 2025)

Biofilm management via loach predation: An eco-friendly approach to enhance membrane performance in wastewater treatment - Weijia Gong; Xianwu Liu; Yuzhou Zhao; Mengmeng Jiang; Lin Guo; Le Tong; Jinyan Lu; Jiaxuan Yang; Heng Liang; Xiaobin Tang (Chemical Engineering Journal, 2025)

General strategy for efficient persistent RTP polymer over 3 s: luminophore with a moderate θn-π angle - Danman Guo; Tong Zou; Yiling Miao; Jinzheng Chen; Zhu Chen; Xiangyu Ge; Faxu Lin; Yi Zhang; Zhenguo Chi; Zhiyong Yang; Huahua Huang (Chemical Engineering Journal, 2025)

Polyvinylidene fluoride/polysulfone nanofiber membranes with dual high-efficiency and self-regenerating filtration for solid-oil aerosols - Le Xu; Peng Jiang; Lu Peng; Chaochen Cai; Yongji Lu; Zhenyu Zhu; Hongxia Wang; Xin Wei; Tong Lin (Chemical Engineering Journal, 2025)

Efficient removal of antibiotics and synthetic dyes using VTMS-functionalized N/S-GQDs-PVA/cellulose composite aerogels - Muhammad Yousif; Meiling Zhang; Bilqees Hussain; Xupin Zhuang; Zhangang Wang; Hongxia Wang; Tong Lin (Chemical Engineering Journal, 2025)

Constructing phase interface in membranes of ultralong layered VxOy nanobelts for exceptional EMI shielding, thermal management, waterproofing, and strain sensing applications - Siyu Xie; Kang Fu; Qian Lin; Ziyi Wu; Junhao Diao; Sirun Yu; Shuhan Huang; Liyan Xie; Guoxiu Tong (Chemical Engineering Journal, 2025)

Genotypic diversity and genome-wide association study of phosphorus content, amylose content, pasting, and textural properties of potato starch - Daraz Ahmad; Lin Zhang; Yan Gao; Yaqi Hu; Bowen Deng; Chuan Tong; Jinsong Bao (Carbohydrate Polymers, 2025)

Effects of plateau pika disturbance on soil net nitrogen mineralization from small to large scales in alpine meadows - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (CATENA, 2025)

The correlation between novel antidiabetic agents utilization and hepatocellular carcinoma incidence in type 2 diabetes patients: a network meta-analysis - Junjie Lin; Tianshu Ren; Qingchun Zhao; Qiang Tong; Jiahui Liu; Ye Kang; Yuan Yuan (European Journal of Clinical Pharmacology, 2025)

Positive effects of gamma aminobutyric acid on growth and lipopolysaccharide-induced intestinal mucosal barrier damage in snakehead (Channa argus) - Xue-qin Wu; Xu-nan Li; Feng-kun Cai; Yun-jie Lin; Xiao-tian Niu; Xiu-mei Chen; Yan-nan Tong; Gui-qin Wang (Aquaculture International, 2025)

Biotransformation of oleanonic acid by circinella muscae to produce novel 11,12-epoxy-13,28-lactonized derivatives and their anti-neuroinflammatory activity - Wei Liu; Li Yang; Liu-Tong Guan; Jia-Hui Wang; Yao-Yu Liu; Yan Song; Jian-Lin Li; Wen-Li Wang; Bo-Yi Fan; Guang-Tong Chen (Natural Product Research, 2025)

Preparation of sludge derived fuels for co-incineration in waste incinerators: Industrial tests and life cycle assessment - Yanfei Lin; Hanqiao Liu; Guoxia Wei; Tong Li; Qianlong Han; Zilu Liu; Xinrui Su; Yifan Chen (Sustainable Production and Consumption, 2025)

Corrigendum to ‘Isolation of undescribed cladosporols and spirobisnaphthalenes from a plant pathogen Cladosporium cladosporioides F-10-2-A’ [Phytochemistry. 222 (2024) 114073] - Peng Li; Zi Jin Zhang; Yu Tong Guo; Jing Guan; Lin Bo Wen Xi; Li Ping Lin (Phytochemistry, 2025)

Two pairs of isomeric resin glycosides from Argyreia obtusifolia - Shuo Chen; Yi-Lin Niu; Zhi-Tong Li; Hong-Hua Cui; Yong-Qin Yin; Yan-Fen Chen (Phytochemistry Letters, 2025)

Coastal creeks as greenhouse gas hotspots: the role of nutrient availability and microbial activity - Guanpeng Chen; Jianuo Gao; Ping Yang; Wenjing Liu; Dongyao Sun; Yongxin Lin; Chuan Tong; Wenjing Tan; Pingping Guo; Hong Yang (Journal of Hydrology, 2025)

SiO2 NP promotes allergic gastritis induced by degranulation of mouse MC9 cell through AQP4-mediated impairment of SIRT3-TFAM deacetylation and mitochondrial autophagy - Yutian Lei; Xiaodan Wang; Hao Wu; Meichen Gao; Tong Xu; Hongjin Lin (Journal of Hazardous Materials, 2025)

Contrasting effects of different acid rain types on soil nitrogen pools - Xingyu Pan; Yi Jian; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Hongwei Xu; Sining Liu; Lixia Wang; et al. (Journal of Environmental Management, 2025)

Performance and mechanism study for 2-octanol oxidation by ozone in synergy with biochar supported manganese-based mullite catalysts - Lin Zhang; Huanzhen Zuo; Tong Wei; Wenming Pei; Xinsheng Zhu; Feng Ge; Kegui Zhang (Journal of Environmental Chemical Engineering, 2025)

Defect-engineered graphene driven mercury oxidation in coal-fired flue gas via in-situ electro-Fenton catalysis - Xin Tong; Changxian Yang; Minsong Lin; Xinxing Zhan; Lingyun Zhou; Yadian Xie; Juan Tian; Gaixia Zhang; Shuhui Sun (Journal of Environmental Chemical Engineering, 2025)

Stable two dimensional copper(II) based metal-organic framework as an efficient peroxymonosulfate activator for tetracycline degradation - Jia-Ting Chen; Wan-Yi Wang; Si-Tong Chen; Wen-Bin Chen; Yan-Yong Lin; Meng Yang; Wen Dong (Journal of Environmental Chemical Engineering, 2025)

Study on the graded thermal response and microstructure damage evolution of coal under microwave radiation - Yihan Wang; Wei Yang; Yuting Zhong; Baiquan Lin; Tong Liu (Journal of Environmental Chemical Engineering, 2025)

Non-monotonic effects of sulfidation on the aggregation behavior of surface-coated silver nanoparticles - Jiameng Liu; Tianchi Cao; Botao Li; Xiaoxia Zhang; Lin Duan; Tong Zhang; Wei Chen (Journal of Environmental Sciences, 2025)

Orientation construction and comparison of mercury removal sites by physical and chemical adsorption on cotton stalk biochar - Guoliang Li; Shuxiao Wang; Qingru Wu; Tao Yue; Jiajia Gao; Yali Tong; Mingyu Zhang; Lin Zhang; Chenyang Zhang; Sizhe Xie (Fuel, 2025)

Optimizing 3D food printing inks: The impact of polysaccharides on Camellia seed protein emulsion gels - Jiaru Lin; Chenhao Liang; Tong Lin; Ruimin Zhong; Yong Cao; Yaqi Lan (Food Hydrocolloids, 2025)

Ball milling boron-doped biochar-based zero-valent iron composite for the removal of Cr(VI) from contaminated farmland: Performance and mechanisms - Hui Zhang; Yingrui Hu; Qiutong Lin; Wenqi Zhang; Siqi Wang; Haoming Li; Ruihan Tong; Jianhua Qu; Ying Zhang (Chemical Engineering Journal, 2025)

Crystallization regulation and defect passivation of perovskite films via resonance-structured ionic additive for high-performance solar cells - Guogen Huang; Yuqing Dong; Guanlin Li; Zebing Gao; Chuanlin Gao; Kangbo Sun; Haoxuan Zeng; Haohua Wu; Jinxing He; Xinting Wang; Qing Bai; Tong Shan; et al. (Chemical Engineering Journal, 2025)

Joule heating-driven efficient catalytic oxidation of chlorobenzene over MnCe-nickel foam: A flexible and energy-efficient strategy - Fanxiang Meng; Yunfeng Ma; Xiaojun Ma; Ling Wang; Feiyi Zhou; Bingcheng Lin; Rong Jin; Minghui Zheng; Chen Sun; Tong Chen (Chemical Engineering Journal, 2025)

Recycling of sub-continental lithosphere during early ocean spreading revealed by Triassic trachytes in the central Tibetan Plateau - Zong-Yong Yang; Qiang Wang; Jun Wang; Lin Ma; Derek Wyman; Andrew C. Kerr; Xian-Wu Bi; Peng Sun; Xiu-Zheng Zhang; Lu-Lu Hao; Xiao Liu; Chuan-Bing Xu; et al. (Chemical Geology, 2025)

Senegenin ameliorates diabetic encephalopathy via promoting mitophagy and repressing NLRP3 inflammasome activation - Xiao-dan Yan; Yu Yang; Wan-ting Zhang; Qing-quan Kong; Xi-tong Zheng; Lin-sen Li; Qing Yu (Psychopharmacology, 2025)

Low-intensity pulsed ultrasound enhances delivery of 30 nm Q10 for improving mental and memory disorder in APP/PS1 mice - Qi Luo; Xuanjie Ye; Jinan Xu; Zihui Sun; Panpan Wang; Haishu Chen; Tingting Gao; Qiangfeng Deng; Ziwen Wang; Qin Wang; Xiaoxiao Chen; Zhuowen Zhao; et al. (Drug Delivery and Translational Research, 2025)

Construction of a Machine Learning-Based Clopidogrel Resistance Risk Prediction Model - Ruo-Ying Wang; Shui-Di Yan; Jian-Qi Zeng; Tong Mu; Ya Yan; Yuan-Yi Zhao; Lin Xie; Li-Li Liu (Cardiovascular Toxicology, 2025)

Anthropogenic land-use driven changes in soil stoichiometry reduce microbial carbon use efficiency - Xinle Tong; Lichao Fan; Mingda Wang; Jingjing Guo; Lei Bao; Lingzhi Hui; Yichao Chen; Zhengrong Li; Shuai Qian; Xiaodong Xu; Lin Ma; Xiangtian Meng; et al. (Agriculture, Ecosystems & Environment, 2025)

Antibacterial activity of pimaradienoic acid from Eleutherococcus trifoliatus (L.) S. Y. Hu - Deng Hongxian; Zhang Mengyu; Xiao Lin; Li Huanhuan; Xu Shiqi; Zeng Si; Luo Luncai; Jiang Hezhong; Tong Yan (Natural Product Research, 2025)

Spatial heterogeneity in the joint effect of heat wave and ozone pollution on mortality at the township-level in China - Kang Ma; Fengman Fang; Yuesheng Lin; Fei Tong; Cheng He; Youru Yao; Jingli Zhu; Huadong Wang; Xiuya Xing (Sustainable Cities and Society, 2025)

Seven previously undescribed steroidal alkaloids from the fruit of Solanum nigrum L. and their biological activities - Liang-Yu Liu; Qing Peng; Yu-Ke Yang; Tong Wu; Li-Xian Chen; Li Lin (Phytochemistry, 2025)

Why is the combined treatment of copper and aluminum more toxic to citrus than single factor treatment? - Wen-Shu Chen; Ti Wu; Tian-Tian Xia; Liang-Yuan Tong; Fei Lu; Xin Ye; Jiuxin Guo; Zeng-Rong Huang; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2025)

Efficient recovery of spent catalysts in PAO production via annular drainage hydrocyclone: a sustainable approach for fluorinated waste reduction - Wei Zhao; Jian-ping Li; Tong Zhang; Shu Zhu; Ao-song Wei; Dan-hui Yang; Xue-jing Yang; Hua-lin Wang (Journal of Cleaner Production, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

A systematic study of pipe and electrical connections for multi-stack vanadium redox flow battery modules considering electrolyte transport delays - Shaojin Wang; Yang Li; Chengyan Li; Xifeng Lin; Wenbo Ma; Nannan Tong; Binyu Xiong (Chemical Engineering Journal, 2025)

Field Tests Using High-Power Microwaves to Crack Iron Ore of Different Grades - Feng Lin; Xia-Ting Feng; Shi-Ping Li; Tian-Yang Tong; Yun-Tan Ao; Yu-Xi Liu (Rock Mechanics and Rock Engineering, 2025)

Rheinheimera fenheensis sp. nov., Isolated from Fenhe River Basin, China - Xuan Shao; Yun-Lin Peng; Jin-Hang Guo; Zhao-Tong Chen; Hua-Ming Zhong; Di Meng; Hong-Jian Hou; Xi-Ying Zhang; Yong Zhao; Yi Li (Current Microbiology, 2025)

Impact of Spartina alterniflora invasion and aquaculture reclamation on soil aggregate stability and carbon sequestration in Chinese coastal wetlands - Yanxun Xu; Wenjing Liu; Yule Lin; Hong Yang; Ping Yang; Guanpeng Chen; Dongyao Sun; Chuan Tong; Linhai Zhang; Wanyi Zhu; Kam W. Tang (Soil Ecology Letters, 2025)

Whether aristolochic acid directly drives hepatocarcinogenesis: comprehensive investigations from mutational signatures to animal models - Lu Yang; Wanjun Lin; Meina Shi; Zifeng Huang; Xuening Zhang; Yanchao Yang; Tong Chu; Dayuan Zheng; Dongfan Yang; Wenzhe Ma (Archives of Toxicology, 2025)

Speciation Caught in the Act: Derived Ciliary Patterns Budded Off From the Oxytricha granulifera ‐Like Lineages (Alveolata, Ciliophora) - Linger Lu; Tian Wang; Lingzhi Ye; Zhangwen Tong; Zina Lin; Xiaotian Luo; Thiago da Silva Paiva; Xinpeng Fan (Zoologica Scripta, 2025)
Oxytricha is a well‐known ciliate genus having a long, but convoluted taxonomic history, which aside from its non‐monophyly and subsequent dismembering into other genera, has a major issue: the type species O. granulifera is consistently paraphyletic. To understand their paraphyly in the context of our perception of species and genera according to the integrated taxonomy concept, we evaluated the phylogenetic status of different O. granulifera ‐like populations using nuclear and mitochondrial genes. We demonstrate that in the clade formed by O. granulifera and its closely related species, which we designate as the ‘OAN‐clade’, O. granulifera populations have diverged into distinct sub‐clades; and these sub‐clades also encompass O. atypica , Architricha indica and Neogastrostyla species including the herein described N. chongmingensis nov. spec. Genetic variations discerned through the secondary structure of ITS2 molecules, pairwise genetic distances of the COI gene, and a range of phylogenetic trees indicate that speciation events have widely occurred within the OAN‐clade, with Architricha , Neogastrostyla and O. atypica evolving from certain O. granulifera ‐like lineages by developmental changes and other lineages retaining ancestral characteristics of O. granulifera . Moreover, our results reveal a recognisable pattern of environmental transition between freshwater and soil in the OAN‐clade, which provides a clue for further splitting the O. granulifera ‐ like populations. Additionally, our findings suggest that cortical granules, as is the case of cyathiform mucocysts containing glycosylated proteins present in the OAN‐clade, could serve as a criterion for delimiting the genus Oxytricha and the family Oxytrichidae, thus excluding other Oxytricha species with other kinds of cortical granules or lacking them.

Quantifying assembly processes of dissolved organic matter pools in eutrophication using high-resolution mass spectrometry and ecological models - Guan-Lin Chen; Chen Qian; Meng Du; Min-Jie Tong; Jie-Jie Chen; Han-Qing Yu (Water Research, 2025)

The characteristics and mechanism of microwave-induced subsurface fracturing of hard rock at different burial depths - Tianyang Tong; Feng Lin; Shiping Li; Xiangxin Su (Tunnelling and Underground Space Technology, 2025)

Multi-perspective analysis of long-term vehicle emissions under intensive policy updates in China - Wentian Xu; Fangyuan Zheng; Zhouzhi Li; Junxia Gao; Hui Tong; Haomiao Niu; Bin Sun; Zhaoyang Fan; Lin Wu; Hongjun Mao (Transportation Research Part D: Transport and Environment, 2025)

Microbial community structure and functional characteristics in shale gas flowback water from marine shale formation in Sichuan Basin, China: Insights into C-N-P-S cycle and correlations - Lin Quan; Aqiang Ding; Jun Liu; Yuhao Tong; Jiayi Qing; Junou Pan; Xiong Li; Bin Lei; Daijun Zhang; Peili Lu (Journal of Water Process Engineering, 2025)

Copper selenide enhanced magnetic biochar for elemental mercury removal from coal combustion flue gas - Lin Zhang; Yang Zheng; Guoliang Li; Jiajia Gao; Yali Tong; Tao Yue (Journal of Environmental Sciences, 2025)

Extending CO2 and CH4 footprints of created habitats through drainage ditches in a subtropical coastal region of southeastern China - Yan Zhang; Yule Lin; Ping Yang; Hong Yang; Guanpeng Chen; Wenjing Liu; Chuan Tong; Yongxin Lin; Dongyao Sun; Wenbo Lin; Kam W. Tang (Environmental Research, 2025)

Iron-modified electroactive material mediated chain elongation: Bridging pseudocapacitance and caproate biosynthesis - Zi-Lin He; Yong-Yao Zhang; Tian Lan; Wei-Tong Ren; Hua-Zhe Wang; Juan-Shan Du; Qing-Lian Wu; Wan-Qian Guo (Chemical Engineering Journal, 2025)

Magnetically-driven Dual-channel Fluorescent Biosensor with Aptamer Logic Gates for Multiplexed Exosomal Protein Profiling and Breast Cancer Subtyping - Yanqiu Wu; Lin Chen; Yao Tong; Changsheng Zhai; Guiyong Xiao; Yupeng Lv; Lutao Du; Juan Li; Peng Ren; Yanyan Jiang (Chemical Engineering Journal, 2025)

Dual-stage matrix elimination-ICP-MS methodology for REEs profiling in barite-associated ores - Xue-lin Dong; Jun-han Liu; Zheng-xun Jia; Shao-zhan Tang; Shuo-yun Tong; Yu-xiang Xiong; Lei Ouyang (Analytica Chimica Acta, 2025)

Corrigendum to “BPA and low-Se exacerbate apoptosis and autophagy in the chicken bursa of Fabricius by regulating the ROS/AKT/FOXO1 pathway” [Science of the Total Environment 2024 (908) 168424] - Wenying Sun; Tong Xu; Hongjin Lin; Yilin Yin; Shiwen Xu (Science of The Total Environment, 2025)

Structurally diverse abietane diterpenoids from the whole plants of Salvia przewalskii Maxim. With anti-inflammatory activity - Rui Guo; Cun-Lin Wang; Tong Zhang; Shuang Xu; Xin Qiao; Guo-Shun Zhang; Qiong Zhang (Phytochemistry, 2025)

Shallow gas accumulation mechanism in the Qiongdongnan Basin, South China Sea - Junfeng Zhang; Detian Yan; Jianxiang Pei; Wei Luo; Entao Liu; Peng Song; Tong Li; Zeyu Lu; Xudong Lin (Marine and Petroleum Geology, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

Axial compressive performance of reinforced sea-sand concrete-filled square stainless steel tubular stub columns - Zhi-Bin Wang; Jing-Dong Tong; Chun-Guang Zhao; Ee Loon Tan; Xin Yu; Ji-Ting Lin (Engineering Structures, 2025)

Synergistically modulating multiple polarizations of electrically insulating and thermally conductive SnO2@C hollow core–shell nanofasciculi for exceptional EM protection capabilities - Baoxin Fan; Junhao Ding; Shiyang Cai; Kang Fu; Xiangyang Liu; Lingling Lin; Zhenjie Yu; Guoxiu Tong; Wenhua Wu (Chemical Engineering Journal, 2025)

Fabrication of graphene-PEI composite membrane by supercritical CO2 exfoliation for efficient nanofiltration performance - Lin Li; Kunpeng Yu; Jing Xie; Haixin Sun; Tong Feng; Qinqin Xu; Jianzhong Yin (Chemical Engineering Journal, 2025)

Liquid–liquid phase separation in normal hematopoiesis and hematological diseases - Lexuan Lin; Fang He; Xu Jin; Xiaoru Zhang; Yue Li; Di Wang; Jingwei Wang; Lingyue Zheng; Haoze Song; Xu Zhu; Qimei Cheng; Yitong Zhao; et al. (Cell and Tissue Research, 2025)

Nasopharyngeal cancer screening and immunotherapy efficacy evaluation based on plasma separation combined with label-free SERS technology - Ruiying Lin; Zhangying Jiang; Jinyong Lin; Feifei Tong; Yangmin Wu; Jinquan Hong; Sufang Qiu; Qiong Wu (Analytica Chimica Acta, 2025)

The substrate configuration influences pollutant removal in constructed wetlands: From the aspects of submerged status of substrate and carbon-felt distribution - Xiang-Zheng Li; Tong Wang; Ting Yang; Xue Li; Lin-Wei Wu; Lin-Lan Zhuang; Jian Zhang (Water Research, 2025)

Paleoproterozoic continental crust accretion on the northern margin of the North China Craton: Evidence from the Shangyi Complex at the eastern segment of the Khondalite Belt - Yinchuan Wang; Zuochen Li; Xianzhi Pei; Meng Wang; Hai Zhou; Ruiguang Wang; Tong Zhang; Hao Lin; Irshad Hussain; Xiao Wang; Xue Jiang; Song Gao; et al. (Precambrian Research, 2025)

Effective feature matching of high-resolution planetary orbiter images based on optimized image partitioning and rapid local correspondence - Lin Xue; Zhen Ye; Dayong Liu; Shijie Liu; Rong Huang; Huan Xie; Yongjiu Feng; Beibei Guo; Yusheng Xu; Xiaohua Tong (Planetary and Space Science, 2025)

Odorant receptor 75 is essential for attractive response to plant volatile p-anisaldehyde in Western flower thrips - Xuan-Pu Luan; Xiao-Tong Zhang; Zhi-Qiang Wei; Jin-Meng Guo; George F.O. Obiero; Merid N. Getahun; Qi Yan; Jin Zhang; Shuang-Lin Dong (Pesticide Biochemistry and Physiology, 2025)

Mechanistic insights into temoporfin-based photodynamic therapy: Ferroptosis as a critical regulator under normoxic and hypoxic conditions in head and neck cancer - Tong-Hong Wang; Li-Fang Chou; Yen-Wen Shen; Nan-Chin Lin; Yin-Hwa Shih; Tzong-Ming Shieh (Journal of Photochemistry and Photobiology B: Biology, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Recycled polyethylene terephthalate/reduced graphene oxide modified with magnesium ferrite for organic dye degradation with benign toxicity towards Vigna radiata L and Ipomoea aquatica, and photocatalytic water splitting to produce H2O2 - Nguyen Huu Hieu; Tong Hoang Lin; Ton That Buu; Che Quang Cong; Hoang An; Nguyen Thanh Hoai Nam (Journal of Environmental Chemical Engineering, 2025)

Study on the characteristics of coal pore structure changes during hot flue gas displacement and their impact on the gas displacement effect - Jiahao He; Baiquan Lin; Tong Liu; Zhenyong Zhang; Shuai Le; Yajie Hu (Geomechanics for Energy and the Environment, 2025)

Integrating mass defect filtering and targeted molecular networking for foodomics research: A case study of Magnolia officinalis cortex - Qi Wang; Haodong Zhu; Hong Zhou; Congwei Yu; Xupeng Tong; Xinya Zhang; Aijing Li; Pei Lin; Xinsheng Yao; Keshen Li; Liangliang He; Zhihong Yao (Food Research International, 2025)

Protein lactylation in broiler breast: Insights on occurrence mechanisms and the correlations with meat quality - Zhenxin Wang; Tong Xing; Lin Zhang; Liang Zhao; Feng Gao (Food Chemistry, 2025)

A rat pup model: Investigate the digestibility and absorption characteristics of human, bovine and camel lactoferrin - Tong Liu; Lina Zhang; Lingyan Zhang; Jie Lin; Yuhong Jiang; Peng Zhou (Food Bioscience, 2025)

Functional molecule surface infiltration treatment for efficient all-inorganic perovskite light-emitting diodes - Shurui Chi; Yongjian Chen; Xiuling Li; Jiaqi Wang; Zixun Zhao; Zhuojian Li; Yanqin Miao; Xin Tong; Jinli Liu; Yuechuan Bi; Zongwen Liu; Zhiming Wang; et al. (Chemical Engineering Journal, 2025)

Glaciers retreat-induced gravelization encroached alpine hillside grassland: A case study in Qilian Mountain, China - Tong Li; Jingxue Zhao; Gao-Lin Wu (CATENA, 2025)

Mantle evolution beneath a back-arc basin: Highly siderophile elements and Os isotope of Dongco ophiolitic peridotites, Tibet - Xiao-Ni Li; Wei-Qi Zhang; Tong Liu; Chang Zhang; Yin-Zheng Lin; Zhen Zhang; Jia-Ning Zhu; Hong-Yu Li; Chuan-Zhou Liu (Chemical Geology, 2025)

Characteristics of Impact Fragmentation and Energy Dissipation of Cylindrical Rock Specimens with Various Aspect Ratios - Yuzhong Qin; Lin Lang; Shuang Tian; Tong Wu; Huaizi Tang; Jun Xu; Yingda Zhang; Jingmei Wang; Huijun Lu; Zheming Zhu (Rock Mechanics and Rock Engineering, 2025)

Retearing of type B blind cystic aortic dissection: computational fluid dynamics analysis - Hongbing Chen; Yujing Huang; Tong Su; Qi Wang; Minzhu Zhao; Shangyu Zhang; Ruijiao Lin; Jianbo Li (Physical and Engineering Sciences in Medicine, 2025)

Targeting Programmed Cell Death in Acquired Sensorineural Hearing Loss: Ferroptosis, Necroptosis, and Pyroptosis - Shasha Zhang; Hairong Xiao; Yanqin Lin; Xujun Tang; Wei Tong; Buwei Shao; He Li; Lei Xu; Xiaoqiong Ding; Renjie Chai (Neuroscience Bulletin, 2025)
Sensorineural hearing loss (SNHL), the most commonly-occurring form of hearing loss, is caused mainly by injury to or the loss of hair cells and spiral ganglion neurons in the cochlea. Numerous environmental and physiological factors have been shown to cause acquired SNHL, such as ototoxic drugs, noise exposure, aging, infections, and diseases. Several programmed cell death (PCD) pathways have been reported to be involved in SNHL, especially some novel PCD pathways that have only recently been reported, such as ferroptosis, necroptosis, and pyroptosis. Here we summarize these PCD pathways and their roles and mechanisms in SNHL, aiming to provide new insights and potential therapeutic strategies for SNHL by targeting these PCD pathways.

Influence of Surging and Pitching Behaviors on the Power Output and Wake Characteristics of a 15 MW Floating Wind Turbine - Tsung-Yueh Lin; Hoi-Yi Tong; Sai-Kiu Wong; Shiu-Wu Chau (Journal of Marine Science and Engineering, 2025)
This study investigates the impacts of surging and pitching motions on the power generation performance and wake characteristics of an IEA 15 MW offshore wind turbine under specific inflow wind conditions. The three-dimensional, unsteady continuity equation, momentum equations, and SST k–ω turbulence model are solved numerically using the computational fluid dynamics software STAR-CCM+ (version 2206) to simulate the aerodynamic flow field around the turbine rotor and in its downstream wake region. Under the condition of an inflow wind speed of 9 m/s at hub height and a corresponding rotor rotational speed of 7.457 RPM, the surging and pitching motions of the turbine are prescribed by sinusoidal functions with a period of 45 s and amplitudes of 2.75 m and 5°, respectively. This study analyzes and quantifies the power output and wake characteristics of the turbine over a duration corresponding to 200 rotor revolutions, considering stationary, surging, and pitching conditions. The results indicate that the surging and pitching motions of the turbine cause reductions in the mean power output of 2.18% and 3.54%, respectively, compared to a stationary condition. The surging and pitching motions also lead to significant wake enhancement in the downstream region, and a minimum spacing of downstream wind turbines is suggested.

Analysis of Offshore Pile–Soil Interaction Using Artificial Neural Network - Peiyuan Lin; Kun Li; Xiangwei Yu; Tong Liu; Xun Yuan; Haoyi Li (Journal of Marine Science and Engineering, 2025)
Offshore wind power is one of the primary forms of utilizing marine green energy in China. Currently, near-shore wind power predominantly employs monopile foundations, with designs typically being overly conservative, resulting in high construction costs. Precise characterization of the interaction mechanisms between marine piles and surrounding soils is crucial for foundation design optimization. Traditional p-y curve methods, with simplified fitting functions, inadequately capture the complex pile–soil behaviors, limiting predictive accuracy and model uncertainty quantification. To address these challenges, this research collected 1852 empirical datasets of offshore wind monopile foundation pile–soil interactions, developing p-y curve and horizontal displacement prediction models using artificial neural network (ANN) expressions and comprehensive uncertainty statistical analysis. The constructed ANN model demonstrates a simple structure with satisfactory predictive performance, achieving average error margins below 6% and low to moderate prediction accuracy dispersion (26%~45%). In contrast, traditional p-y curve models show 30%~50% average biases with substantial accuracy dispersion near 80%, while conventional finite element methods exhibit approximately 40% error and dispersion. By strictly characterizing the probability cumulative function of the neural network model factors, a foundation is provided for reliability-based design. Through comprehensive case verification, it is demonstrated that the ANN-based model has significant advantages in terms of computational accuracy and efficiency in the design of offshore wind power foundations.

Fusion of monocular camera and 3D LiDAR data for navigation line extraction under corn canopy - Chao Ban; Lin Wang; Tong Su; Ruijuan Chi; Guohui Fu (Computers and Electronics in Agriculture, 2025)

Aged microplastics-induced growth inhibition via DNA damage, GH/IGF-1 and HPT axes disruption in zebrafish larvae - Qing Ge; Tong Zheng; Ping Ding; Zhenyuan Li; Xihua Lin; Xintong Li; Miao He; Guocheng Hu (Science of The Total Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Low-level exposure to environmental lithium element affects male reproductive outcomes: Results from the MARHCS cohort study in Chongqing, China and in vivo animal experiments - Lihong Wang; Guanghui Zhang; Xi Ling; Mei Wan; Qing Chen; Lei Sun; Huan Yang; Tong Wang; Jinyi Liu; Jia Cao; Lin Ao; Peng Zou (Reproductive Toxicology, 2025)

Elevated N2O emissions from coastal small water bodies: Implications for greenhouse gas inventories - Lele Tang; Wenjing Liu; Hong Yang; Ping Yang; Chuan Tong; Yongxin Lin; Dongyao Sun; Wenjing Tan; Wenbo Lin; Pingping Guo; Linhai Zhang; Kam W. Tang (Journal of Hydrology, 2025)

Exposure profiles, determinants, and health risks of chemicals in personal care products among healthy older adults from the China BAPE study - Xiaojie Guo; Jiankun Qian; Huimin Ren; Enmin Ding; Xiao Ma; Jiran Zhang; Tian Qiu; Yifu Lu; Peijie Sun; Chenfeng Li; Chenlong Li; Yibo Xu; et al. (Journal of Hazardous Materials, 2025)

Targeting sustainable desalination solutions: A techno-economic and life cycle approach to guiding zero liquid discharge desalination - Brandi M. Grauberger; Garrett M. Cole; Tiezheng Tong; Shihong Lin; Jason C. Quinn; Todd Bandhauer (Journal of Cleaner Production, 2025)

Nighttime reactions of a series of unsaturated alcohols with NO3•: Kinetics, products and mechanisms study - Yanyong Xu; Shengrui Tong; Weiran Li; Meifang Chen; Lin Hu; Hailiang Zhang; Sufan Wang; Maofa Ge (Journal of Environmental Sciences, 2025)

Association between exposure to perfluoroalkyl substances (PFASs) and risk of hyperemesis gravidarum - Lan Zhang; Xiuxiu Ma; Tong Su; Yue Wang; Miaomiao Hai; Feifei Qi; Le Ma; Shunming Zhang; Jing Lin (Environmental Pollution, 2025)

Bimetallic MOF-derived Co/Ni@C and MXene co-decorated cellulose-derived carbon foams for absorption-dominated electromagnetic interference shielding - Fang Ren; Lin Ma; Chunjie Li; Tong Wu; Jiale Zhang; Lu Pei; Yanling Jin; Zhenfeng Sun; Zhengzheng Guo; Ping Song; Penggang Ren (Carbohydrate Polymers, 2025)

The Effects of Experimental Warming on Phyllosphere Microbial Communities of Picea asperata and Fargesia nitida in Eastern Tibetan Plateau, China - Yunyi Li; Xiaoyan Yan; Lin Luo; Jin Tong; Chunzhang Zhao (Current Microbiology, 2025)

Effective Strategies for Accelerating the Phase-Out of Mercury Thermometers in Underdeveloped Regions: A Critical Step Towards Implementing the Minamata Convention on Mercury - Wanying Lin; Qihong Yang; Zhanhua Zhang; Xia Sheng; Tong Zhang; Yan Lin (Bulletin of Environmental Contamination and Toxicology, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Shale wastewater treatment policies recommended by integrated knowledge graph and probability-based algorithms - Li He; Yugeng Luo; Mengxi He; Tong Sun; Yiming Yan; Wei Ye; Yupeng Lin (Environmental Monitoring and Assessment, 2025)

Development of a rat airway organoids model for studying chronic obstructive pulmonary disease - Chuanlai Yang; Hongwei Yang; Yangling Xian; Nanyi Liu; Haoyin Tan; Zirui Ren; Yanzhen Lin; Huan Zhao; Changjian Fang; Kang Yu; Dequan Pan; Yali Zhang; et al. (Tissue and Cell, 2025)

Genome-wide association analysis reveals genetic loci and candidate genes for white diarrhea in Jingyuan chickens - Lijuan Yang; Siyu Chen; Wei Zhao; Guojun Zhang; Hu Zhang; Tong Zhang; Lin Xue; Jinli Tian; Yaling Gu; Lanlan Li; Hu Wang; Juan Zhang (Research in Veterinary Science, 2025)

Mantle metasomatism by subducted Indian continental crust: Evidence from post-collisional basaltic ultrapotassic rocks in southern Tibetan plateau - Miao-Yan Zhang; Lu-Lu Hao; Yue Qi; Qiang Wang; Andrew C. Kerr; Lin Ma; Cheng-Cheng Huang; Gang-Jian Wei; Jie Li; Jin-Long Ma; Qi-Wei Li; Zi-Long Wang; et al. (Lithos, 2025)

Rapid electrothermal upcycling hexachlorobutadiene (HCBD) polluted distillation residue into turbostratic graphene for enhanced electromagnetic wave absorption - Tong Chen; Yunxiao Zhao; Hanyang Sun; Xinyu Niu; Pei Li; Yan Xia; Xiaoqing Lin; Xiaodong Li; Ying Wang; Jianhua Yan; Chen Sun (Journal of Hazardous Materials, 2025)

Approximate the optimal energy management strategy for plug-in hybrid electric vehicle from the constant-sum game - Jincheng Hu; Yang Lin; He Tong; Quan Zhou; Zheng Chen; Yonggang Liu; Jingjing Jiang; Yuanjian Zhang (Journal of Cleaner Production, 2025)

Recent advances on carbon capture and electrochemical CO2 reduction with amphiphile surfactants and polymers - Fentahun Wondu Dagnaw; Rui-Qi Li; Yi-Lin Xie; Qing-Xiao Tong; Jing-Xin Jian (Journal of Environmental Chemical Engineering, 2025)

A screening model for predicting the potential of soil colloids-enhanced leaching of hydrophobic organic contaminants to groundwater at contaminated sites - Lin Duan; Jiahuan Liu; Jing Wang; Chuanjia Jiang; Tong Zhang; Wei Chen (Journal of Environmental Sciences, 2025)

Preferential association of PBDEs and PAHs with mineral particles vs. dissolved organic carbon: Implications for groundwater contamination at e-waste sites - Cuiyi Yang; Lin Duan; Jing Wang; Chuanjia Jiang; Tong Zhang; Wei Chen (Journal of Environmental Sciences, 2025)

WTAP-mediated m6A modification of Hmgb2 contributes to spermatogenic damage induced by PM2.5 exposure - Jiankang Wang; Zhonghao Zhang; Fuquan Shi; Yingqing Li; Chaofeng Shi; Tong Wang; Lei Sun; Lin Ao; Fei Han; Qing Chen; Jia Cao; Jinyi Liu (Environmental Pollution, 2025)

Wide-area tip-like effect boosting electrocatalytic sulfion oxidation for energy-efficient hydrogen production in seawater electrolysis - Kecheng Tong; Wenhui Qiu; Shucong Zhang; Weiyue Zhao; Pingwei Wu; Fei Lin; Lei Chu; Huanlei Wang; Weiqian Tian; Minghua Huang (Chemical Engineering Journal, 2025)

Natural phenolic Acid-Functionalized polyurethane microcapsules with superior foliar retention and UV protection for improving pesticide efficacy and safety - Yanan Xiao; Mengdie Li; Shuhui Hu; Lin-Lin Yang; Jian Wang; Chang Yan; Yi Tong; Shuo Liu; Liqian Cao; Wenneng Wu; Bo Zhang (Chemical Engineering Journal, 2025)

Differential microbial degradation of cross-linked Polythene by Aspergillus niger in space and on the ground - Shuyuan Zhang; Lei Dang; Weiliang Li; Qin Zhang; Kui Xiao; Tong Tong; Qianqian Liu; Lingling Ma; Nana Chen; Lantao Zhang; Yali Feng; Yan Song; et al. (Chemical Engineering Journal, 2025)

Perylene diimide cathode interface layer with siloxane bay-modification for efficient and stable organic solar cells - Dan Zhou; Yujie Pu; Yanyan Wang; Lin Hu; Jianwei Quan; Senmei Lan; Jiangang Ma; Fang Wang; Wentian Wan; Yongfen Tong; Ruizhi Lv; Haitao Xu; et al. (Chemical Engineering Journal, 2025)

Peptide-conjugated alginate fiber: A skeletal muscle regenerative scaffold - Yajun Li; Yueren Wu; Tong Wu; Can Zhang; Jianwu Dai; Jianping Tang; Lin Li; Liyang Shi (Carbohydrate Polymers, 2025)

Research on Coal Reservoir Pore Structures: Progress, Current Status, and Advancing - Kai Wang; Lin Guo; Chao Xu; Wenjing Wang; Tong Yang; Yuanyuan Hu; Yongwang Yuan (Natural Resources Research, 2025)

Rainfall Promote Bruceine D Release from Brucea javanica Leaf Litter Thus Reducing Weeds and Enhancing Plant Competitiveness - Yao Tong; Hai-Ou Lin; Dong-Qiang Zeng; Fa-Yang Xie; Wen-Wei Tang (Journal of Chemical Ecology, 2025)

Preface to the Special Topic on Air Pollution Complex Research in China: Recent Advances - Tong Zhu; Mingjin Tang; Hong Liao; Yele Sun; Lin Wang; Minghuai Wang; Xuemei Wang (Advances in Atmospheric Sciences, 2025)

The Influence of Heterogeneous Processes on the Physicochemical Properties of Atmospheric Aerosols - Maofa Ge; Shengrui Tong; Lin Du; Lingyan Wu; Ting Lei; Kun Li; Minglan Xu; Narcisse T. Tsona; Wenqian Zhang; Hailiang Zhang (Advances in Atmospheric Sciences, 2025)
With the rapid development of the world economy, complex air pollution has increasingly become a serious threat; for example, with haze events occurring frequently in various regions of the globe. Recent evidence has indicated that secondary aerosols play an important role in haze formation, and that heterogeneous processes are among the main forces driving their explosive growth. In this regard, this paper reviews recent advances in the understanding of the impact of heterogeneous processes on haze chemistry, including the impact on NO 2 chemistry, marine aerosols, and the hygroscopicity and optical properties of atmospheric aerosols. It is distinguished from past reviews on this topic by focusing mainly on new insights from the past five years. We summarize the main findings of the impacts of heterogeneous processes on NO 2 chemistry, marine aerosols, and the physicochemical properties of atmospheric aerosols, and propose several future research directions.

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Tailored large-particle quantum dots with high color purity and excellent electroluminescent efficiency - Bo-Chen Liu; Qizhong Lin; Shuang-Qiao Sun; Qi Sun; Xing Peng; Xinyuan Chen; Yang Li; Yue-Min Xie; Shuit-Tong Lee; Man-Keung Fung (Science Bulletin, 2025)

Adrenomedullin gene delivery rescues estrogen production in Leydig cells via the inhibition of TGF-β1/Smads signaling pathway - You-wen Luo; Xia-lian Zhu; Zhi-min Yang; Jian-hua Zhou; Tong Tao; Bing-hai Chen; Song-lin Qin; Bo-long Liu; Wei Hu (Reproductive Toxicology, 2025)

Structure optimization of a hydrocyclone for separation of recycled rubber particles with low-density difference - Long Li; Li Dai; Lin Zeng; Penghui Zhou; Jianping Li; Yulong Chang; Tong Zhang; Aosong Wei; Liang Ma; Hualin Wang (Process Safety and Environmental Protection, 2025)

Chronological and palaeoecological insights into the Dayakou fauna in Yanjinggou, Chongqing, China: Responses of large mammals to the Early-Middle Pleistocene Climate Transition - Haiqian Hu; Haowen Tong; Fei Han; Hui Dai; Wanbo Huang; Qigao Jiangzuo; Paul Rummy; Xunqian Wang; Yu Lin; Guangbiao Wei (Quaternary Science Reviews, 2025)

A novel polydopamine-loaded copper sulfide (CuS@PDA) for activating H2O2 to eliminate tetracycline via 1O2 dominated oxidation pathway - Zhou Shi; Chenxi He; Hao Huang; Xile Huang; Tong Hu; Yijia He; Dazhi Yang; Simeng Xia; Haojie Zhang; Lin Deng (Journal of Water Process Engineering, 2025)

High-performance computing in urban flood modeling: A study on spatial partitioning techniques and parallel performance - Tong Chen; Jian Sun; Zihao Zhang; Zijun Xiao; Liang Zheng; Hua Chai; Binliang Lin (Journal of Hydrology, 2025)

Multiscale analysis of ecosystem service interactions and driving factors in the Loess Plateau: Implications for ecological management - Tao Xu; Guangjin Tian; Tong Lin; Wanlong Li; Chenxi Liu (Journal of Cleaner Production, 2025)

Microbial augmented aerobic composting for effective phthalates degradation in activated sludge - Bogui Pan; Hong Tian; Qi-Feng Liang; Hong-Jia Huang; Yi-Tong Huang; Bai-Lin Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Management, 2025)

New insights into quercetin's attenuation of TBBPA-induced injury to MCEC cells: Involvement of the p38/NF-κB pathway and pyroptosis - Ke Li; Kun Wang; Tong Xu; Chencong Lyu; Xuejiao Yang; Hongjin Lin; Shiwen Xu (Journal of Environmental Management, 2025)

Development of a net ozone production rate detection system based on dual-channel cavity ring-down spectroscopy - Jinzhao Tong; Renzhi Hu; Changjin Hu; Xiaoyan Liu; Haotian Cai; Chuan Lin; Liujun Zhong; Jiawei Wang; Pinhua Xie (Journal of Environmental Sciences, 2025)

Kinetic model of heterogeneous growth onto organic particles in supersaturated water environments - Xin Wang; Qi Zhang; Tong Zhang; Shoujie Yan; Lin Liu; Luying Yang (Journal of Aerosol Science, 2025)

Effects of different drying methods on the structure, bioaccessibility, and bioavailability of selenium-enriched peptides from soybean sprouts - Yangyang Xiong; Bei Fan; Lin Li; Yanfang Liu; Xinrui Wang; Chengxin Fei; Litao Tong; Fengzhong Wang; Yatao Huang (Food Chemistry, 2025)

High electrocatalytic activity of crystallization-modulated ordered PtCu3/C nanoalloy catalysts for oxygen reduction reaction - Xiaomei Li; Linfeng Fu; Lin Cao; Lihui Lei; Xinxing Zhan; Changgang Hu; Xin Tong; Juan Tian (Chemical Engineering Journal, 2025)

Cholesterol suppresses AMFR-mediated PDL1 ubiquitination and degradation in HCC - Wei-Qing Shao; Yi-Tong Li; Xu Zhou; Sheng-Guo Zhang; Ming-Hao Fan; Dong Zhang; Zhen-Mei Chen; Chen-He Yi; Sheng-Hao Wang; Wen-Wei Zhu; Ming Lu; Ji-Song Chen; et al. (Molecular and Cellular Biochemistry, 2025)

In vitro and in silico studies on α-glucosidase inhibitory properties of bioactive components from the rhizomes of Alpinia officinarum Hance - Zakhele Mphatsi Dlamini; Bongani Sicelo Dlamini; Shih-Han Fu; Ya-Lin Chang; Chi-Chien Lin; Yu-Kuo Chen; Kok-Tong Tan; Chi-I Chang (Medicinal Chemistry Research, 2025)

Effectiveness of Conditioning Strategies in Improving Fish Fitness‐Related Traits - Zonghang Zhang; Guihui Ning; Fei Tong; Wuhan Lin; Yangke Shang; Daomin Peng; Wenhua Liu (Fish and Fisheries, 2025)
Although conditioning strategies are widely used to increase fish post‐release adaptability in stock enhancement projects, their effectiveness has not been systematically evaluated. Using a global‐scale meta‐analysis, we demonstrate that three major conditioning strategies, including environmental enrichment, life skills training and release tactic, can significantly improve fish fitness‐related traits, with the fitness indicator and developmental stage being the most important moderators for interpreting the high heterogeneity among cases. The effect size of approximate fitness indicators was marginally lower than that of post‐release behavioural traits. Our findings indicate the necessity of conditioning procedures and highlight the need to enact context‐dependent strategies in practical conservation projects.

Patterns of shelf margin clinoform: control of the development of deep-water sedimentary systems - Tong Li; Detian Yan; Entao Liu; Junfeng Zhang; Xiaosong Wei; Zeyu Lu; Xudong Lin (Frontiers in Marine Science, 2025)
The clinothem is the fundamental element of basin infill and plays an important role in the source-to-sink system of deep-water basins. In this study, which is based on 2D and 3D seismic data, the spatiotemporal evolution of clinothems and depositional systems from the Miocene to the Pleistocene in the Qiongdongnan Basin, northern South China Sea, is investigated. The following conclusions are drawn: (1) three variations of clinothems in the Qiongdongnan Basin were recognized respective O-, S- and F-type clinothems; (2) fluctuations in the relative base level, in combination with variations in sediment supply, result in different clinothem patterns that may be used to understand changes in these depositional factors; and (3) the development of O-type clinothem is usually accompanied by slope instability and slumping, leading to mass transport deposits on the basin plain. When suitable transport pathways exist (e.g., shelf canyons) on the shelf-edge or when the F-type clinothem develops, sediments can be dispersed basinward, promoting submarine fan development. Results from this study will help in understanding the sedimentological development of slope and basin plain areas and offers significant insights into the understanding of deep-sea depositional systems.

Hydraulic analysis and design of subsurface irrigation system with ceramic emitters based on iterative method: An exploration in North China - Xuanyue Tong; Pute Wu; Xufei Liu; Lin Zhang (Computers and Electronics in Agriculture, 2025)

RTR-CNN: Rotated tray region selection and young seedling health status detection by CNN in greenhouse seedbed - Lei Wang; Yatao Li; Hao Lin; Junhua Tong; Liang Sun; Xiaoqin Wang; Jiahang Jiang (Computers and Electronics in Agriculture, 2025)

Impact of defatted black soldier fly (Hermetia illucens) larvae meal on health, muscle texture, and intestinal microbiota in Pacific white shrimp (Penaeus vannamei) - Tong Chang; Hongxing Lin; Fenglu Han; Chang Xu; Erchao Li (Aquaculture, 2025)

Impact of aerosol-photolysis interaction on the ozone concentration in the upper boundary layer on Mountain Everest - Yi Chen; Gang Zhao; Chunxiang Ye; Weili Lin; Chong Zhang; Jiacheng Zhou; Jing Gao; Tong Zhu (Science of The Total Environment, 2025)

Remnants of a Jurassic marginal sea plate in the Meso-Tethyan Ocean revealed by multi-stage magmatism in the Lagkorco ophiolite, Central Tibet - Wei-Qi Zhang; Chuan-Zhou Liu; Tong Liu; Chang Zhang; Xiao-Ni Li; Zhen-Yu Zhang; Zhen Zhang; Yin-Zheng Lin (Lithos, 2025)

Enzymatic degradation of polybutylene succinate by recombinant cutinase cloned from Paraphoma chrysanthemicola - Jingwei Lin; Kexin Sun; Li Ma; Chunwang Li; Haibin Tong; Zhanyong Wang (Journal of Environmental Management, 2025)

Ultrathin LDH-coated SnO2 catalysts linked by hydrogen bonding for PMS activation via interlayer high-speed electron transfer channels: Performance and mechanism - Guangjie Lv; Haoyang Ye; Cui Lai; Dengsheng Ma; Xuerong Zhou; Xiuqin Huo; Hao Deng; Lin Tang; Tao Tong; Ming Yan; Shuyuan Hu; Lei Qin (Journal of Environmental Chemical Engineering, 2025)

Selenium deficiency exacerbates ROS/ER stress mediated pyroptosis and ferroptosis induced by bisphenol A in chickens thymus - Kun Wang; Xu Shi; Hongjin Lin; Tong Xu; Shiwen Xu (Journal of Environmental Sciences, 2025)

Microscopic mechanism of gas-water two-phase flow based on low-field nuclear magnetic resonance - Wei Zha; Baiquan Lin; Tong Liu; Ting Liu; Wei Yang; Wenyuan Wang (Gas Science and Engineering, 2025)

Integrating lipidomics and metabolomics to reveal biomarkers of fat deposition in chicken meat - Wei Zhao; Jiahuan Hu; Lanlan Li; Lin Xue; Jinli Tian; Tong Zhang; Lijuan Yang; Yaling Gu; Juan Zhang (Food Chemistry, 2025)

Deep eutectic solvent-based ultrasonic-assisted extraction of polyphenol from Chenopodium quinoa Willd.: Optimization and lipid-lowering activity - Xiao-tong Lin; Si-xuan Zhou; Zhi-peng Sun; Ming-yuan Cao; Tao Zhou; Li-yan Zhao; Gui-tang Chen (Food Chemistry, 2025)

Non-destructive detection of freshness in crayfish (Procambarus clarkii) based on near-infrared spectroscopy combined with deep learning - Qing-li Han; Jian-feng Lu; Jiao-jiao Zhu; Lin Lin; Zhi Zheng; Shao-tong Jiang (Food Control, 2025)

Use of biochar derived from Spartina alterniflora to reduce sediment methane (CH4) production potential during non-farming period in earthen aquaculture ponds - Ping Yang; Dongyao Sun; Wenjing Liu; Kaiyuan Liu; Hong Yang; Chuan Tong; Linhai Zhang; Yongxin Lin; Derrick Y.F. Lai; Lishan Tan; Weifeng Chen; Kam W. Tang (Environmental Pollution, 2025)

Robust photothermal self-healing superhydrophobic composite coating for durable anti/de-icing applications - Jie zhu; Wen Li; Tong Wang; Huimeng Feng; Jia Cheng; Cunguo Lin; Xin Wang; Wei Wang; Shougang Chen (Chemical Engineering Journal, 2025)

Design and numerical analysis of an offshore methanol synthesis process through CO2 hydrogenation - Dong Lin; Liyu Zhang; Chenxi Pan; Jia Yang; Haitao Hu; Bo Tong; Zhiyu Li; Xin Zhang (Chemical Engineering Journal, 2025)

Nrf2 Signaling Pathway: Focus on Oxidative Stress in Spinal Cord Injury - Chun-lin Xiao; Hong-tong Lai; Jiang-jun Zhou; Wu-yang Liu; Min Zhao; Kai Zhao (Molecular Neurobiology, 2025)

Enzymatic Stoichiometry and Vector Characteristics Can Indicate Microbial Resource Limitation: Empirical Evidence from Experiment with Multiple Nutrient Addition - Zhifeng Zhai; Liying Lin; Tong Li; Zhaojun Bu; Meng Wang (Ecosystems, 2025)

Recycling of subduction-modified refractory mantle beneath the Marion Rise, Southwest Indian Ridge - Yin-Zheng Lin; Chuan-Zhou Liu; Wei-Qi Zhang; Zhen-Yu Zhang; Chang Zhang; Tong Liu (Contributions to Mineralogy and Petrology, 2025)

Thermodynamic mechanism of silica dosage and temperature on phase composition of well cement at high temperature and its impact on macro-properties - Huiting Liu; Tong Li; Jiaying Zhang; Pu Xu; Xiujian Xia; Yongjin Yu; Lin Liu; Huisu Chen (Applied Geochemistry, 2025)

Modeling of wave-induced drift based on stepwise parameter calibration - Kui Zhu; Xueyao Chen; Lin Mu; Dingfeng Yu; Runze Yu; Zhaolong Sun; Tong Zhou (Frontiers in Marine Science, 2025)
The motion of waves in water causes the slow movement of drifting sea targets—a phenomenon usually ignored in target-drift prediction models for maritime search and rescue (SAR). This study examined the wave-induced drift’s influence on field-observation experiments involving two common, differently sized SAR targets—an offshore fishing vessel (OFV) and a person in the water (PIW)—using parameter stepwise calibration and machine-learning (ML) methods. The sample of wave-induced drift velocity was obtained by gradually separating current-induced (CI) drift’s and wind-induced (WI) drift’s influence from the target-drift velocity using the least-square method and AP98 model. A force analysis method and three ML methods, long short-term memory (LSTM), back-propagation (BP) neural network, and random forest (RF), were used to fit the wave-induced drift velocity by combining eight different parameter schemes. Finally, the drift trajectories considering the influence of waves were fitted and verified based on 2 independent samples respectively. Compared with the force analysis method, the accuracy of the ML methods in the verification test was higher. In addition, the results show that for OFVs, considering wave-induced drift’s influence in the ensemble-trajectory prediction could improve the simulation accuracy. However, for a PIW, no significant improvement was observed. This result also indicates that wave-induced drift may not be simply ignored in large SAR targets’ drift prediction.

Effects of light colors on the growth, body color changes, and phototactic behaviors of green, purple, and white sea cucumbers, Apostichopus japonicus - Haoyu Tong; Xu Wang; Mingxin Lyu; Libin Zhang; Chenggang Lin (Aquaculture, 2025)

Earth's record-high greenness and its attributions in 2020 - Yulong Zhang; Jiafu Mao; Ge Sun; Qinfeng Guo; Jeffrey Atkins; Wenhong Li; Mingzhou Jin; Conghe Song; Jingfeng Xiao; Taehee Hwang; Tong Qiu; Lin Meng; et al. (Remote Sensing of Environment, 2025)

Optimizing working water head of subsurface irrigation system with ceramic emitters based on various climatic scenarios and water balance components - Xuanyue Tong; Pute Wu; Xufei Liu; Lin Zhang; Ligang Xu; Ying Tang (Journal of Hydrology, 2025)

Can biodegradable film replace polyethylene film to obtain similar mulching effects on soil functions and maize productivity in irrigation region? A three-year experimental appraisal - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Jing Wang; Shu-Tong Liu; Fu-Jian Mei; Wen-Ying Wang; Yi-Bo Wang; Xiang-Wen Fang; Ying Zhu; Jin-Lin Zhang; Ning Wang; et al. (Journal of Cleaner Production, 2025)

Comparative analyses of bacterial contamination and microbiome of broiler carcasses in wet market and industrial processing environments - Yuanyuan Zhou; Nan-lin Wang; Jin-qi Cen; Jia-tong Han; Yu-xuan Tang; Zi-qi Xu; Hang Zeng; Kurt Houf; Zhongjia Yu (International Journal of Food Microbiology, 2025)

Sedimentary, geochemical and reservoir characteristics of the Quaternary submarine fan in the Qiongdongnan basin - Junfeng Zhang; Detian Yan; Jianxiang Pei; Wei Luo; Entao Liu; Peng Song; Tong Li; Zeyu Lu; Xudong Lin (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Water-triggered stimuli-responsive luminescent crown-ether-coordinated cuprous bromides for multi-functional applications - Rui Wu; Hao Yang; Meifeng Jiang; Hui Tong; Xinyu Hu; Ziyang Liu; Chunhua Luo; Hui Peng; Hechun Lin (Chemical Engineering Journal, 2025)

Protein Phosphatase 2ACα Regulates ATR-Mediated Endogenous DNA Damage Response Against Microcephaly - Lin Lin; Jing Ding; Simeng Liu; Chunying Liu; Qing Li; Xiang Gao; Yamei Niu; Wei-Min Tong (Molecular Neurobiology, 2025)

The importance of porewater exchange process on carbon lateral export from saltmarsh creek to coastal sea - Jian’an Liu; Xueqing Yu; Xinyi Lin; Tong Peng; Liming Xue; Jinzhou Du (Journal of Oceanology and Limnology, 2025)

Establishment of Biopredictive Dissolution and Bioequivalence Safe Space Using the Physiologically Based Biopharmaceutics Modeling for Tacrolimus Extended-Release Capsules - Fulin Bi; Tong Yuan; Baohong Zhang; Jixia Li; Yan Lin; Jin Yang (AAPS PharmSciTech, 2024)

Carbon chain elongation characterizations of electrode-biofilm microbes in electro-fermentation - Wei-Tong Ren; Zi-Lin He; Yang Lv; Hua-Zhe Wang; Lin Deng; Shan-Shan Ye; Juan-Shan Du; Qing-Lian Wu; Wan-Qian Guo (Water Research, 2024)

Efficient ontology matching through compact linear genetic programming with surrogate-assisted local search - Xingsi Xue; Jerry Chun-Wei Lin; Tong Su (Swarm and Evolutionary Computation, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Resveratrol alleviates Mono-2-ethylhexyl phthalate-induced mitophagy, ferroptosis, and immunological dysfunction in grass carp hepatocytes by regulating the Nrf2 pathway - Xiaodan Wang; Meichen Gao; Xiunan Lu; Yutian Lei; Jiatong Sun; Mengyao Ren; Tong Xu; Hongjin Lin (Journal of Environmental Management, 2024)

Automatic extraction of Transverse Aeolian Ridges (TARs) and analysis of landform influence for the Zhurong landing area on Mars - Jie Zhang; Sicong Liu; Kecheng Du; Xiaohua Tong; Huan Xie; Yongjiu Feng; Yanmin Jin; Yizhang Lin; Bo Wan (Geomorphology, 2024)

Lignanamides: A comprehensive review of chemical constituents, biological activities, extraction methods and synthetic pathway - Jing Sun; Li-Tao Tong; Peng-Fei Tu; Lin-Lin Chen; Xin Xu; Ya Song; Xin-Xin Yang; Zi-Bin Guo; Xiang Zou; Chen-Xin Sun; Yan Mi; Bei Fan; et al. (Food Chemistry, 2024)

Interface engineering of Platinum–Copper alloy/titanium dioxide for enhanced photocatalytic carbon dioxide reduction - Xin Wang; Wei Tan; Bo Peng; Shangcong Sun; Xue Li; Kaiqiang Wang; Jiawei Ji; Haohong Liao; Jingfang Sun; Qing Tong; Haiqin Wan; Lin Dong (Environmental Research, 2024)

Association of fine particulate matter and residential green space with rheumatoid arthritis - Jingjing Hu; Peng Shen; Yingying Mao; Jie Qiu; Lisha Xu; Yonghao Wu; Yixing Wang; Ye Ding; Hongbo Lin; Liming Shui; Tong Feng; Jianbing Wang; et al. (Environmental Research, 2024)

Corrigendum to “Response of sulfur-metabolizing biofilm to external sulfide in element sulfur-based denitrification packed-bed reactor” [Environ. Res. 231 (2023) 116061] - Hong-Xu Bao; Han-Lin Wang; Shu-Tong Wang; Yi-Lu Sun; Xue-Ning Zhang; Hao-Yi Cheng; Zhi-Min Qian; Ai-Jie Wang (Environmental Research, 2024)

Nano-fuels-driven self-sacrificed ZIF-8@Apt integrated chip coupled with a DNAzyme system for the isolation and detection of glioblastoma-derived extracellular vesicles - Zehan Zeng; Mingzhen Zhong; Tong Liao; Xuan Zhou; Lin Shi; Xin Zhang; Ye Zhang; Jingyan Feng; Yiqian Chen; Shuya Sheng; Jun Chen; Lei Zheng; et al. (Chemical Engineering Journal, 2024)

Molecular properties, structure, neurotrophic and anti-inflammatory activities of cultured secondary metabolites from the cultures of the mushroom Cyathus striatus CBPFE A06 - Jing Wei; Mei-Yu Ye; Zhen-Xin Wang; Yi-Lin Zhang; Xuan-Sheng Hu; He-ping Hui; Yi-tong Liu; Jianzhao Qi (Natural Product Research, 2024)

Peroxynitrite-Triggered Carbon Monoxide Donor Improves Ischemic Stroke Outcome by Inhibiting Neuronal Apoptosis and Ferroptosis - Xin-Jian Guo; Lin-Yan Huang; Shi-Tong Gong; Ming Li; Wan Wang; Jie Chen; Yi-De Zhang; Xicun Lu; Xiaohua Chen; Lan Luo; Youjun Yang; Xiao Luo; et al. (Molecular Neurobiology, 2024)

Efficient transformation of CO2 into α-alkylidene cyclic carbonates over Cu0/Cu+ derived from CuAl layered double hydroxide/reduced graphene oxide hybrid - Zheng Wang; Yue Qiu; Baoyu Zou; Deke Wang; Zifei Gao; Xuanheng Zhang; Juanjuan Ma; Lin Liu; Chao Liu; Zhiwei Tong (Applied Clay Science, 2024)

Lactobacillaceae-mediated eye-brain-gut axis regulates high myopia-related anxiety: from the perspective of predictive, preventive, and personalized medicine - Yuze Mi; Ke Chen; Shaokai Lin; Luyao Tong; Jiawei Zhou; Minghui Wan (EPMA Journal, 2024)

Genetic diversity, antibiotic resistance, and pathogenicity of Aeromonas veronii isolated from farmed largemouth bass (Micropterus salmoides) in the main aquaculture regions of China - Qikai Chen; Yunfei Xing; Yan Lei; Guixiang Tong; Xiaobu Lin; Pengcheng He; Shaolin Tang; Feifei Zheng; Hui Zeng; Xinxian Wei; Yong-An Zhang; Yang Zhou (Aquaculture, 2024)

Berbamine inhibits porcine epidemic diarrhea virus in vitro and in vivo - Hongwei Xiang; Jixue Qiao; Haicheng Lin; Jie Li; Yangfan Li; Huihui Sun; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jinchi Zhou; et al. (Veterinary Microbiology, 2024)

Crustal-scale architecture and origin of the Haiyuan Arcuate Tectonic Belt, NE Tibet - Zizhao Yuan; Yanqi Lin; Xiao Xu; Huilin Li; Xiaoyu Guo; Chunsen Li; Xiaofei Tong (Tectonophysics, 2024)

Cyanobacteria-cyanophage interactions between freshwater and marine ecosystems based on large-scale cyanophage genomic analysis - Wei Lin; Dengfeng Li; Lingting Pan; Mengzhe Li; Yigang Tong (Science of The Total Environment, 2024)

Metabolite profiles of distinct obesity phenotypes integrating impacts of altitude and their association with diet and metabolic disorders in Tibetans - Wen Peng; Lin Shi; Qingxia Huang; Tiemei Li; Wenxiu Jian; Lei Zhao; Ruijie Xu; Tianqi Liu; Bin Zhang; Haijing Wang; Li Tong; Huiru Tang; et al. (Science of The Total Environment, 2024)

Performance and biotoxicity of electro-Fenton treatment of bisphenol A: Evaluation of copper recovered from microbial fuel cell cathodes for subsequent catalytic applications - Chi-Wen Lin; Guan-Yi Chen; Shu-Hui Liu; Wei Tong Chen; Shih-Hsien Chang; Chih-Yu Ma (Process Safety and Environmental Protection, 2024)

Effective strategies alleviate mitochondrial toxicity of perfluorooctanoic acid: Modification of functional head group and inhibition of toxic target - Ruijia Zhang; Lanyin Tu; Yingshi Lin; Jiahui Liu; Tong Liang; Wenhua Lu; Baowei Chen; Tiangang Luan (Journal of Hazardous Materials, 2024)

Unveiling the pathogenic and multidrug-resistant profiles of Vibrio alfacsensis: A potential identified threat in turbot (Scophthalmus maximus) aquaculture - Ren-Ge Hu; Lei Yang; Li-Yan Wang; Yu-Lin Yang; Hong-Jin Li; Bin-Tong Yang; Yuan-Huan Kang; Zhen-Lin Liang; Wei Cong (Journal of Hazardous Materials, 2024)

Diffusion behavior and transport risk of bioaerosol particles in a domestic waste landfill site in an arid and cold region of northwestern China - Tong Gao; Wenwen Wang; Jiawei Ma; Tianlong Zheng; Lin Li (Journal of Hazardous Materials, 2024)

Emission characteristics and process distributions of multiple brominated persistent organic pollutants during co-disposal of hexabromocyclododecane-containing waste in a municipal solid waste incinerator - Wenhui Xie; Bingcheng Lin; Yaqi Peng; Bei Chen; Yuchun Wang; Yuxuan Ying; Shengyong Lu; Tong Chen (Journal of Environmental Management, 2024)

Intelligent identification of picking periods of Lu’an Guapian tea by an indicator displacement colorimetric sensor array combined with machine learning - Yao Chen; Yuan Li; Li-Lin Lin; Yue Liao; Huan Fang; Tong Wang (Food Research International, 2024)

Corrigendum to ‘Machine-learning-based corrections of CMIP6 historical surface ozone in China during 1950–2014’ [Environ. Pollut. 357 (2024) 124397] - Yuanxi Tong; Yingying Yan; Jintai Lin; Shaofei Kong; Zhixuan Tong; Yifei Zhu; Yukun Yan; Zhan Sun (Environmental Pollution, 2024)

Preparation of polyethylene based composite nanofiltration membrane and its application in removal of heavy metals for water purification - Lin Wang; Guiru Zhu; Haochen Ge; Yunbo Tong; Lingling Li; Ziqi Wang; Congjie Gao (Desalination, 2024)

Quercetin antagonizes apoptosis, autophagy and immune dysfunction induced by di(2-ethylhexyl) phthalate via ROS/ASK1/JNK pathway - Jiatong Sun; Xiaodan Wang; Tong Xu; Mengyao Ren; Meichen Gao; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Synergistic effects of metallic IrCo for promoted nitrate reduction in industrial-relevant wastewater level - Yu Tang; Pan Ran; Linjun Zhong; Haohong Liao; Qing Tong; Weixin Zou; Lin Dong (Chemical Engineering Journal, 2024)

Si-based all-lithium-reactive high-entropy alloy for thin-film lithium-ion battery anode - Yi Su; Xincheng Lei; Wenjie Chen; Yipeng Su; Haowen Liu; Shuaiyang Ren; Ruoyu Tong; Yitao Lin; Weijing Jiang; Xiaozhi Liu; Dong Su; Yuegang Zhang (Chemical Engineering Journal, 2024)

The formation of yukonite from FeIII-AsV slurries: Kinetic studies and implications for calcium arsenate treatment - Danni Zhang; Min Li; Ying Wang; Qiuli Xia; Yumeng Wang; Yuting Jin; Junting Tong; Lin Wang; Dake Xu; Fuhui Wang; Yongfeng Jia (Chemical Engineering Journal, 2024)

Networking SiO2-Al2O3 and amines into robust and long-lasting molded sorbents for continuous CO2 capture - Tong Zhou; Zhinan Wu; Yunxia Wen; Zhengxing Dai; Shuailong Song; Han Lin; Xin Feng; Xiaohua Lu; Tuo Ji; Jiahua Zhu (Chemical Engineering Journal, 2024)

Base on photothermal interfacial molecular transfer for efficient biodiesel catalysis via enzyme@cyclodextrin metal-organic frameworks loaded MXene - Qi Ao; Lin Jiang; Ying Song; Xinglai Tong; Tuohao Jiang; Xiaoxiao Lv; Jun Tang (Carbohydrate Polymers, 2024)

Comparative study on environmental and economic assessment of straw heating across administrative areas scale of rural China - Tong Li; Guoxia Wei; Hanqiao Liu; Hailong Zhao; Yuwen Zhu; Yanfei Lin; Qianlong Han; Yifan Chen; Yanzhang Wang (The International Journal of Life Cycle Assessment, 2024)

Study on Influence of Preset Circular Holes on Propagation of Blast-Induced Cracks Based on Experiments and Discrete Element Simulations - Minghua Lin; Baiquan Lin; Wei Yang; Ting Liu; Yang Shen; Tong Liu; Xiangliang Zhang; Fei Lin; Guang Xia (Rock Mechanics and Rock Engineering, 2024)

Mechanistic analyses reveal that Pueraria montana var. lobata (Willd.) is effective in inhibiting ovarian cancer progression - Chao Lin; Tong Su; Yong-ju Ye (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Imaged capillary isoelectric focusing method development for charge variants of high DAR ADCs - Chuan Leng; Shuwen Sun; Wei Lin; Jorge Alexander Pavon; Lynn Gennaro; Rico C. Gunawan; Xiaodong Bu; Tong Yang; Senwu Li (Analytica Chimica Acta, 2024)

On the properties of lower mid-latitudes ionospheric scintillation observed over Chengdu, China - Shucan Ge; Hailong Li; Song Zhang; Mengyan Zhu; Jinghua Li; Bin Xu; Tong Xu; Shuji Sun; Lin Meng; Jian Wu (Advances in Space Research, 2024)

Nutrient depletion and phytoplankton shifts driven by the Pearl River plume in the Taiwan Strait - Zhuyin Tong; Changyun Wang; Lizhen Lin; Lingqi Ma; Bangqin Huang (Frontiers in Marine Science, 2024)
The intrusion of the Pearl River plume into the Taiwan Strait provides a unique case study that challenges traditional assumptions about the impacts of nutrient-rich river plumes on coastal phytoplankton communities. In this study, we conducted a detailed analysis of nutrient dynamics and phytoplankton composition within the Taiwan Strait, focusing on the effects of the Pearl River plume. Our findings reveal significant nutrient depletion, particularly of nitrogen, in the surface waters as the plume extends seaward, resulting in nitrogen limitation and a marked reduction in phytoplankton biomass. Vertical stratification within the Taiwan Strait creates distinct ecological niches, with the mid-layer supporting a deep chlorophyll maximum and the surface layer becoming dominated by the picophytoplankton Synechococcus . This shift from diatom-dominated communities to Synechococcus dominance has far-reaching implications for carbon cycling and food web dynamics in the region. Our results suggest that the Pearl River plume’s influence on the Taiwan Strait represents a departure from the typical nutrient enrichment associated with river plumes, highlighting the complexity of coastal biogeochemical processes.

Diffusion behavior and environmental impact of odorants and TVOCs detected in a wastewater treatment plant for collaborative leachate treatment in Northwest China - Zilan Liao; Tong Gao; Pengyu Li; Tianlong Zheng; Lin Li; Cui Li; Wenwen Wang; Ying Wang; Junxin Liu (Chemosphere, 2024)

A novel variable discharge emitter for irrigation and salt-leaching - Xufei Liu; Lin Zhang; Yuli Sun; Xuanyue Tong; Xuefei He; Yiqian Wei (Biosystems Engineering, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Relevance of genetic causes and environmental adaptation of Cronobacter spp. isolated from infant and follow-up formula production factories and retailed products in China: A 7-year period of continuous surveillance based on genome-wide analysis - Wei Tong; Dajin Yang; Shaofu Qiu; Sai Tian; Zehong Ye; Shuran Yang; Lin Yan; Weiwei Li; Ning Li; Xiaoyan Pei; Zhongqing Sun; Chengwei Liu; et al. (Science of The Total Environment, 2024)

Laboratorial radiative shocks with multiple parameters and first quantifying verifications to core-collapse supernovae - Lu Zhang; Jianhua Zheng; Zhenghua Yang; Tianming Song; Shuai Zhang; Tong Liu; Yunfeng Wei; Longyu Kuang; Longfei Jing; Zhiwei Lin; Liling Li; Hang Li; et al. (Science Bulletin, 2024)

Reduction in polycyclic aromatic hydrocarbon exposure in Beijing following China’s clean air actions - Yan Lin; Xiaodi Shi; Xinghua Qiu; Xing Jiang; Jinming Liu; Peiwen Zhong; Yihui Ge; Chi-Hong Tseng; Junfeng (Jim) Zhang; Tong Zhu; Jesus A Araujo; Yifang Zhu (Science Bulletin, 2024)

Corrigendum to “Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L.” [Phytochem. Lett. 55 2023, 61–66] - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2024)

Internal solitary wave-induced soil responses and its effects on seabed instability in the South China Sea - Linlong Tong; Jisheng Zhang; Ning Chen; Xiangfeng Lin; Rui He; Lei Sun (Ocean Engineering, 2024)

Petrogenesis of the pyroxenitic Moho transition zone in the Zedong ophiolite, Southeastern Tibet - Zhen-Yu Zhang; Chuan-Zhou Liu; Yan Liang; Liang-Liang Zhang; Chang Zhang; Tong Liu; Bo-Da Liu; Wei-Qi Zhang; Yin-Zheng Lin; Wen-Bin Ji (Lithos, 2024)

Personal exposure to airborne organic pollutants and lung function changes among healthy older adults - Xiaojie Guo; Huimin Ren; Peijie Sun; Enmin Ding; Jianlong Fang; Ke Fang; Xiao Ma; Chenfeng Li; Chenlong Li; Yibo Xu; Kangning Cao; Elizabeth.Z. Lin; et al. (Environmental Research, 2024)

ForestAdvisor: A multi-modal forest decision-making system based on carbon emissions - Tong Ji; Yifeng Lin; Yuer Yang (Environmental Modelling & Software, 2024)

Role of polarized and interfacial built-in electric fields in photocatalysts for enhanced photocatalytic performance - Caiyu Luo; Chunping Yang; Jun Xie; Xiang Li; Yan Lin; Shehua Tong; Shanying He (Chemical Engineering Journal, 2024)

Fluorinated metal-organic framework aerogels with enhanced moisture resistance and efficient gas diffusion for CO2 capture - Huijuan Zhao; Feifei Lan; Hang Wang; Shaojuan Chen; Guodong Zhao; Tong Lin; Xupin Zhuang (Chemical Engineering Journal, 2024)

Concentration characteristics and emission estimates of major HCFCs and HFCs at three typical fluorochemical plants in China based on a Gaussian diffusion model - Zehua Liu; Jing Wu; Tengfei Ma; Minde An; Tong Ye; Xingchen Zhao; Mingzhu Li; Fan Wang; Mao Yuan; Dongmei Hu; Yueling Zhang; Lin Peng (Atmospheric Environment, 2024)

Effects of Humic Acid-Copper Interactions on Growth, Nutrient Absorption, and Photosynthetic Performance of Citrus sinensis Seedlings in Sand Culture - Wei-Tao Huang; Qian Shen; Hui Yang; Xu-Feng Chen; Wei-Lin Huang; Han-Xue Wu; Ning-Wei Lai; Lin-Tong Yang; Zeng-Rong Huang; Li-Song Chen (Journal of Plant Growth Regulation, 2024)

A 3D bedrock modeling method based on information mining of 2D geological map - Tong Niu; Bingxian Lin; Liangchen Zhou; Guonian Lv (Earth Science Informatics, 2024)

P21-52 Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - H. Hong; J. Li; T. Tong; X. Lin; Y. Xu; J. Lin; S. Liu; K. Luo; Z. Zhou (Toxicology Letters, 2024)

Optimizing waste leachate treatment for environmental and economic sustainability: Insights from a bottom-up study of over 300 cities - Qian-long Han; Hai-long Zhao; Guo-xia Wei; Han-qiao Liu; Yu-wen Zhu; Tong Li; Yan-fei Lin; Xin-rui Su (Sustainable Production and Consumption, 2024)

From sequences to sustainability: Exploring dipterocarp genomes for oleoresin production, timber quality, and conservation - Liuming Luo; Peng Ye; Qiongqiong Lin; Min Liu; Gang Hao; Tong Wei; Sunil Kumar Sahu (Plant Science, 2024)

Rare oxoisoaporphine alkaloids from Menispermum dauricum with potential anti-inflammatory activity - Rui Guo; Cun-Lin Wang; Xiao-Juan Cao; Xiao-Juan Yao; Xin Qiao; Ya-Tian Meng; Tong Zhang; Qiong Zhang (Phytochemistry, 2024)

Biocontrol potential of Bacillus velezensis QF-2 isolated from rhizosphere soil of Vickifunkia tianschanica - Tong Shen; Lei Zhang; Zhi-Han Ma; Zheng Gong; Hui-Ming Qi; Hong-Ying Yang; Yi-Lin He (Physiological and Molecular Plant Pathology, 2024)

Machine-learning-based corrections of CMIP6 historical surface ozone in China during 1950–2014 - Yuanxi Tong; Yingying Yan; Jintai Lin; Shaofei Kong; Zhixuan Tong; Yifei Zhu; Yukun Yan; Zhan Sun (Environmental Pollution, 2024)

Optimizing wolfberry crop productivity and economic sustainability using subsurface irrigation with ceramic emitters for smallholders: A four-year study - Xuanyue Tong; Pute Wu; Lin Zhang; Zhaoguo Wang (European Journal of Agronomy, 2024)

Small molecule perylene diimide derivatives with different bay site modifications as cathode interface layers for organic solar cells - Yanyan Wang; Dan Zhou; Senmei Lan; Jianwei Quan; Fang Wang; Lin Hu; Ruizhi Lv; Yujie Pu; Haitao Xu; Yongfen Tong; Bin Hu; Zhentian Xu; et al. (Chemical Engineering Journal, 2024)

Early-onset and later-onset cancer: trends, risk factors, and prevention in Northern China - Tong Liu; Chen-An Liu; Qing-Song Zhang; Qi Zhang; Yi-Ming Wang; Meng-Meng Song; Shi-Qi Lin; Li Deng; Shou-Ling Wu; Han-Ping Shi (Science China Life Sciences, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

Association Between COVID-19 and Neurological Diseases: Evidence from Large-Scale Mendelian Randomization Analysis and Single-Cell RNA Sequencing Analysis - Lin Huang; Yongheng Wang; Yijie He; Dongyu Huang; Tong Wen; Zhijie Han (Molecular Neurobiology, 2024)
Observational studies have suggested that SARS-CoV-2 infection increases the risk of neurological diseases, but it remains unclear whether the association is causal. The present study aims to evaluate the causal relationships between SARS-CoV-2 infections and neurological diseases and analyzes the potential routes of SARS-CoV-2 entry at the cellular level. We performed Mendelian randomization (MR) analysis with CAUSE method to investigate causal relationship of SARS-CoV-2 infections with neurological diseases. Then, we conducted single-cell RNA sequencing (scRNA-seq) analysis to obtain evidence of potential neuroinvasion routes by measuring SARS-CoV-2 receptor expression in specific cell subtypes. Fast gene set enrichment analysis (fGSEA) was further performed to assess the pathogenesis of related diseases. The results showed that the COVID-19 is causally associated with manic (delta_elpd, − 0.1300, Z -score: − 2.4; P = 0.0082) and epilepsy (delta_elpd: − 2.20, Z -score: − 1.80; P = 0.038). However, no significant effects were observed for COVID-19 on other traits. Moreover, there are 23 cell subtypes identified through the scRNA-seq transcriptomics data of epilepsy, and SARS-CoV-2 receptor TTYH2 was found to be specifically expressed in oligodendrocyte and astrocyte cell subtypes. Furthermore, fGSEA analysis showed that the cell subtypes with receptor-specific expression was related to methylation of lysine 27 on histone H3 (H3K27ME3), neuronal system, aging brain, neurogenesis, and neuron projection. In summary, this study shows causal links between SARS-CoV-2 infections and neurological disorders such as epilepsy and manic, supported by MR and scRNA-seq analysis. These results should be considered in further studies and public health measures on COVID-19 and neurological diseases.

Win-win integration: A mitochondria targeted AIE photosensitizer for hypochlorite detection and type I & type II photodynamic therapy - Jiahao Ni; Lichao Yu; Yixuan Wang; Tong Yang; Yueqi Bai; Bowen Zheng; Manshan Liang; Xiaoxia Ye; Yun-Yun Quan; Feifei Lin; Zu-Sheng Huang (Analytica Chimica Acta, 2024)

Effects of Environmental Enrichment on the Growth, Gonadal Development, and Welfare of the Chinese Hooksnout Carp (Opsariichthys bidens) - Yurui Lin; Qianhui Li; Zhuo Cai; Jiazheng Ye; Wanqing Tong; Siqi Ren; Xinrui Wu; Huixian Chen; Meidi Lü; Shanjian Zheng (Fishes, 2024)
To investigate the effects of environmental enrichment on the growth and welfare level of the Chinese hooksnout carp (Opsariichthys bidens), an experiment was carried out for 56 d with four types of enrichment environments: low-density physical enrichment, high-density physical enrichment, low-density social enrichment, and high-density social enrichment. The experimental results revealed that both physical and social enrichment treatments positively affected the growth and gonadal development of O. bidens. The physical enrichment treatment was found to increase the antioxidants’ content, such as CAT, SOD, and GSH, in the liver of O. bidens. Moreover, this treatment was able to lead to a reduction in MDA content and enhancement of the fish’s antioxidant capabilities. Behavioral observations, cortisol level analysis, and pcna gene expression analysis indicated that the physical enrichment treatment redused the clustering, aggression, and stress behaviors of O. bidens, maintaining them in a low-stress state. In most respects, the high-density physical enrichment has more positive effects than the low-density one. In contrast, the social enrichment treatments resulted in higher stress levels for O. bidens.

Salinity threshold for phosphorus limitation in an estuary-coast continuum - Shujie Cai; Weiran Liu; Zhuyin Tong; Lizhen Lin; Linjian Ou; Wupeng Xiao; Bangqin Huang (Frontiers in Marine Science, 2024)
River-derived nutrient imbalances can induce phosphorus (P) limitation in coastal plankton, but the salinity thresholds that govern this phenomenon have received little attention. Here, we provide a first insight into threshold responses in P-limitation along the salinity gradient in coastal ecosystems. Our seasonal sampling in the northern South China Sea showed a clear nonlinear decrease in alkaline phosphatase activity (APA) with increasing salinity. A pivotal finding was the identification of a salinity threshold at 32.83, presenting an early-warning indicator for P-limitation detection. Using a mixed-effects model, we further revealed that the robust positive correlation between phytoplankton biomass and APA gradually weakened as salinity increased toward this threshold. This implies a shift in phytoplankton’s P-limitation at this salinity threshold and the contribution of heterotrophic bacteria in APA within high-salinity seawater. These insights highlight the importance of refining monitoring strategies with salinity and APA dynamics as early-warning indicators for nutrient limitation in coastal ecosystems.

A Camera-LiDAR-IMU fusion method for real-time extraction of navigation line between maize field rows - Chao Ban; Lin Wang; Ruijuan Chi; Tong Su; Yueqi Ma (Computers and Electronics in Agriculture, 2024)

Knockdown of NUF2-derived exosomes can inhibit the migration and autophagy of BC cells and improve resistance to doxorubicin - Lin Luo; Tong Sha; Hongtao Li (Tissue and Cell, 2024)

Adaptations to changing substrates in diploblastic dinomischids from the early Cambrian - Yang Zhao; Ai-lin Chen; Christian Klug; Xiang-tong Lei; Pei-yun Cong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Strengthened oil-water separation by swirl vane hydrocyclone based on short-circuit flow regulation - Wei Zhao; Jian-ping Li; Tong Zhang; Aosong Wei; Shi-yun Li; Zi-heng Zhao; Xue-jing Yang; Xia Jiang; Hua-lin Wang (Journal of Water Process Engineering, 2024)

General performance, kinetic modification, and key regulating factor recognition of microalgae-based sulfonamide removal - Lin-Lan Zhuang; Weiyi Qian; Xiaoxiong Wang; Tong Wang; Jian Zhang (Journal of Hazardous Materials, 2024)

Rational design of Bacteria-Targeted and Photo-Responsive MOF gel with antibacterial and anti-inflammatory function for infected wound healing - Qiao-Tong He; Peipei Qian; Xin-Yi Yang; Qiancheng Kuang; Yue-Ting Lin; Wei Yi; Tianzhao Tian; Yue-Peng Cai; Xu-Jia Hong (Chemical Engineering Journal, 2024)

In vitro and in vivo studies of a biodegradable Zn-4Ag-0.1Sc alloy with high strength-elongation product, cytocompatibility, osteogenic differentiation, and anti-infection properties for guided bone-regeneration membrane applications - Xian Tong; Xinkun Shen; Zhiqiang Lin; Lei Lu; Khurram Munir; Runqi Zhou; Li Zhu; Yuncang Li; Jianfeng Ma; Cuie Wen; Jixing Lin (Chemical Engineering Journal, 2024)

Feedback of chain elongation microorganisms on iron-based conductive materials: Enhanced microbial functions and biotoxicity adaptation mechanisms - Wei-Tong Ren; Yang Lv; Zi-Lin He; Hua-Zhe Wang; Lin Deng; Shan-Shan Ye; Qing-Lian Wu; Wan-Qian Guo (Bioresource Technology, 2024)

In-situ treatment of gaseous benzene in fixed-bed biofilter with polyurethane foam: Functional population response and benzene transformation pathway - Wenwen Wang; Shuyan Zhang; Tong Gao; Lin Li (Bioresource Technology, 2024)

Occurrence, seasonal variations, and spatial distributions of current-use organoamine pesticides in the atmosphere of Shanghai, China - Junkang Ni; Minghong Cai; YongJun Lin; Tong Li; Jing Ma (Atmospheric Pollution Research, 2024)

The role of galectins in the regulation of autophagy and inflammasome in host immunity - Tzu-Han Lo; I-Chun Weng; Hung-Lin Chen; Fu-Tong Liu (Seminars in Immunopathology, 2024)

A Test System for Microwave-Assisted Dual-Mode Mechanical Cutting of Hard Rock Under True Triaxial Compression - Xia-Ting Feng; Xiang-xin Su; Cheng-xiang Yang; Feng Lin; Shi-ping Li; Jiu-yu Zhang; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)
This paper introduces a test system for microwave-assisted dual-mode mechanical cutting of hard rock under true triaxial compression. The test system was developed by Northeastern University, China, to simulate the cutting and breaking of hard rock by a tunnel boring machine (TBM). The test system is mainly composed of a dual-mode mechanical cutting subsystem, a true triaxial loading subsystem and a high-power microwave presplitting subsystem. The system performs dual-mode cutting under true triaxial stress, applies a single sensor to monitor the three-dimensional force of the cutter head, and integrates the reduction in the vibration and resistance to torsion during the cutting process. Mechanical cutting tests of basalt under different amounts of microwave irradiation and true triaxial stress conditions were conducted in Chifeng, Inner Mongolia, China. The results showed that microwave radiation presplitting effectively improved the efficiency of mechanical rock breaking. However, after 180 s of microwave irradiation, true triaxial high stress inhibited the mechanical breaking of basalt in terms of the overall excavation depth. During the tests, each system performed stably. The test results verified the reliability of the test system.

Ovalbumin promotes innate immune response of Caenorhabditis elegans through DAF-16 and SKN-1 pathways in insulin/IGF-1 signaling - Haibing Pei; Zhiyin Lin; Kexin Yao; Yeqing Luo; Ping Tong; Hongbing Chen; Yong Wu; Zhihua Wu; Jinyan Gao (Journal of Physiology and Biochemistry, 2024)

Upregulation of hsa-miR-141-3p promotes uterine cervical carcinoma progression via targeting dual-specificity protein phosphatase 1 - Zi-Qian Liang; Wei Zhang; Da-Tong Zeng; Jun-Hong Chen; Jia-Yuan Luo; Lin Shi; Kang-Lai Wei; Gang Chen (Functional & Integrative Genomics, 2024)

Impacts of urbanization on ecosystem carbon cycle: a case study of land use change in Tianjin metropolitan area - Yanning Gao; Guangjin Tian; Xiaowen Shi; Tong Lin (Environmental Monitoring and Assessment, 2024)

Experimental study on liquefaction influence factors of saturated silty soil using orthogonal design method - Chunxia Huang; Tong Cao; Lin Wang; Liang Zhang; Yanshun Chen; Lei Wang (Bulletin of Engineering Geology and the Environment, 2024)

Rederiving kinetics to model biohydrogen production from immobilized microalgae alginate beads at various polymerization degrees of alginate under dark fermentative environment - Jia Min Woon; Kuan Shiong Khoo; Nurul Tasnim Sahrin; Fatima Musa Ardo; Jun Wei Lim; Woei-Yenn Tong; Yi Jing Chan; Chuxia Lin; Pei Sean Goh; Sabah Ansar; Man Kee Lam (Algal Research, 2024)

Comparative Assessment of the Environmental and Economic Performance of Two Straw Utilization Pathways in China - Tong Li; Guoxia Wei; Hanqiao Liu; Yuwen Zhu; Yanfei Lin; Qianlong Han (BioEnergy Research, 2024)

Post-cyclic undrained behavior of marine soft clay subjected to partially drained cyclic loading - Junhao Tong; Qiang Wang; Weikang Zhang; Lin Guo; Dingyu Ni; Junli Zhai; Dongyang Yuan; Haozheng Wang (Marine Georesources & Geotechnology, 2024)

First success in captive breeding of the Tiger Cowrie, Cypraea tigris (Gastropoda: Cypraeidae), with notes on its early life development - Teresa S. Tay; K.E. Kayden Tong; Yuchen Sun; Mei Lin Neo (Molluscan Research, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - Huihui Hong; Jingdian Li; Tong Tong; Ting Yang; Hui Wang; Yudong Xu; Xiqin Lin; Jinxian Lin; Sicheng Liu; Kun Luo; Zhengping Yu; Wei Yuan; et al. (Science of The Total Environment, 2024)

Corrigendum to “Quantification and variation characteristics of baseflow nonpoint source pollution in Yiluo River Basin, China” [J. Hydrol. 626(Part B) (2023) 130303] - Jiake Zheng; Rong Gan; Xiaoxia Tong; Lin Guo; Hui Tang; Jie Tao (Journal of Hydrology, 2024)

Rice grain quality traits impacted by rice black-streaked dwarf virus disease - Yue Sun; Jiayuan Zhang; Linlin Du; Chenyang Li; Ying Lan; Tong Zhou; Xin Zhou; Baodong Wei; Feng Lin (Journal of Cereal Science, 2024)

Review on toxicology and activity of tomato glycoalkaloids in immature tomatoes - Li-hao Wang; De-hong Tan; Xue-song Zhong; Mei-qi Jia; Xue Ke; Yu-mei Zhang; Tong Cui; Lin Shi (Food Chemistry, 2024)

Insights into the catalytic mechanism of V-Mo@CN for the oxidation of 5-hydroxymethylfurfural to 2,5-diformylfuran - Shibo Yang; Tong Sun; Xiaokai Li; Wenbo Liao; Jianfei Bian; Xing Tang; Shuling Yang; Lu Lin; Wei Jiang; Lincai Peng; Yong Sun (Chemical Engineering Journal, 2024)

Dual regulation of the orderly aggregation of covalent organic frameworks at the molecular level and nanoscale to achieve efficient phototherapy and gene therapy - Tong Li; Dianwei Wang; Meng Meng; Xiaoya Guo; Lin Lin; Zhiyu Yang; Zhen Li; Longwei Xiang; Cong Liu; Jie Chen; Xuan Pang; Kai Hao; et al. (Chemical Engineering Journal, 2024)

Synergistic selenium doping and colloidal quantum dots decoration over ZnIn2S4 enabling high-efficiency photoelectrochemical hydrogen peroxide production - Hongyang Zhao; Yisen Yao; Mengke Cai; Xin Li; Peihang Li; Ali Imran Channa; Feng Lin; Mingzhu Wang; Zhiming M. Wang; Xin Tong (Chemical Engineering Journal, 2024)

Antiadhesive, antibacterial, and anti-inflammatory sandwich-structured ZIF8-containing gauze for enhanced wound healing - Xinghai Wu; Cheng Wang; Jia Wang; Yuchen Feng; Yunpeng Zhu; Yijia Pan; Yifan Yuan; Chenhui Chen; Junyan Cao; Jixing Lin; Xian Tong; Yuncang Li; et al. (Chemical Engineering Journal, 2024)

Effect of separation pretreatment on environmental and economic performance of sludge resource utilization - Shiqi Liu; Hanqiao Liu; Yuwen Zhu; Hailong Zhao; Tong Liu; Yanfei Lin; Huizhen Shi; Qianlong Han; Xueke Wang (Bioresource Technology, 2024)

Diagnosis of the accuracy of land cover classification using bootstrap resampling - Tong Yang; Binghong Han; Xiaofei He; Ziqi Ye; Yongli Tang; Jiexin Lin; Xia Cui; Jian Bi (International Journal of Remote Sensing, 2024)

Direct shear behaviors of excavated clay reinforced with geocomposite drainage layer encapsulated in thin sand layers - Lin-Jie Wang; Hui Xu; Jian-Wen Qian; Jin-Nan Wang; Liang-Tong Zhan (Environmental Science and Pollution Research, 2024)

Two new anti-inflammatory compounds from the roots and rhizomes of Clematis terniflora var . manshurica (Rupr.) Ohwi - Ping Shao; Sheng Dong; Lin-Tong Mu; Ling Han; Chong-Ning Lv; Jiu-Zhi Yuan; Jin-Cai Lu (Natural Product Research, 2024)

High-resolution and real-time wastewater viral surveillance by Nanopore sequencing - Xiaoqing Xu; Yu Deng; Jiahui Ding; Qinling Tang; Yunqi Lin; Xiawan Zheng; Tong Zhang (Water Research, 2024)

Intestinal microbiota via NLRP3 inflammasome dependent neuronal pyroptosis mediates anxiety-like behaviour in mice exposed to 3.5 GHz radiofrequency radiation - Gui-qiang Zhou; Xing Wang; Peng Gao; Tong-zhou Qin; Ling Guo; Zhao-wen Zhang; Zhi-fei Huang; Jia-jin Lin; Yun-tao Jing; Hao-nan Wang; Chun-ping Wang; Gui-rong Ding (Science of The Total Environment, 2024)

Decoding the influence of low temperature on biofilm development: The hidden roles of c-di-GMP - Yu-Ting Lin; Yong-Chao Wang; Yi-Mei Xue; Zhen Tong; Guan-Yu Jiang; Xu-Rui Hu; John C. Crittenden; Can Wang (Science of The Total Environment, 2024)

Removal of pesticide acetamiprid using KOH activated biochar derived from crayfish shell: Behavior and mechanism - Xiao-Wen Yao; Xie Chen; Man-Li Chen; Neng-Jia Feng; Lin-Yin Tong; Yun-Qiang Yi; Wei Qian; Zeng-Hui Diao (Process Safety and Environmental Protection, 2024)

Isolation of undescribed cladosporols and spirobisnaphthalenes from a plant pathogen Cladosporium cladosporioides F-10-2-A - Peng Li; Zi Jin Zhang; Yu Tong Guo; Jing Guan; Lin Bo Wen Xi; Li-Ping Lin (Phytochemistry, 2024)

A novel method for determining the neutral axis position of the asymmetric cross section and its application in the simplified progressive collapse method for damaged ships - Zhiyao Zhu; Huilong Ren; Atilla Incecik; Tong Lin; Chenfeng Li; Xueqian Zhou (Ocean Engineering, 2024)

Spatiotemporal distributions of dissolved N2O concentration, diffusive N2O flux and relevant functional genes along a coastal creek in southeastern China - Ping Yang; Yongxin Lin; Hong Yang; Chuan Tong; Linhai Zhang; Derrick Y.F. Lai; Dongyao Sun; Lishan Tan; Lele Tang; Yan Hong; Kam W. Tang (Journal of Hydrology, 2024)

Pade approximation operator iterative method for potential field downward continuation - Zhenhua Tai; Lin Chai; Yuanhao Wang; Tong Sun (Journal of Applied Geophysics, 2024)

Effect of the pore structure characteristics of coal samples on the dynamic adsorption of water vapor - Wei Zha; Baiquan Lin; Tong Liu; Ting Liu; Wei Yang; Xiangliang Zhang (Fuel, 2024)

The role of C18 fatty acids in improving the digestion and retrogradation properties of highland barley starch - Mengzi Nie; Jiaxin Li; Ran Lin; Xue Gong; Bin Dang; Wengang Zhang; Xijuan Yang; Lili Wang; Fengzhong Wang; Li-Tao Tong (Food Research International, 2024)

Insight into succinylated modified soy protein isolate-sodium alginate emulsion gels: Structural properties, interactions and quercetin release behavior - Sai Yang; Ziteng Lian; Lin Cheng; Xiuying Liu; Shicheng Dai; Xiaohong Tong; Huan Wang; Lianzhou Jiang (Food Hydrocolloids, 2024)

Flexible and stretchable photodetectors constructed by integrating photosensor, substrate, and electrode in one polymer matrix - Xiaoling Wu; Wenkang Wei; Haimen Lin; Tong Wu; Wenzhen Zheng; Guorong Chen; Weiang Luo; Conghui Yuan; Birong Zeng; Yiting Xu; Lizong Dai (Chemical Engineering Journal, 2024)

Hydrochromic convertibility on fiberized self-assembling of copper-based perovskite quantum dots - Li Liang; Junze Tong; Lifan Shen; Yuhang Zhang; Edwin Yue Bun Pun; Hai Lin (Chemical Engineering Journal, 2024)

Kinetics, products and mechanisms of unsaturated alcohols and NO3 radicals - Lin Hu; Shengrui Tong; Yanyong Xu; Hailiang Zhang; Meifang Chen; Xiang He; Maofa Ge (Atmospheric Environment, 2024)

Germ cell-specific gene 2 accelerates cell cycle in epithelial ovarian cancer by inhibiting GSK3α-p27 cascade - Keyu Zhu; Xiaolu Ma; Xiaolin Guan; Ying Tong; Suhong Xie; Yanchun Wang; Hui Zheng; Lin Guo; Renquan Lu (Journal of Molecular Histology, 2024)
Epithelial ovarian cancer (EOC) is one of the most common malignant gynecological tumors with rapid growth potential and poor prognosis, however, the molecular mechanism underlying its outgrowth remained elusive. Germ cell-specific gene 2 (GSG2) was previously reported to be highly expressed in ovarian cancer and was essential for the growth of EOC. In this study, GSG2-knockdown cells and GSG2-overexpress cells were established through lentivirus-mediated transfection with Human ovarian cancer cells HO8910 and SKOV3. Knockdown of GSG2 inhibited cell proliferation and induced G2/M phase arrest in EOC. Interestingly, the expression of p27, a well-known regulator of the cell cycle showed a most significant increase after GSG2 knockdown. Further phosphorylation-protein array demonstrated the phosphorylation of GSK3αSer21 decreased in GSG2-knockdown cells to the most extent. Notably, inhibiting GSK3α activity effectively rescued GSG2 knockdown’s suppression on cell cycle as well as p27 expression in EOC. Our study substantiates that GSG2 is able to phosphorylate GSK3α at Ser21 and then leads to the reduction of p27 expression, resulting in cell cycle acceleration and cell proliferation promotion. Thus, GSG2 may have the potential to become a promising target in EOC.

Spatially confined CuFe2O4 nanosphere in N/O-codoped porous carbon mimetics for triple-mode sensing of antibiotics and visual detection of neurotransmitters in biofluids - Ying Lin; Wan-Wan Shao; Dan Wu; Tong Zhang; Dan-Ni Fei; Ya-Nan Kong; Yi-Fan Gao; Shu-Chang Zhao; Rui-Lin Liu (Analytica Chimica Acta, 2024)

Distribution and Formation Causes of PM2.5 and O3 Double High Pollution Events in China during 2013–20 - Zhixuan Tong; Yingying Yan; Shaofei Kong; Jintai Lin; Nan Chen; Bo Zhu; Jing Ma; Tianliang Zhao; Shihua Qi (Advances in Atmospheric Sciences, 2024)

CYTOR-NFAT1 feedback loop regulates epithelial-mesenchymal transition of retinal pigment epithelial cells - Rong Zhang; Lin Wang; Yang Li; Yan Liu; Kui Dong; Yajing Pei; Junmei Zhao; Gang Liu; Jing Li; Xiaodan Zhang; Tong Cui; Yan Gao; et al. (Human Cell, 2024)

Identification and health risk evaluation of soil contaminated by polycyclic aromatic hydrocarbons at shale gas extraction sites based on positive matrix factorization - Zhilei Liu; Tong Zheng; Qiyu Chen; Xichao Chen; Yi Xie; Yuyu Wang; Mingzhong Ren; Zhi-qiang Gao; Bigui Lin; Xidan Feng (Chemosphere, 2024)

Secondary infections may cause host mortality by inhibiting NRF1-mediated antiviral immune responses - Xu Feng-Lin; Wang Cheng-Qiang; Yin Cheng-Ming; Sun Ya-Nan; Cao Xiao-Tong; Lan Jiang-Feng (Aquaculture, 2024)

Wavelength dependency and photosensitizer effects in UV-LED photodegradation of iohexol - Meng-Yuan Xu; Chao Zeng; Yi-Li Lin; Tian-Yang Zhang; Qi Fu; Heng-Xuan Zhao; Zhen-Ning Luo; Zheng-Xiong Zheng; Tong-Cheng Cao; Chen-Yan Hu; Bin Xu (Water Research, 2024)

Biodegradation of phthalate acid esters and whole-genome analysis of a novel Streptomyces sp. FZ201 isolated from natural habitats - Nai-Xian Feng; Da-Wei Li; Fei Zhang; Hui Bin; Yi-Tong Huang; Lei Xiang; Bai-Lin Liu; Quan-Ying Cai; Yan-Wen Li; De-Lin Xu; Yunchang Xie; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Study on the influence law of gangue filling structure on the gas emission in adjacent coal seams - Jiahao Shen; Yu Shi; Baiquan Lin; Ting Liu; Yang Shen; Tong Liu; Xiangliang Zhang; Wei Yang (Journal of Cleaner Production, 2024)

Glowing and flaming autoignition of wood exposed to coupled convective and radiative heating - Junhui Gong; Hu Lin; Tong Cui; Haochen Lian; Lun Li; Kun Zhao (Fuel, 2024)

A CRISPR/Cas12a-assisted bacteria quantification platform combined with magnetic covalent organic frameworks and hybridization chain reaction - Xuening Shi; Hang Li; Shuo Yao; Yukun Ding; Xiuzhu Lin; Hui Xu; Yi Liu; Chao Zhao; Tong Zhang; Juan Wang (Food Chemistry, 2024)

Overall quality changes and deterioration mechanism of fragrant rapeseed oils during 6-Month storage - Chen Chen; Ping-Ping Ye; Feng-Jie Cui; Ming Tan; Hai-Bo Zhang; Tong-Lin Zhou; Jian-Cheng Shi; Xue-Quan Shu; Zhi-Wei Chen (Food Chemistry, 2024)

PHB2 inhibits WSSV replication by promoting the nuclear translocation of STAT - Jia-Yu Si; Lian-Jie Wu; Feng-Lin Xu; Xiao-Tong Cao; Jiang-Feng Lan (Fish & Shellfish Immunology, 2024)

Rhythmic mild photothermal therapy enhancing anti-PD-L1 response for oral squamous cell carcinoma immunotherapy - Tao Liu; Shilin Guo; Dongyao Zhang; Diya Xie; Xinyu Zhang; Lin Chen; Yanyi Wang; Huihui Zou; Linzhong Yang; Meng Zhou; Xin Tong; Jianchuan Ran; et al. (Chemical Engineering Journal, 2024)

Machine learning solution for regional landslide susceptibility based on fault zone division strategy - Yunhao Wang; Luqi Wang; Songlin Liu; Weixin Sun; Pengfei Liu; Lin Zhu; Wenyu Yang; Tong Guo (Journal of Mountain Science, 2024)

Low-abundance proteins-based label-free SERS approach for high precision detection of liver cancer with different stages - Tong Sun; Yamin Lin; Yun Yu; Siqi Gao; Xingen Gao; Hongyi Zhang; Kecan Lin; Juqiang Lin (Analytica Chimica Acta, 2024)

Carbon doping enhances the fluoride removal performance of aluminum-based adsorbents - Lin Tong; Ying Miao; Shushu Li; Ning Bao; Qingwen Zhou; Yuhuan Yang; Changqing Ye (Environmental Science and Pollution Research, 2024)

Responses to light in terms of embryonic development and larval phototactic behavior in sea cucumber, Apostichopus japonicus - Haoyu Tong; Xu Wang; Mingxin Lyu; Beini Deng; Libin Zhang; Chenggang Lin (Aquaculture, 2024)

Ferrate(VI) assists in reducing cytotoxicity and genotoxicity to mammalian cells and organic bromine formation in ozonated wastewater - Ye Du; Tong Liu; Lu-Lin Yang; Zhi-Min Song; Xin Dai; Wen-Long Wang; Bo Lai; Qian-Yuan Wu (Water Research, 2024)

PI3K/AKT mediated De novo fatty acid synthesis regulates RIG-1/MDA-5-dependent type I IFN responses in BVDV-infected CD8+T cells - Shan-shan Liu; Tong-tong Bai; Tao-lin Que; An Luo; Yu-xin Liang; Yu-xin Song; Tian-yi Liu; Jin-wei Chen; Jing Li; Nan Li; Ze-chen Zhang; Nan-nan Chen; et al. (Veterinary Microbiology, 2024)

Enhancing flood-response commuting resilience via driving mechanism investigation: New evidence from Wuhan, China - Huiting Chen; Hongxin Zhang; Zhaomin Tong; Ying Jing; Lin Zhang; Sui Liu; Yan Zhang; Cuizhen Chen; Yaolin Liu (Travel Behaviour and Society, 2024)

Co-foliar application of zinc and nano-silicon to rice helps in reducing cadmium exposure risk: Investigations through in-vitro digestion with human cell line bioavailability assay - Qiang Lin; Yasir Hamid; Honhang Wang; Min Lu; Xuerui Cao; Tong Zou; Zhiqin Chen; Bilal Hussain; Ying Feng; Tingqiang Li; Zhenli He; Xiaoe Yang (Journal of Hazardous Materials, 2024)

Boron-mediated amelioration of copper toxicity in Citrus sinensis seedlings involved reduced concentrations of copper in leaves and roots and their cell walls rather than increased copper fractions in their cell walls - Huan-Huan Chen; Zhi-Chao Zheng; Dan Hua; Xu-Feng Chen; Zeng-Rong Huang; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2024)

Emergence of tet(X4)-positive Enterobacterales in retail eggs and the widespread of IncFIA(HI1)-HI1A-HI1B(R27) plasmids carrying tet(X4) - Chao Yue; Yuman Bai; Tong Li; Haotian Deng; Litao Lu; Wannan Lin; Xiaoxiao Cui; Luchao Lv; Guolong Gao; Jian-Hua Liu; Yi-Yun Liu (International Journal of Food Microbiology, 2024)

Transesterification of acidic palm oil using solid waste/CaO as a bifunctional catalyst - Jisen Liu; Tong Lin; Shengli Niu; Jie Zhu; Zihao Yang; Jie Geng; Sitong Liu; Yue Zheng; Bo Liang; Xiaobin Sun; Huaji Zhang (Fuel, 2024)

Controllable lignin valorization to value-added aromatic chemicals by a UV-assisted ternary heterogeneous photo-fenton catalytic system - Fen Wang; Lin Zhang; Zhiping Wu; Wenbo Peng; Peng Zhan; Lishu Shao; Hui Wang; Yan Qing; Hanxue Lin; Quan Wei; Na Liu; Zhaohui Tong (Fuel, 2024)

Anti-obesity effect of fucoidan from Laminaria japonica and its hydrothermal degradation product - Hai-Yan Lu; Xue Zhao; Tong-Jie Liu; Xi Liang; Mao-Zhen Zhao; Xiao-Ying Tian; Hua-Xi Yi; Pi-Min Gong; Kai Lin; Zhe Zhang; Lan-Wei Zhang (Food Bioscience, 2024)

Effect of phlorotannins modification on the physicochemical, structural and functional properties of soybean protein isolate and controlled hydrolysates: Covalent and non-covalent interactions - Lin Cheng; Ziteng Lian; Xiuying Liu; Shicheng Dai; Lanxin Li; Mengmeng Wang; Ka Li; Kunyu Ren; Xiaohong Tong; Huan Wang; Lianzhou Jiang (Food Hydrocolloids, 2024)

Enhancement of anaerobic digestion from food waste via inert substances based on metagenomic analysis: Oxidative phosphorylation and metabolism - Xiupeng Jiang; Zongsheng Li; Kunsen Lin; Youcai Zhao; Lianghu Su; Tong Wu; Tao Zhou (Environmental Research, 2024)

The fabrication of thin-film nanocomposite membrane for organic solvent forward osmosis via host-guest chemistry of α-cyclodextrin - Lin Wang; Fangkun Xiao; Haochen Ge; Yunbo Tong; Congjie Gao; Guiru Zhu (Desalination, 2024)

Global multifaceted biodiversity patterns, centers, and conservation needs in angiosperms - Ao Luo; Yaoqi Li; Nawal Shrestha; Xiaoting Xu; Xiangyan Su; Yichao Li; Tong Lyu; Kilara Waris; Zhiyao Tang; Xiaojuan Liu; Luxiang Lin; Yongsheng Chen; et al. (Science China Life Sciences, 2024)

Alternation of social behaviors for zebrafish (Danio rerio) in response to acute cold stress - Sian-Tai Liu; Chun-Yung Chang; Kuang-Yung Lee; Sok-Keng Tong; Han-Liang Huang; Hsi Chen; Jiun-Lin Horng; Ming-Yi Chou (Fish Physiology and Biochemistry, 2024)

Latitudinal responses of wetland soil nitrogen pools to plant invasion and subsequent aquaculture reclamation along the southeastern coast of China - Lishan Tan; Ping Yang; Xiao Lin; Yongxin Lin; Linhai Zhang; Chuan Tong; Yan Hong; Derrick Y.F. Lai; Kam W. Tang (Agriculture, Ecosystems & Environment, 2024)

Regional ship collision risk prediction: An approach based on encoder-decoder LSTM neural network model - Chenyan Lin; Rong Zhen; Yanting Tong; Shenhua Yang; Shengkai Chen (Ocean Engineering, 2024)

Perturbation of lipid metabolism in 3T3-L1 at different stages of preadipocyte differentiation and new insights into the association between changed metabolites and adipogenesis promoted by TBBPA or TBBPS - Yun-Jiang Yu; Jing-Lin Tian; Tong Zheng; Hong-Xuan Kuang; Zong-Rui Li; Chao-Jie Hao; Ming-Deng Xiang; Zhen-Chi Li (Journal of Hazardous Materials, 2024)

Effects of atrazine and curcumin exposure on TCMK-1 cells: Oxidative damage, pyroptosis and cell cycle arrest - Mengyao Ren; Xiunan Lv; Tong Xu; Jiatong Sun; Meichen Gao; Hongjin Lin (Food and Chemical Toxicology, 2024)

Research on the influence of parallel joints on the extension length and morphology of blasting cracks - Yang Shen; Baiquan Lin; Ting Liu; Minghua Lin; Tong Liu; Wei Yang; Fei Lin; Guang Xia (Computers and Geotechnics, 2024)

Polynorepinephrine-regulated filler sulfonation toward interfacial reformation and conductive promotion of nanocomposite proton exchange membrane - Tong Huang; Xin Liu; Ruibin Ma; Yangyang Gao; Xiaomin Xu; Chengrun Yan; Yuchen Guo; Xiaoxu Li; Yanzhou Qin; Lingling Liu; Jiandang Xue; Huadong Huang; et al. (Chemical Engineering Journal, 2024)

Optimization of Microwave Presplitting Iron Ore to Improve Mechanical Mining Efficiency - Feng Lin; Xia-ting Feng; Shi-ping Li; Jiu-yu Zhang; Xiang-xin Su; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)

Rice responds to Spodoptera frugiperda infestation via epigenetic regulation of H3K9ac in the jasmonic acid signaling and phenylpropanoid biosynthesis pathways - Rongrong Xue; Ruiqing Guo; Qing Li; Tianhuang Lin; Zicha Wu; Ning Gao; Fei Wu; Lu Tong; Rensen Zeng; Yuanyuan Song; Jie Wang (Plant Cell Reports, 2024)

Feeding experience on hairy vetch induces a loss of host-specific adaptation to maize and changes in the gut microbiota communities of the fall armyworm - Lin Ma; Dao-Tong Wang; Qi-Lin Ren; Lei Zhang; Yun-Xia Cheng; Xing-Fu Jiang (Journal of Pest Science, 2024)

Mapping land-use and land-cover changes through the integration of satellite and airborne remote sensing data - Meng-Hsuan Lin; Ying-Tong Lin; Min-Lin Tsai; Yi-Ying Chen; Yi-Chun Chen; Hsueh-Ching Wang; Chi-Kuei Wang (Environmental Monitoring and Assessment, 2024)

The research on a novel multivariate grey model and its application in carbon dioxide emissions prediction - Yan Xu; Tong Lin; Pei Du; Jianzhou Wang (Environmental Science and Pollution Research, 2024)

Improvement of non-specific immunity, intestinal health and microbiota of crucian carp (Carassius auratus) juvenile with dietary supplementation of Bacillus coagulans BC1 - Ren-Ge Hu; Bin-Tong Yang; Zi-Yan Zheng; Zhen-Lin Liang; Yuan-Huan Kang; Wei Cong (Aquaculture, 2024)

Significant inter-annual fluctuation in CO2 and CH4 diffusive fluxes from subtropical aquaculture ponds: Implications for climate change and carbon emission evaluations - Ping Yang; Linhai Zhang; Yongxin Lin; Hong Yang; Derrick Y.F. Lai; Chuan Tong; Yifei Zhang; Lishan Tan; Guanghui Zhao; Kam W. Tang (Water Research, 2024)

Influence of bionics shark gills tunnel portal on the micro-pressure wave at the tunnel exit - Tong-tong Lin; Ming-zhi Yang; Lei Zhang; Tian-tian Wang; Sha Zhong (Tunnelling and Underground Space Technology, 2024)

Foliar application of plant growth regulators for enhancing heavy metal phytoextraction efficiency by Sedum alfredii Hance in contaminated soils: Lab to field experiments - Zhiqin Chen; Qizhen Liu; Shijun Zhang; Yasir Hamid; Jiapan Lian; Xiwei Huang; Tong Zou; Qiang Lin; Ying Feng; Zhenli He; Xiaoe Yang (Science of The Total Environment, 2024)

Taste traces: Capsaicin and sweeteners as anthropogenic markers in municipal wastewater - Xue-Ting Shao; Yan-Song Wang; Yue-Tong Zhao; Jian-Guo Lin; Wei Pei; Ming-Xing Guo; De-Gao Wang (Science of The Total Environment, 2024)

Fine-scale monitoring of lake ice phenology by synthesizing remote sensed and climatologic features based on high-resolution satellite constellation and modeling - Jie Tong; Yaling Lin; Chenyu Fan; Kai Liu; Tan Chen; Fanxuan Zeng; Pengfei Zhan; Linghong Ke; Yongnian Gao; Chunqiao Song (Science of The Total Environment, 2024)

The impact of long-term PM1 exposure on all-cause mortality and its interaction with BMI: A nationwide prospective cohort study in China - Jie Jiang; Yongyue Wei; Ying Wang; Xiaowen Wang; Xiao Lin; Tong Guo; Xurui Sun; Zhiqiang Li; Yuqin Zhang; Gonghua Wu; Wenjing Wu; Shirui Chen; et al. (Science of The Total Environment, 2024)

Fucoidan-based antibody-free magnetic nanoparticle for on-site detection of waterborne SARS-CoV-2 - Jinhui Zhu; Huijun Lu; Qiuyuan Lin; Tong Zhang; Guang Chen; Yang Zhou; Guodong Sui (Science of The Total Environment, 2024)

A tale of two vein types: Bed-parallel fibrous versus blocky filled fractures in organic-rich shales and their overpressured hydrocarbon fluids - Miao Wang; Feng Liang; Tong Lin; Yelei Wang; Hui Zhang; Qian Huang; Yifan Song; Tingting Liu; Yanwei Feng; Rui Ni; Xiaoying Guo; Tengfei Zhou; et al. (Marine and Petroleum Geology, 2024)

Regeneration of sedimentary phosphorus and iron in a large seasonally hypoxic estuary deciphered by 224Ra/228Th disequilibria - Zhongliang Lin; Yilin Cheng; Ergang Lian; Tong Wu; Lin Wei; Xiangming Shi; Xinyu Jiang; Liuting Yuan; Shouye Yang; Pinghe Cai (Marine Chemistry, 2024)

The Earth Summit Mission-2022: Successful ozone soundings contribute to source identification in the north Mt. Qomolangma region - Jinqiang Zhang; Chunxiang Ye; Yuejian Xuan; Zhixuan Bai; Weili Lin; Dan Li; Lingkun Ran; Baofeng Jiao; Yaoming Ma; Weiqiang Ma; Nan Yao; Yunshu Zeng; et al. (Journal of Environmental Sciences, 2024)

Deeply analyzing dynamic fermentation of highland barley vinegar: Main physicochemical factors, key flavors, and dominate microorganisms - Yan Li; Aixia Wang; Bin Dang; Xijuan Yang; Mengzi Nie; Zhiying Chen; Ran Lin; Lili Wang; Fengzhong Wang; Li-Tao Tong (Food Research International, 2024)

Mechanisms underlying palmitic acid-induced disruption of locomotor activity and sleep behavior in Drosophila - Yumei Huang; Jiaqi Zhang; Dongdong You; Shangqin Chen; Zhongdong Lin; Boyang Li; Menglai Ling; Haibin Tong; Feng Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

The role of a small molecular dipole moment for efficient non-doped deep blue thermally activated delayed fluorescence emitters - Hong-Ji Tan; Jie-Rong Yu; Zhi-Zhong Lin; Guo-Xi Yang; Zhi-Qiang Long; Ying-Lan Deng; Ze-Lin Zhu; Xian-Kai Chen; Jing-Xin Jian; Qing-Xiao Tong; Chun-Sing Lee (Chemical Engineering Journal, 2024)

Rapid and efficient preparation of cationized lignin for downstream high value-added utilization of biodegradable antimicrobial nanofibrous membranes - Yu-Fei Gao; Cheng-Ye Ma; Qian Sun; Xin-Xu Zhang; Jing Liu; Jia-Long Wen; Rou-Xi Chen; Hsing-Lin Wang; Tong-Qi Yuan (Chemical Engineering Journal, 2024)

High fractal-dimensional carbon conductive agent for improving the Li storage performance of Si-based electrode - Yueqiang Lin; Bin Qi; Chao Huangfu; Xinhou Yang; Zheng Liu; Su Zhang; Tong Wei; Zhuangjun Fan (Chemical Engineering Journal, 2024)

Green Synthesis of Carbon Aerogel Derived from Lotus Root for the Removal of Ciprofloxacin, Oil, Organic Solvents, and Supercapacitor Applications - Mai Thanh Phong; Phan Minh Tu; Nguyen Duy Hai; Nguyen Thanh Hoai Nam; Vo Minh Quan; Tran Ngoc Son; Tong Hoang Lin; Le Gia Han; Nguyen Truong Son; Nguyen Huu Hieu; Ton That Buu (Water, Air, & Soil Pollution, 2024)

Human milk oligosaccharides and the association with microbiota in colostrum: a pilot study - Wen Sun; Lin Tao; Chen Qian; Peipei Xue; Xiankun Tong; Li Yang; Fang Lu; Hua Wan; Yingna Tao (Archives of Microbiology, 2024)
HMOs (Human milk oligosaccharide) has an impact on maternal and infant health. Colostrum samples of 70 breastfeeding women in China were collected and recorded clinical characteristics. The major oligosaccharides and microbiota were quantitated in colostrum. The concentration of fucosylated HMOs in primipara was higher than that of multipara ( p = 0.030). The concentration of N-acetylated HMOs in vaginal delivery milk was less than that of cesarean ( p = 0.038). Non-fucosylated HMOs of breastfeeding women were less than that of breast pump ( p = 0.038). Meanwhile, the concentration of LNT was positively correlated with Lactobacillus ( r = 0.250, p = 0.037). DS-LNT was negatively correlated with Staphylococcus ( r = – 0.240, p = 0.045). There was a positive correlation of Streptococcus with LNFP II ( r = 0.314, p = 0.011) and 3-SL ( r = 0.322, p = 0.009). In addition, there was a negative correlation between 2'-FL and 3-FL ( r = – 0.465, p = 0.001). There was a positive correlation between LNT and LNnT ( r = 0.778, p = 0.001). Therefore, the concentration of HMOs is related to number of deliveries, delivery mode, lactation mode and perinatal antibiotic. The concentration of HMOs is related to Lactobacillus , Streptococcus and Streptococcus in colostrum. In addition, there are connections between different oligosaccharides in content. The study protocol was also registered in the ClinicalTrails.gov (ChiCTR2200064454) (Oct. 2022).

Effects of dietary betaine supplementation on growth performance, feed intake, intestinal histology, lipid metabolism, and immune response of black tiger shrimp (Penaeus monodon) fed diets containing two levels of raw feed attractants - Gui-Lun He; Meng-Lin Shi; Yu-Cheng Liu; Liu-Tong Chen; Xin Chen; Wen-Bo Zhu; Zheng-Bang Chen; Bei-Ping Tan; Shi-Wei Xie (Aquaculture International, 2024)

XFEM-Based Study of Fatigue Crack Propagation in Rocket Deflector Troughs under Coupled High-Temperature and Impact Conditions - Zhixin Xiong; Chengyuan Zhu; Yue Yang; Tong Lin; Ruoxuan Li (Journal of Marine Science and Engineering, 2024)
This research investigated fatigue crack propagation on the lower surface of rocket deflector troughs in offshore rocket launch platforms. Initially, a numerical model of an offshore rocket launch platform was established using ABAQUS based on the Extended Finite Element Method (XFEM). Subsequently, two variable parameters—the initial crack length and initial tilt angle—were introduced. This research systematically analysed the impact of these parameters on the fatigue crack propagation patterns in both the maximum stress and maximum deformation regions of the deflector channels under the combined conditions of high temperature and impact. Finally, the research indicated that the propagation length of surface cracks in the deflector trough exhibited an initial increase followed by a decrease with the rise in the pre-set inclination angle. Notably, the stable propagation rate of the crack in the region of maximum deformation surpassed that observed in the region of maximum stress. Through meticulous comparative analysis, it was evident that temperature loading significantly exacerbated the initiation and propagation of cracks, particularly in the upper region of the deflector channel’s lower surface.

Three new cardenolides from the fruits of Cascabela thevetia (L.) Lippold and their cytotoxic activities - Juan Long; Jia-Cheng Ouyang; Yu-Hao Luo; Qi-Jing Wu; Xiao-Tong Liao; Zhi-Le Chen; Qi-Lin Wang; Xiao-Yan Liang; Li Liu; Xue-Mei Yang; Xiao-San Li (Natural Product Research, 2024)

A novel Vibrio alginolyticus phage and its therapy application in Portunus trituberculatus larvae - Ruqian Cai; Dengfeng Li; Weinan Qin; Wei Lin; Lingting Pan; Minhua Qian; Fei Wang; Chunlin Wang; Changkao Mu; Yigang Tong (Aquaculture, 2024)

BPA and low-Se exacerbate apoptosis and autophagy in the chicken bursa of Fabricius by regulating the ROS/AKT/FOXO1 pathway - Wenying Sun; Tong Xu; Hongjin Lin; Yilin Yin; Shiwen Xu (Science of The Total Environment, 2024)

Aerobic methane production by phytoplankton as an important methane source of aquatic ecosystems: Reconsidering the global methane budget - Yufeng Mao; Tong Lin; Hong Li; Ruixu He; Kailai Ye; Weiwei Yu; Qiang He (Science of The Total Environment, 2024)

Evaluating nutrient limitation in co-culture of Chlorella pyrenoidosa and Rhodobacter sphaeroides - Xiao-Fei Shen; Ya-Ping Xu; Yi-Fan Jiang; Lin-Jun Gao; Xiao-Qin Tong; Jing Gong; Yan-Fang Yang; Raymond Jianxiong Zeng (Science of The Total Environment, 2024)

Peptides: Opening the door - Zongcheng Lin; Ke Jin; Noni Franklin-Tong (Molecular Plant, 2024)

BMP4 up-regulated by 630 nm LED irradiation is associated with the amelioration of rheumatoid arthritis - Guoming Du; Mengyue Liu; Yue Qi; Monan Lin; Jiaxin Wu; Wenting Xie; Dandan Ren; Siqi Du; Tong Jia; Fengmin Zhang; Wuqi Song; Hailiang Liu (Journal of Photochemistry and Photobiology B: Biology, 2024)

Eupatilin inhibits xanthine oxidase in vitro and attenuates hyperuricemia and renal injury in vivo - Guitao Xu; Lele Wu; Hongxuan Yang; Tianfeng Liu; Ying Tong; Jiliang Wan; Bin Han; Lin Zhou; Xuguang Hu (Food and Chemical Toxicology, 2024)

Returning personal genetic information on susceptibility to arsenic toxicity to research participants in Bangladesh - Lizeth I. Tamayo; Syed Emdadul Haque; Tariqul Islam; Alauddin Ahmed; Moziber Rahman; Abu Horayra; Lin Tong; Lin Chen; Aresha Martinez-Cardoso; Habibul Ahsan; Brandon L. Pierce (Environmental Research, 2024)

pH-tailored activated water reservoir for rapid solar water purification via dual-layer hydrogel architecture - Xue-Tong Yang; Huan Lin; Jia-Chen Zhang; Gangqiang Yu; Yuelian Peng; Quan-Fu An (Chemical Engineering Journal, 2024)

Spatio-temporal variation of toxin-producing gene abundance in Microcystis aeruginosa from Poyang Lake - Lin Wu; Li Zhang; Lijuan Yuan; Qiegen Liao; Jianjun Xiang; Dawen Zhang; Tong Qiu; Jutao Liu; Junhui Guo (Environmental Science and Pollution Research, 2023)

Toward a mechanistic understanding of Rhenium(VII) adsorption behavior onto aminated polymeric adsorbents: Batch experiments, spectroscopic analyses, and theoretical computations - Shuo Lin; Juan Mao; Jian Xiong; Yuhang Tong; Xiejuan Lu; Tao Zhou; Xiaohui Wu (Chemosphere, 2023)

Eminent destruction of organics and pathogens concomitant with power generation in a visible light-responsive photocatalytic fuel cell with NiFe2O4/ZnO pine tree-like photoanode and CuO/Cu2O nanorod cathode - Sze-Mun Lam; Jin-Chung Sin; Meng Wei Warren Tong; Honghu Zeng; Haixaing Li; Liangliang Huang; Hua Lin; Jun-Wei Lim (Chemosphere, 2023)

Ioxynil and diethylstilbestrol impair cardiac performance and shell growth in the mussel Mytilus coruscus - Yi-Feng Li; Yue-Tong Lin; Yu-Qing Wang; Ji-Yue Ni; Deborah M. Power (Science of The Total Environment, 2023)

Corrigendum to “Co-exposure of silica nanoparticles and methylmercury induced cardiac toxicity in vitro and in vivo” [Sci. Total Environ. 631–632 (2018) 811–821] - Xiaozhe Yang; Lin Feng; Yannan Zhang; Hejing Hu; Yanfeng Shi; Shuang Liang; Tong Zhao; Lige Cao; Junchao Duan; Zhiwei Sun (Science of The Total Environment, 2023)

New insights into brain injury in chickens induced by bisphenol A and selenium deficiency—Mitochondrial reactive oxygen species and mitophagy-apoptosis crosstalk homeostasis - Huanyi Liu; Hongjin Lin; Tong Xu; Xu Shi; Yujie Yao; Pervez Ahmed Khoso; Zhihui Jiang; Shiwen Xu (Science of The Total Environment, 2023)

Vacuolar H+-ATPase and BZR1 form a feedback loop to regulate the homeostasis of BR signaling in Arabidopsis - Yu-Tong Jiang; Lu-Han Yang; Ji-Xuan Zheng; Xian-Chen Geng; Yu-Xuan Bai; Yu-Chen Wang; Hong-Wei Xue; Wen-Hui Lin (Molecular Plant, 2023)

Comparison of microalgae cultivation modes for advanced wastewater purification and pollutant-resource conversion: A pilot study - Lin-Lan Zhuang; Pengfei Yang; Shuang Liang; Tong Yu; Chao Liu; Tingting Zhao; Guoliang Tan; Yueying Niu; Jian Zhang (Journal of Water Process Engineering, 2023)

Exploring the potential of magnetic persimmon tannins-based bio-adsorbent for Cd (II) ions removal from water: Experiment and DFT study - Fan Zhou; Lin Gao; Shunyan Cui; Jing Tian; Tong Wang; Guiyin Li; Zhongmin Wang; Chaoke Qin; Dahong Lin; Weijiang Gan; Zhaojin Ran (Journal of Water Process Engineering, 2023)

Influence law and control mechanism of overburden isolated grout injection on methane emission in the working face - Youping Xu; Baiquan Lin; Ting Liu; Junwen Cao; Tong Liu (Journal of Cleaner Production, 2023)

Multi-objective optimization of gas-steam-power system for an integrated iron and steel mill considering carbon emission reduction and cost - Tingting Xu; Zhaoyi Huo; Tong Wang; Jiawei Lv; Yixuan Han; Lin Mu (Journal of Cleaner Production, 2023)

Integrated multifunctional nanoplatform for fluorescence detection and inactivation of Staphylococcus aureus - Jing-bo Jiao; Qing Kang; Jiang-li Cao; Shuai-qi Zhang; Chen-jing Ma; Tong Lin; Ze-hui Xiao; Chu-min Zhao; Ting Du; Xin-jun Du; Shuo Wang (Food Chemistry, 2023)

An acidic heteropolysaccharide rich in galactose and arabinose derived from ginger: Structure and dynamics - Xiao-tong Lin; Bo-xian Xiao; Jun-ping Liu; Ming-yuan Cao; Zhi-ping Yang; Li-yan Zhao; Gui-tang Chen (Food Bioscience, 2023)

A two-stage optimization method for improving the load flexibility of existing district energy systems - Quanyi Lin; Shilei Lu; Lu Yue; Tong Guo (Energy and Buildings, 2023)

Construction of molecular enrichment accelerators via assembly of enzyme surface grafted polymer and cyclodextrin achieving rapid and stable ester catalysis for biodiesel synthesis - Qi Ao; Lin Jiang; Xinglai Tong; Ying Song; Xiaoxiao Lv; Jun Tang (Carbohydrate Polymers, 2023)

Bioleaching of Silicon from Fly Ash by Co-culture of Silicate Bacteria and Fungi - Yanzhu Lin; Shida Li; Xuefeng Li; Hanrui Lin; Ningfei Lei; Di Wu; Jin Tong; Hongguan Xie (Water, Air, & Soil Pollution, 2023)

Reexamining the Causes and Effects of Cholesterol Deposition in the Brains of Patients with Alzheimer’s Disease - Ze-Lin Hu; Yang-Qi Yuan; Zhen Tong; Mei-Qing Liao; Shun-Ling Yuan; Ye Jian; Jia-Lun Yang; Wen-Feng Liu (Molecular Neurobiology, 2023)

Relationship between night shift and sleep problems, risk of metabolic abnormalities of nurses: a 2 years follow-up retrospective analysis in the National Nurse Health Study (NNHS) - Heli Zhang; Jingpin Wang; Siwei Zhang; Sumei Tong; Jinping Hu; Ying Che; Lin Zhuo; Peng Wang; Rongmei Geng; Yujie Zhou; Panfeng Wang; Siyan Zhan; et al. (International Archives of Occupational and Environmental Health, 2023)
Background and purpose Efforts to improve nurses’ physical and mental health are critical to ensuring the safety and quality of the healthcare system. Long-term studies targeting the relevancy of nurses’ occupation characteristics with health conditions remain insufficient. This study aimed to examine the relationship between nurses’ night shift and sleep problems and metabolic abnormalities risk. Methods This study was a part of the National Nurse Health Study, an ambispective cohort study in China, in 2021. Based on an integration physical examination data system, this study carried out a retrospective analysis of 730 nurses from 2018 to 2020 and combined with a questionnaire survey in 2021. The STROBE guidelines were adopted for reporting. Results In the 23 (23.0, 24.0) months follow-up, higher night shift load was associated with more sleep problems such as shortened sleep duration, sleep disorders, poor sleep quality, and sleep deprivation. Moreover, night shift load was associated with chronic diseases risk factors, increasing body mass index and body fat, with more night shift density, increasing the occurrence of low levels of high-density lipoprotein cholesterol, high triglyceride, triglyceride/high-density lipoprotein cholesterol ratio, and serum uric acid. Conclusion The night shift load has become an occupational health concern, contributing to chronic diseases relevant metabolic risk factors and negative influence on sleep health. Focus on the strategies to improve the sleep quality of nurses undergoing night shift work, optimize work scheduling and ongoing monitor the relevant risk factors are essential to enhance the stability and well-being of the nursing workforce. Clinical Trials registration information: NCT04572347, on October 1, 2020. https://www.clinicaltrials.gov/ct2/show/NCT04572347

Pyroxenite–harzburgite sequences in the Dazhuqu ophiolite (Southern Tibet) formed through hydrous melt infiltration and melt–peridotite reaction - Zhen-Yu Zhang; Chuan-Zhou Liu; Yan Liang; Tong Liu; Chang Zhang; Bo-Da Liu; Yin-Zheng Lin; Wei-Qi Zhang; Wen-Bin Ji (Contributions to Mineralogy and Petrology, 2023)

SIRT3-dependent mitochondrial redox homeostasis mitigates CHK1 inhibition combined with gemcitabine treatment induced cardiotoxicity in hiPSC-CMs and mice - Jia-Wen Chen; Tian-Kai Shan; Tian-Wen Wei; Qi-Qi Jiang; Chong Du; Ling-Feng Gu; Tong-Tong Yang; Liu-Hua Zhou; Si-Bo Wang; Yu-Lin Bao; Hao Wang; Yong Ji; et al. (Archives of Toxicology, 2023)

Enhancing fluoride removal from wastewater using Al/Y amended sludge biochar - Shushu Li; Mingshan Song; Lin Tong; Changqing Ye; Yuhuan Yang; Qingwen Zhou (Environmental Science and Pollution Research, 2023)

Traditional Chinese medicine bufalin inhibits infectious pancreatic necrosis virus genogroups I and V infection in vitro and in vivo - Jing-Zhuang Zhao; Lin-Fang Li; Li-Ming Xu; Yi-Zhi Shao; Guang-Ming Ren; Qi Liu; Tong-Yan Lu (Aquaculture, 2023)

Spatial-temporal clogging development in leachate collection systems of landfills: Insight into chemical and biological clogging characteristics - Qian Wang; Qianming Miao; Ke Huang; Yeqi Lin; Tong Wang; Xinyue Bai; Qiyong Xu (Waste Management, 2023)

Intimately tracking NO2 pollution over the New York City - Long Island Sound land-water continuum: An integration of shipboard, airborne, satellite observations, and models - Maria Tzortziou; Christopher P. Loughner; Daniel L. Goldberg; Laura Judd; Dilchand Nauth; Charlotte F. Kwong; Tong Lin; Alexander Cede; Nader Abuhassan (Science of The Total Environment, 2023)

The iLABdb: a web-based integrated lactic acid bacteria database - Hao Jin; Teng Ma; Lin Chen; Lai-Yu Kwok; Keyu Quan; Yalin Li; Zeng Zhang; Tong Chen; Jiachao Zhang; Zhihong Sun; Heping Zhang (Science Bulletin, 2023)

Seasonal variations in source-sink balance of CO2 in subtropical earthen aquaculture ponds: Implications for carbon emission management - Lele Tang; Linhai Zhang; Ping Yang; Chuan Tong; Hong Yang; Lishan Tan; Yongxin Lin; Derrick Y.F. Lai; Kam W. Tang (Journal of Hydrology, 2023)

Quantification and variation characteristics of baseflow nonpoint source pollution in Yiluo River Basin, China - Jiake Zheng; Rong Gan; Xiaoxia Tong; Lin Guo; Hui Tang; Jie Tao (Journal of Hydrology, 2023)

Slab dehydration and potassium-lithium recycling in the forearc indicated by potassium and lithium isotope compositions of exhumed metabasites - Haiyang Liu; Tinggen Yang; Ying-Yu Xue; Jianghong Deng; Yilin Xiao; He Sun; Fengtai Tong; Kun Wang; Yongjun Gao; Kuan-Yu Lin; Fangyi Zhang; Xin Jin; et al. (Geochimica et Cosmochimica Acta, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

The metabolism of membrane lipid participates in the occurrence of chilling injury in cold-stored banana fruit - Qian Li; Han Lin; He-tong Lin; Meng-shi Lin; Hui Wang; Wei Wei; Jian-ye Chen; Wang-jin Lu; Xing-feng Shao; Zhong-qi Fan (Food Research International, 2023)

Sensory-directed isolation and identification of an intense salicin-like bitter compound in infected teas with bird’s eye spot disease - Jingna Yan; Yiwen Miao; Jingyun Zhou; Rui Huang; Hongwei Dai; Ming Liu; Yunzhi Lin; Yingjuan Chen; Chi-Tang Ho; Huarong Tong; Qing Meng (Food Research International, 2023)

Selenium alleviates lead-induced CIK cells pyroptosis and inflammation through IRAK1/TAK1/IKK pathway - Xiunan Lv; Mengyao Ren; Tong Xu; Meichen Gao; Huanyi Liu; Hongjin Lin (Fish & Shellfish Immunology, 2023)

Chronic cadmium exposure induces Parkinson-like syndrome by eliciting sphingolipid disturbance and neuroinflammation in the midbrain of C57BL/6J mice - Yudong Xu; Huihui Hong; Xiqin Lin; Tong Tong; Jingjing Zhang; Haotian He; Lingling Yang; Gaofeng Mao; Rongrong Hao; Ping Deng; Zhengping Yu; Huifeng Pi; et al. (Environmental Pollution, 2023)

Impacts of autochthonous dissolved organic matter on the accumulation of methylmercury by phytoplankton and zooplankton in a eutrophic coastal ecosystem - Bo Shao; Zhike Li; Zhengyu Wu; Ning Yang; Xiaoyu Cui; Huiming Lin; Yiwen Liu; Wei He; Yingxin Zhao; Xuejun Wang; Yindong Tong (Environmental Pollution, 2023)

Behavior of 3D-printed HPC plates with FRP grid reinforcement under bending - Jun-Jie Zeng; Pei-Lin Li; Zi-Tong Yan; Jie-Kai Zhou; Wai-Meng Quach; Yan Zhuge (Engineering Structures, 2023)

Advances and promotion strategies of membrane-based methods for extracting lithium from brine - Yu-ning Zhang; De-hao Yu; Chen-yu Jia; Li-yue Sun; Ang Tong; Yao Wang; Yan-xin Wang; Lin-jun Huang; Jian-guo Tang (Desalination, 2023)

Insights into the surface Structure-Sensitive photocatalytic oxidation of gaseous toluene on Pd/TiO2 catalysts - Cong Wu; Qinglong Liu; Yu Zhan; Wei Tan; Xiaoqian Wei; Qing Tong; Haiqin Wan; Lin Dong (Chemical Engineering Journal, 2023)

Soil organic nitrogen content and composition in different wetland habitat types along the south-east coast of China - Xiao Lin; Yanli Yang; Ping Yang; Yan Hong; Linhai Zhang; Chuan Tong; Derrick Y.F. Lai; Yongxin Lin; Lishan Tan; Yalan Tian; Kam W. Tang (CATENA, 2023)

Opportunities and challenges for ribosome-inactivating proteins in traditional Chinese medicine plants - Yi-xuan Yang; Xin-yi Wang; Tong Lin; Yu Sun; Yi-cheng Yu; Zhen-hong Zhu (Toxicon, 2023)

The shock of benzalkonium chloride on aerobic granular sludge system and its microbiological mechanism - Yuhao Tong; Peili Lu; Wenyu Zhang; Jun Liu; Yuhai Wang; Lin Quan; Aqiang Ding (Science of The Total Environment, 2023)

Prospects and perspectives on advanced materials for sodium-ion batteries - Zhen-Yi Gu; Xiao-Tong Wang; Yong-Li Heng; Kai-Yang Zhang; Hao-Jie Liang; Jia-Lin Yang; Edison Huixiang Ang; Peng-Fei Wang; Ya You; Fei Du; Xing-Long Wu (Science Bulletin, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

Regulation on copper-tolerance in Citrus sinensis seedlings by boron addition: Insights from root exudates, related metabolism, and gene expression - Huan-Huan Chen; Zhi-Chao Zheng; Wen-Shu Chen; Rong-Yu Rao; Xu-Feng Chen; Xin Ye; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2023)

Efficient activation of persulfate by metallic sulfide mineral for the efficient removal of pesticides: Performance, radical generation and mechanism - Xie Chen; Wen-Xuan Zhang; Zhi-Liang Chen; Xiao-Wen Yao; Man-Li Chen; Lin-Yin Tong; Wei Qian; Peng-Ran Guo; Ling-Jun Kong; Zeng-Hui Diao (Journal of Cleaner Production, 2023)

Fe-MOF-derived carbon compounds as catalysts for trichloroethylene degradation via persulfate oxidation: Role of precursor template and pyrolysis temperature - Jiashu Liu; Lin Zhao; Hongzhi Geng; Bin Wang; Xuejiao Tong; Yihan Li; Daying Chen; Peizhe Sun; Yongkui Yang (Journal of Environmental Chemical Engineering, 2023)

Performance and mechanisms of photocatalysis of silver phosphate modified by carbon nanosheets doped with both nitrogen and boron for removal of norfloxacin - Shehua Tong; Yan Lin; Shuai Zhang; Jinlin Nie; Caiyu Luo; Yupei Zhang; Shaohua Wu; Chunping Yang (Journal of Environmental Chemical Engineering, 2023)

Study on the micro conjugate heat transfer characteristics of coal reconstructed from CT images under the influence of temperature - Yanchi Liu; Baiquan Lin; Ting Liu; Tong Liu; Jiayun Yang (Fuel, 2023)

Insight on the meat quality and carbonylation profile of breast muscle of broilers in response to chronic heat stress: A proteomic research - Yingsen Liu; Zhen Liu; Tong Xing; Jiaolong Li; Lin Zhang; Yun Jiang; Feng Gao (Food Chemistry, 2023)

Effect of different agricultural conditions, practices, and processing on levels of total arsenic and species in cereals and vegetables: A review - Yanfang Liu; Yatao Huang; Lin Li; Yangyang Xiong; Litao Tong; Fengzhong Wang; Bei Fan; Jiashun Gong (Food Control, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

A novel framework to improve the consistency of water quality attribution from natural and anthropogenic factors - Shanlin Tong; Wenpan Li; Jie Chen; Rui Xia; Jingyu Lin; Yan Chen; Chong-Yu Xu (Journal of Environmental Management, 2023)

Novel hydrocortisone magnetic molecularly imprinted polymers: Preparation, characterization, and application - Si-xuan Zhou; Xiao-tong Lin; Jie Wang; Hai-xiang Wang; Gui-tang Chen (Food Chemistry, 2023)

Evodiamine alleviates DEHP-induced hepatocyte pyroptosis, necroptosis and immunosuppression in grass carp through ROS-regulated TLR4 / MyD88 / NF-κB pathway - Yutian Lei; Tong Xu; Wenying Sun; Xiaodan Wang; Meichen Gao; Hongjin Lin (Fish & Shellfish Immunology, 2023)

Lc-pPG-612-OmpU-CTB: A promising oral vaccine for protecting Carassius auratus against Vibrio mimicus infection - Bin-Tong Yang; Tong Zhao; Hong-Jin Li; Zhen-Lin Liang; Wei Cong; Yuan-Huan Kang (Fish & Shellfish Immunology, 2023)

Ultrafast self-assembled supramolecular nanoparticles for enhanced chemodynamic therapy and ferroptosis through lactic acid metabolism regulation - Qi Meng; Jia Tan; Weifang Tong; Changxiao Chen; Zhendong Liu; Sainan Liu; Meifang Wang; Ziyong Cheng; Binbin Ding; Ping'an Ma; Jun Lin (Chemical Engineering Journal, 2023)

A wearable micro air cleaner for occupant-oriented indoor environmental controls - Lingzhe Wang; Sebastian A. Romo; Elaine Sanico; Hevander Da Costa; Tong Lin; Nicholas Rabchevsky; Moritz Kern; Shengwei Zhu; Jelena Srebric (Building and Environment, 2023)

Analysis of Nord Stream explosions using seismic recordings - Yang Shen; Xiao-Lin Hu; Tong-Dong Wang; Wei Zhu; Quan-Shi Guo; Shuo Yang; Qiang Lu; De-Zhi Zhang; Wei-Guo Xiao (Applied Geophysics, 2023)

CNN-based automated trace editing method using Hough transform - Yang Shen; Xiao-lin Hu; Tong-dong Wang; Jia-jia Cui; Si-hao Tao; Ao Li; Qiang Lu; De-zhi Zhang; Wei-guo Xiao (Applied Geophysics, 2023)

Effect of Ca–modified biochar coupling with low–Cd accumulation maize cultivars on remediation of Cd contaminated soils and microbial community composition - Tong Sun; Wenhao Yang; Yingming Xu; Lin Wang; Xuefeng Liang; Qingqing Huang; Yuebing Sun (Soil and Tillage Research, 2023)

Nano-pesticide carrier O-Carboxymethyl chitosan is indigestible in Apis cerana cerana and affects intestinal flora - Sheng-nan Li; Hao Wu; Rui-quan Hou; Jing-tong Zhou; Su-kun Lin; Kun-yu Zhao; Rui-fei Wang; Su-qing Huang; Zhi-xiang Zhang (Science of The Total Environment, 2023)

Anti-apoptotic effect of adrenomedullin gene delivery on Leydig cells by suppressing TGF-β1 via the Hippo signaling pathway - You-wen Luo; Xia-lian Zhu; Ming-yong Li; Jian-hua Zhou; Zhi-min Yang; Tao Tong; Bing-hai Chen; Song-lin Qin; Bo-long Liu; Wei Hu (Reproductive Toxicology, 2023)

Response of sulfur-metabolizing biofilm to external sulfide in element sulfur-based denitrification packed-bed reactor - Hong-Xu Bao; Han-Lin Wang; Shu-Tong Wang; Yi-Lu Sun; Xue-Ning Zhang; Hao-Yi Cheng; Zhi-Min Qian; Ai-Jie Wang (Environmental Research, 2023)

Theoretical study of supported ionic liquid membrane reaction and transport for CO2 cycloaddition reaction - Jian-Fei Sun; Xu-Peng Chen; Xin-Tong Li; Kun-Peng Yu; Qin-Qin Xu; Jin-Tao Wu; Lin Li; Jian-Zhong Yin (Chemical Engineering Journal, 2023)

Hierarchical CoMn-LDH based photothermal membrane with low evaporation enthalpy and narrow bandgap toward highly efficient Solar-Driven evaporation - Ruoxuan Zheng; Tong Lin; Wan-Lei Zhao; Rutao Yin; Hongqiang Li; Zhuoqun Deng; Wei Chen; Yu-Fei Song (Chemical Engineering Journal, 2023)

3D lithiophilic framework fixed on the surface of LLZTO solid electrolyte shaping the contact between Li metal and ceramic - Yuhao Shi; Yifei Cai; Jiaqi Zhao; Tong Wu; Xiaoqian Xue; Tiesong Lin; Panpan Lin; Ce Wang; He Peng (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Distribution Characteristics and Influencing Factors of Bio-elements in the Human Hair of Uyghur Communities in an Oasis Area of Xinjiang, China - Muyesaier Tudi; Fengqing Jiang; Li Wang; Hairong Li; Shuangmei Tong; Jiangping Yu; Min Meng; Lin sheng Yang; Muhammad Ubaid Ali; Qiming Jimmy Yu; Huada Daniel Ruan (Biological Trace Element Research, 2023)

Positive responses and mechanisms of nitrifying sludge to carbon quantum dots: reactor performance, microbial behavior, and antioxidant defense - Lin-Kai Guo; Lei Yang; Shen Cui; Zhao Sun; Xiao-Tong Li; Yu-Chao Wang; Yu-Cai Li; Yong-Xiang Ren (Environmental Science and Pollution Research, 2023)

Transformation and toxicity studies of UV filter diethylamino hydroxybenzoyl hexyl benzoate in the swimming pools - Panduo Shan; Jiayi Lin; Yanbo Zhai; Shuai Dong; Zuo Tong How; Rui Qin (Science of The Total Environment, 2023)

Using quantum chemistry theory to elucidate the mechanism for treating sulfonamide antibiotic wastewater by progressive freezing - Zhang Yan; Liu Tong-shuai; Wang Xiao-zhuang; Liu Yu-can; Zhao Chen; Lin Hao; Zou Yi-hong (Journal of Water Process Engineering, 2023)

Effect of acidification on microscopic properties and pore structure of coal - Zha Wei; Lin Baiquan; Liu Tong; Liu Ting; Yang Wei (Fuel, 2023)

Exploring in vitro gastrointestinal digestion of myofibrillar proteins at different heating temperatures - Hua Chen; Gaiming Zhao; Xiaoling Yu; Qiuhui Zhang; Chaozhi Zhu; Lin Tong; Jiangang Hao (Food Chemistry, 2023)

Potential causal links between long-term ambient particulate matter exposure and cerebrovascular mortality: Insights from a large cohort in southern China - Shirui Chen; Xiao Lin; Zhicheng Du; Yuqin Zhang; Lingling Zheng; Xu Ju; Tong Guo; Xinran Wang; Lichang Chen; Jie Jiang; Weihua Hu; Wangjian Zhang; et al. (Environmental Pollution, 2023)

Uncovering the role of renewable energy innovation in China's low carbon transition: Evidence from total-factor carbon productivity - Tong Su; Yufang Chen; Boqiang Lin (Environmental Impact Assessment Review, 2023)

A green synthesized medicine residue carbon-based iron composite for the removal of chromium (VI) and cadmium (II): Performance, kinetics and mechanism - Fa-Ming Diao; Man-Li Chen; Lin-Yin Tong; Ying-Nan Chen; Zeng-Hui Diao (Environmental Science and Pollution Research, 2023)

Peroxymonosulfate and peroxydisulfate activation by fish scales biochar for antibiotics removal: Synergism of N, P-codoped biochar - Qingyun He; Chenhui Zhao; Lin Tang; Zhifeng Liu; Binbin Shao; Qinghua Liang; Ting Wu; Yuan Pan; Jiajia Wang; Yang Liu; Shehua Tong; Tianjue Hu (Chemosphere, 2023)

“Restorative-Repressive” perception on post-industrial parks based on artificial and natural scenarios: Difference and mediating effect - Fang Wei; Chuli Huang; Xuqing Cao; Shuhan Zhao; Tong Xia; Yijing Lin; Qisheng Han (Urban Forestry & Urban Greening, 2023)

Semi-analytical solutions of three-dimensional ground movements due to shallow tunnelling - Lin Yu; Dingli Zhang; Qian Fang; Tong Xu; Jiwei Luo; Wenbo Chen (Tunnelling and Underground Space Technology, 2023)

Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L. - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2023)

Crustal accretion in a slow-spreading center of Meso-Tethyan Ocean: Constraints from cumulates in the Dongco ophiolite (Central Tibet) - Xiao-Ni Li; Wei-Qi Zhang; Tong Liu; Chang Zhang; Zhen Zhang; Yin-Zheng Lin; Chuan-Zhou Liu (Lithos, 2023)

Synergistic action of ferrate and biochar in the removal of trichloroethylene from water: Little biochar addition, large ferrate activity improvement - Yongkui Yang; Xiaoke Ma; Shaoyi Zhang; Xiao Luo; Hongzhi Geng; Jiashu Liu; Xuejiao Tong; Youjun Zhang; Peizhe Sun; Lin Zhao (Journal of Environmental Chemical Engineering, 2023)

Cues of intraguild predators (Harmonia axyridis) and different temperatures alter foraging and oviposition strategies of the parasitoid Aphidius gifuensis - Xing-Lin Yu; Yi Feng; Tong-Xian Liu; Bao-Li Qiu (Journal of Asia-Pacific Entomology, 2023)

Investigation of additive-assisted microbial-induced calcium carbonate precipitation in 3D printed cross fractures - Liang Guo; Min Zhang; Mingwei Liao; Baoquan Wang; Xiaoyu He; Yiqi Peng; Xingzhu Lin; Ni He; Zhuhong Xiong; Han Chen; Yehui Shi; Tong Li (Geomechanics for Energy and the Environment, 2023)

Synergistic effects of combined treatment of 1,2-dichloroethane and high-dose ethanol on liver damage in mice and the related mechanisms - Jinhan Yang; Lin Zhang; Tong Wang; Jiajia Zhang; Mingyue Li; Xiaoxia Jin; Xiaoqiong Tan; Gaoyang Wang; Fenghong Zhao; Yaping Jin (Food and Chemical Toxicology, 2023)

Effects of landscape modification on coastal sediment nitrogen availability, microbial functional gene abundances and N2O production potential across the tropical-subtropical gradient - Ping Yang; Kam W. Tang; Linhai Zhang; Xiao Lin; Hong Yang; Chuan Tong; Yan Hong; Lishan Tan; Derrick Y.F. Lai; Yalan Tian; Wanyi Zhu; Manjing Ruan; et al. (Environmental Research, 2023)

Coaxial electrospun nanofibrous substrates with tunable wettability for constructing cucurbit[n]uril-embedded organic solvent nanofiltration membranes - Qian Wang; Qin-Yuan He; Liu-Lin Zhao; Yue Wang; Rong Fang; Cong Luo; Wei-Tong Lu; Hong-Ya Jiang; Shi-Peng Sun; Xue-Li Cao (Chemical Engineering Journal, 2023)

Projected land use changes in the Qinghai-Tibet Plateau at the carbon peak and carbon neutrality targets - Runhong Xu; Peijun Shi; Miaoni Gao; Yanjun Wang; Guojie Wang; Buda Su; Jinlong Huang; Qigen Lin; Tong Jiang (Science China Earth Sciences, 2023)

Legacy effect of plant chemical defence substances on litter decomposition - Yunchao Luo; Lin Wang; Tingting Cao; Weihua He; Shangxian Lu; Fei Li; Zhenwei Zhang; Tong Chang; Xingjun Tian (Plant and Soil, 2023)

Dimethyl Itaconate Reduces Cognitive Impairment and Neuroinflammation in APPswe/PS1ΔE9 Transgenic Mouse Model of Alzheimer’s Disease - Jing Xiong; Dong-Lin Lu; Bai-Qiang Chen; Tong-Yun Liu; Zi-Xuan Wang (NeuroMolecular Medicine, 2023)

Short- and medium-chain chlorinated paraffins in urban road dust of Shanghai, China: concentrations, source apportionment and human exposure assessment - Xue-Tong Wang; Cheng-Lin Wang; Ying Zhou; Guo-Fa Ren; Rui Fu; Jing An (Environmental Geochemistry and Health, 2023)

Sialylation of cell surface glycoconjugates modulates cytosolic galectin-mediated responses upon organelle damage - I-Chun Weng; Hung-Lin Chen; Wei-Han Lin; Fu-Tong Liu (Glycoconjugate Journal, 2023)

Effect of Tyrosol Acyl Esters on the Antioxidant Status of Mussel ( Mytilus edulis ) Oil During Accelerated Oxidative Storage - Qian Wang; Mo-Tong Zhang; Xin-Miao Wang; Guan-Hua Zhao; Yuan-Yuan Hu; Fa-Wen Yin; Hui-Lin Liu; Xiao-Yang Liu; Da-Yong Zhou (Journal of Aquatic Food Product Technology, 2023)

Rice OsHsp16.9A interacts with OsHsp101 to confer thermotolerance - Yi-Hsin Liu; Tong-Seung Tseng; Ching-Rong Wu; Shu-Ting Cho; Chih-Horng Kuo; Xin-Jie Huang; Jung-Yi Cheng; Kuo-Hsuan Hsu; Kung-Fu Lin; Chia-Chin Liu; Ching-Hui Yeh (Plant Science, 2023)

Ceria-Promoted and stabilized copper and iron oxides cooperatively catalyze NO efficient degradation by CO - Xiaobing Shi; Lin Tao; Zhangfa Tong; Minguang Fan; Lihui Dong; Bin Li (Fuel, 2023)

Synergistic analysis of performance, functional genes, and microbial community assembly in SNDPR process under Zn(II) stress - Tong Wu; Jie Ding; Le Zhong; Yi-Lin Zhao; Han-Jun Sun; Ji-Wei Pang; Lei Zhao; Shun-Wen Bai; Nan-Qi Ren; Shan-Shan Yang (Environmental Research, 2023)

Responses of coastal sediment organic and inorganic carbon to habitat modification across a wide latitudinal range in southeastern China - Yan Hong; Linhai Zhang; Ping Yang; Chuan Tong; Yongxin Lin; Derrick Y. F. Lai; Hong Yang; Yalian Tian; Wanyi Zhu; Kam W. Tang (CATENA, 2023)

Overview of the main biological mechanisms linked to changes in periodontal ligament stem cells and the inflammatory microenvironment - Xuetao Zhao; Hongbing Lin; Tong Ding; Yawei Wang; Na Liu; Yuqin Shen (Journal of Zhejiang University-SCIENCE B, 2023)

Triclosan and triclocarban weaken the olfactory capacity of goldfish by constraining odorant recognition, disrupting olfactory signal transduction, and disturbing olfactory information processing - Lin Huang; Weixia Zhang; Difei Tong; Lingzheng Lu; Weishang Zhou; Dandan Tian; Guangxu Liu; Wei Shi (Water Research, 2023)

The ginsenoside Rh2 protects porcine oocytes against aging and oxidative stress by regulating SIRT1 expression and mitochondrial activity - Hongye Liu; Zhi-Yong An; Zhou-Yan Li; Liu-Hui Yang; Xiu-Li Zhang; Yan-Tong Lv; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2023)

What are the individual and joint impacts of key meteorological factors on the risk of unintentional injuries? A case-crossover study of over 147,800 cases from a sentinel-based surveillance system - Xiao Lin; Tian Tian; Congxing Shi; Pengyu Wang; Shimin Chen; Tong Guo; Zhiqiang Li; Boheng Liang; Wangjian Zhang; Pengzhe Qin; Yuantao Hao (Sustainable Cities and Society, 2023)

Sulfide- and UV-induced aging differentially affect contaminant-binding properties of microplastics derived from commercial plastic products - Lin Duan; Yiyuan Qin; Xin Meng; Yaqi Liu; Tong Zhang; Wei Chen (Science of The Total Environment, 2023)

Responses of microbial community to geochemical parameters on vertical depth in bioheap system of low-grade copper sulfide - Xiu-Tong Li; Zhong-Sheng Huang; Ye Huang; Zhen Jiang; Zong-Lin Liang; Hua-Qun Yin; Guang-Ji Zhang; Yan Jia; Ye Deng; Shuang-Jiang Liu; Cheng-Ying Jiang (Science of The Total Environment, 2023)

Optimizing the parameters of microbial fuel cells using response surface methodology to increase Cr(VI) removal efficiency and power production - Chi-Wen Lin; Yi-Pei Chung; Shu-Hui Liu; Wei Tong Chen; Ting-Jun Zhu (Process Safety and Environmental Protection, 2023)

Involvement of microRNA164 in responses to heat stress in Arabidopsis - Wei-An Tsai; Po-Han Sung; Yun-Wei Kuo; Ming-Cheng Chen; Shih-Tong Jeng; Jeng-Shane Lin (Plant Science, 2023)

Fabrication of polyamide thin film nanocomposite membranes with enhanced desalination performance modified by silica nanoparticles formed in-situ polymerization of tetramethoxysilane - Yunbo Tong; Yulin Wei; Han Zhang; Lin Wang; Lingling Li; Fangkun Xiao; Congjie Gao; Guiru Zhu (Journal of Environmental Chemical Engineering, 2023)

Recent progress on highly efficient removal of heavy metals by layered double hydroxides - Tong He; Qian Li; Tong Lin; Jiaxin Li; Sha Bai; Sai An; Xianggui Kong; Yu-Fei Song (Chemical Engineering Journal, 2023)

Late diagenetic alteration of carbonate evidenced by carbonate-deficient siliciclastic laminae - Xubin Wang; Lin Dong; Tong Li; Ziyi Wang; Changhu Zhang; Zhijun Jin; Jinhua Fu; Rukai Zhu; Kun Ling; Tianyu Wang (Chemical Geology, 2023)

Lipopolysaccharide-induced endotoxaemia during adolescence promotes stress vulnerability in adult mice via deregulation of nuclear factor erythroid 2-related factor 2 in the medial prefrontal cortex - Yan-chen Chen; Yan-hua Huang; Li Song; Xiao-han Tong; Jun-feng Li; Song Lin; Xi Chen; Ji-chun Zhang; Zi-li Zhang; Qi-yi Zeng (Psychopharmacology, 2023)

Preliminary identification of soil fungi for the degradation of polyurethane film - Kong-Yang Wu; Tong-Xiang Yang; Meng Yang; Jin-Qiu Wu; Xue Li; Xue-Dong Chen; Lin Tang; Xue-Yi Yang (Archives of Microbiology, 2023)

The ecotoxicological effects of chromium (III) oxide nanoparticles to Chlorella sp.: perspective from the physiological and transcriptional responses - Huan-Huan Liu; Lei Yang; Xiao-Tong Li; Hui Shi; Lin-Kai Guo; Li-Xin Tu; Jia Wang; Yan-Li Li (Environmental Science and Pollution Research, 2023)

A Hybrid–Source Ranging Method in Shallow Water Using Modal Dispersion Based on Deep Learning - Tong Wang; Lin Su; Qunyan Ren; He Li; Yuqing Jia; Li Ma (Journal of Marine Science and Engineering, 2023)
The relationship between modal elevation angle and the relative arrival time between modes, derived from exploiting modal dispersion, provides source information that is less susceptible to environmental influences. However, the standard method based on modal dispersion has limitations for application. To overcome this, we propose a hybrid method for passive source ranging of low-frequency underwater acoustic-pulse signals in a range-independent shallow-water waveguide. Our method leverages deep learning, utilizing the intermediate results from the standard method as inputs, and short-time conventional beamforming to transform signals received by a vertical line array into a beam-time-domain sound-intensity map. The source range is estimated using an attention-based regression model with a ResNet backbone that has been trained on the beam-time-domain sound-intensity map. Our experimental results demonstrate the superiority of the proposed method, with a mean relative-error reduction of 71%, mean root-squared error reduction of 2.25 km, and an accuracy of 85%, compared to matched-field processing.

Novel biofortification candidate: MTP1 increases microelement contents and decreases toxic heavy metal accumulation in grains - Mingyue Tong; Xiang Liu; Jing Guan; Yuanyuan Lin; Aimin Zhou; Kun Qiao (Chemosphere, 2023)

Biodegradation of polylactic acid by a mesophilic bacteria Bacillus safensis - Yujun Wang; Ting Hu; Wanting Zhang; Jinwei Lin; Zhanyong Wang; Shuxia Lyu; Haibin Tong (Chemosphere, 2023)

Citrate-promoted dissolution of nanostructured manganese oxides: Implications for nano-enabled sustainable agriculture - Di Fu; Lin Duan; Xiaoyan Li; Chuanjia Jiang; Tong Zhang; Wei Chen (Journal of Environmental Sciences, 2023)

A portable paper-based aptasensor for simultaneous visual detection of two mycotoxins in corn flour using dual-color upconversion nanoparticles and Cu-TCPP nanosheets - Xianfeng Lin; Changxin Li; Xinyu Tong; Nuo Duan; Zhouping Wang; Shijia Wu (Food Chemistry, 2023)

Effects of mannoprotein on the stability and in vitro digestion of cyanidin-3-glucoside - Meizhi Wan; Sixu Lin; Chang Tan; Mingyue Wang; Yuqi Tong; Yang Zhao; Yanwen Kong; Haotian Deng; Xianjun Meng; Yan Ma (Food Chemistry, 2023)

Comparison of tropomyosin released peptide and epitope mapping after in vitro digestion from fish (Larimichthys crocea), shrimp (Litopenaeus vannamei) and clam (Ruditapes philippinarum) through SWATH-MS based proteomics - LiLi Xu; Xiao Mei Zhang; Yun Qi Wen; Jin Long Zhao; Tong Cheng Xu; Ling Yong; Hong Lin; Hong Wei Zhang; Zhen Xing Li (Food Chemistry, 2023)

Emulsifying properties and oil–water interface properties of succinylated soy protein isolate: Affected by conformational flexibility of the interfacial protein - Ziteng Lian; Sai Yang; Lin Cheng; Peilong Liao; Shicheng Dai; Xiaohong Tong; Tian Tian; Huan Wang; Lianzhou Jiang (Food Hydrocolloids, 2023)

Effective removal of Hg2+ and Cd2+ in aqueous systems by Fe–Mn oxide modified biochar: A combined experimental and DFT calculation - Tong Sun; Yuebing Sun; Yingming Xu; Lin Wang; Xuefeng Liang (Desalination, 2023)

Fouling characteristic of reverse osmosis membrane for reclaimed water treatment operating under cold winter condition - Zi-Hao Li; Guo-Wei Ni; Jin-Long Wang; Lin Zhou; Qiang Yang; Pei-Zhuo Li; Ai-Li Gao; Tong Yu; Li-Hua Cheng; Xue-Jun Bi (Desalination, 2023)

Rising temperatures affect the interspecific interference competition between Harmonia axyridis and Propylea japonica, and their predation rate on Myzus persicae - Xing-Lin Yu; Yu-Jie Zhang; Jun-Feng Zuo; Xun Luo; Long Zhang; Zhuo-Ma Danzeng; Bo Wang; Peng-Liang Xia; Shi-Ze Zhang; Tong-Xian Liu; Yi Feng (Journal of Pest Science, 2023)

New remains of Ailuropoda melanoleuca baconi from Yanjinggou, China: Throwing light on the evolution of giant pandas during the Pleistocene - Haiqian Hu; Haowen Tong; Qingfeng Shao; Guangbiao Wei; Haidong Yu; Jingsong Shi; Xunqian Wang; Can Xiong; Yu Lin; Ning Li; Zhaoying Wei; Ping Wang; et al. (Journal of Mammalian Evolution, 2023)

Water infiltration and soil-water characteristics of compacted loess under applied vertical stress - Lin Zhang; Tong-lu Li; Ji-heng Li; Wei Liang; Cun-li Chen (Journal of Mountain Science, 2023)

Rapid shifts in thermal reaction norms and tolerance of brooded coral larvae following parental heat acclimation - Lei Jiang; Cheng‐Yue Liu; Guoxin Cui; Lin‐Tao Huang; Xiao‐Lei Yu; You‐Fang Sun; Hao‐Ya Tong; Guo‐Wei Zhou; Xiang‐Cheng Yuan; Yi‐Si Hu; Wen‐Liang Zhou; Manuel Aranda; et al. (Molecular Ecology, 2023)
Thermal priming of reef corals can enhance their heat tolerance; however, the legacy effects of heat stress during parental brooding on larval resilience remain understudied. This study investigated whether preconditioning adult coral Pocillopora damicornis to high temperatures (29°C and 32°C) could better prepare their larvae for heat stress. Results showed that heat‐acclimated adults brooded larvae with reduced symbiont density and shifted thermal performance curves. Reciprocal transplant experiments demonstrated higher bleaching resistance and better photosynthetic and autotrophic performance in heat‐exposed larvae from acclimated adults compared to unacclimated adults. RNA‐seq revealed strong cellular stress responses in larvae from heat‐acclimated adults that could have been effective in rescuing host cells from stress, as evidenced by the widespread upregulation of genes involved in cell cycle and mitosis. For symbionts, a molecular coordination between light harvesting, photoprotection and carbon fixation was detected in larvae from heat‐acclimated adults, which may help optimize photosynthetic activity and yield under high temperature. Furthermore, heat acclimation led to opposing regulations of symbiont catabolic and anabolic pathways and favoured nutrient translocation to the host and thus a functional symbiosis. Notwithstanding, the improved heat tolerance was paralleled by reduced light‐enhanced dark respiration, indicating metabolic depression for energy saving. Our findings suggest that adult heat acclimation can rapidly shift thermal tolerance of brooded coral larvae and provide integrated physiological and molecular evidence for this adaptive plasticity, which could increase climate resilience. However, the metabolic depression may be maladaptive for long‐term organismal performance, highlighting the importance of curbing carbon emissions to better protect corals.

Normal Operating Performance Study of 15 MW Floating Wind Turbine System Using Semisubmersible Taida Floating Platform in Hsinchu Offshore Area - Hoi-Yi Tong; Tsung-Yueh Lin; Shiu-Wu Chau (Journal of Marine Science and Engineering, 2023)
This study predicted the motion response and power performance of a floating wind turbine system equipped with a semisubmersible Taida platform, an IEA 15 MW wind turbine, and a 3 × 2 mooring design in the Hsinchu offshore area in the Taiwan Strait. The hydrodynamic properties were calculated using ANSYS-AQWA and STAR-CCM+. The motion equations were solved by OrcaFlex to obtain the motion response and generator power, as well as the dynamics of the mooring system and aerodynamics of the wind turbine. The waves were assumed to share the same direction as the wind. This study compared the mean values and standard deviations of the motion response, generator power, and mooring line tension between the potential- and viscous-flow approaches by considering the combination of seven wind directions and four current directions under two wave conditions in the Hsinchu offshore area. The numerical prediction shows that the viscous effect has a larger impact on the hydrodynamic properties in the heave, roll, and pitch motions. The angle between the leading mooring line of the system and dominant wind direction in the Taiwan Strait, which comes from the northeast, should be from 120° to 180° in order to deliver a relatively favorable performance of the system.

The effect of short-term air pollutants exposure on outpatient admission for blepharitis in Shanghai, China: a hospital-based study - Han Zhao; Tong Lin; Yun Yang; Changming Feng; Wushuang Wang; Lan Gong (Environmental Science and Pollution Research, 2023)

Identification of SNPs and candidate genes associated with early growth in orange-spotted grouper (Epinephelus coioides) by a genome-wide association study - Chun Hui Ai; Zong Xian Zhu; Dan Dan Huang; Gan Yang; Tong De Liu; Ying Bai; Xue Ying Liang; Ying Ying Xiong; Yi Long Lin; Hao Ran Lin; Shui Sheng Li; Jun Hong Xia (Aquaculture, 2023)

A rapid, high-throughput, and sensitive PEG-precipitation method for SARS-CoV-2 wastewater surveillance - Xiawan Zheng; Mengying Wang; Yu Deng; Xiaoqing Xu; Danxi Lin; Yulin Zhang; Shuxian Li; Jiahui Ding; Xianghui Shi; Chung In Yau; Leo L.M. Poon; Tong Zhang (Water Research, 2023)

Suppression on PCDD/Fs formation by a novel inhibition system consisting of phosphorous-based compounds coupled with a chlorine-deactivation material - Tong Chen; Weican Xiang; Angjian Wu; Xiaoqing Lin; Zhiliang Chen; Xiaodong Li; Jianhua Yan (Waste Management, 2023)

Two new pentasaccharide resin glycosides from Argyreia acuta - Yi-Lin Niu; Zhi-Tong Li; Yong-Qin Yin (Phytochemistry Letters, 2023)

Bibliometric overview of research progress, challenges, and prospects of rural domestic sewage: Treatment techniques, resource recovery, and ecological risk - Le Zhong; Jie Ding; Tong Wu; Yi-lin Zhao; Ji Wei Pang; Ji-Ping Jiang; Jun-Qiu Jiang; Yan Li; Nan-Qi Ren; Shan-Shan Yang (Journal of Water Process Engineering, 2023)

Experimental study on the influence of gas pressure on CH4 adsorption-desorption-seepage and deformation characteristics of coal in the whole process under triaxial stress - Haifei Lin; Pengfei Ji; Xiangguo Kong; Shugang Li; Hang Long; Tong Xiao; Bai Li (Fuel, 2023)

CH4 adsorption and diffusion characteristics in stress-loaded coal based on molecular simulation - Hai-fei Lin; Hang Long; Shu-gang Li; Yang Bai; Tong Xiao; Ao-li Qin (Fuel, 2023)

Soy protein isolate-catechin non-covalent and covalent complexes: Focus on structure, aggregation, stability and in vitro digestion characteristics - Shicheng Dai; Peilong Liao; Yilun Wang; Tian Tian; Xiaohong Tong; Bo Lyu; Lin Cheng; Liming Miao; Weijie Qi; Lianzhou Jiang; Huan Wang (Food Hydrocolloids, 2023)

Subassemblage tests on seismic behavior of double-corrugated-plate shear walls - Jing-Zhong Tong; Ruo-Min Wu; Zhao-Yu Xu; Yan-Lin Guo (Engineering Structures, 2023)

Cobalt single atom anchored on N-doped carbon nanoboxes as typical single-atom catalysts (SACs) for boosting the overall water splitting - Tong Li; Siyuan Ren; Cheng Zhang; Lingxia Qiao; Jiang Wu; Ping He; Jia Lin; Yongsheng Liu; Zaiguo Fu; Qunzhi Zhu; Weiguo Pan; Baofeng Wang; et al. (Chemical Engineering Journal, 2023)

Experimental study on 3D source localization in indoor environments with weak airflow based on two bionic swarm intelligence algorithms - Axiang Chen; Yu Liao; Hao Cai; Xun Guo; Boyuan Zhang; Bencheng Lin; Wei Zhang; Ling Wei; Yan Tong (Building and Environment, 2023)

Compound Probiotic Ameliorates Acute Alcoholic Liver Disease in Mice by Modulating Gut Microbiota and Maintaining Intestinal Barrier - Haixia Liu; Xing Kang; Xiaodan Yang; Hao Yang; Xiaoyu Kuang; Peng Ren; Huan Yan; Xiaorong Shen; Yongbo Kang; Lin Li; Xiaohui Wang; Linzhi Guo; et al. (Probiotics and Antimicrobial Proteins, 2023)

Transcriptome and DNA Methylation Responses in the Liver of Yellowfin Seabream Under Starvation Stress - Yi Long Lin; Zong Xian Zhu; Chun Hui Ai; Ying Ying Xiong; Tong De Liu; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2023)

Palladium nanoparticles supported on LDH: A highly efficient and recyclable heterogeneous catalyst for the Heck reaction - Hao Sun; Chenzhe Xu; Xiaoting Yang; Lei Tao; Zheng Wang; Haitao Zhang; Xiang Ji; Juanjuan Ma; Lin Liu; Zhiwei Tong; Zhong Chen (Applied Clay Science, 2023)

A fluorescent probe based on a phenylalanine derivative is capable of sequential detection of Zn2+ and Cys/His - Qiu-Yu Yu; Chuan-Wan Wei; Xiao-Juan Wang; Shu-Qin Gao; Xin-Yi Tong; Ying-Wu Lin (JBIC Journal of Biological Inorganic Chemistry, 2023)

Combined effects of prenatal phthalate exposure on cardiometabolic risk score among 4- to 7-year-old children: MABC study - Hui Gao; Meng-long Geng; Juan Tong; Bao-lin Wang; Kun Huang; Yi Zhang; Hong Gan; Bei-bei Zhu; Peng Ding; Qu-nan Wang; Jian-qing Wang; Cheng Zhang; et al. (Chemosphere, 2023)

Corrigendum to “Prenatal exposure to perfluoroalkyl and polyfluoroalkyl substances and birth outcomes: A longitudinal cohort with repeated measurements” [Chemosphere volume 267 (2021) /128899] - Lin Chen; Chuanliang Tong; Xiaona Huo; Jun Zhang; Ying Tian (Chemosphere, 2023)

The occurrence, speciation, and ecological effect of plastic pollution in the bay ecosystems - Yifan Tong; Lin Lin; Yi Tao; Yuxiong Huang; Xiaoshan Zhu (Science of The Total Environment, 2023)

ZIF-8-derived Cu, N co-doped carbon as a bifunctional cathode catalyst for enhanced performance of microbial fuel cell - Bi-Lin Lai; Hui-Xu Wei; Zi-Nuo Luo; Tong Zheng; Yi-Hui Lin; Zhao-Qing Liu; Nan Li (Science of The Total Environment, 2023)

The association between wind speed and the risk of injuries among preschool children: New insight from a sentinel-surveillance-based study - Congxing Shi; Xiao Lin; Tingyuan Huang; Kai Zhang; Yanan Liu; Tian Tian; Pengyu Wang; Shimin Chen; Tong Guo; Zhiqiang Li; Boheng Liang; Pengzhe Qin; et al. (Science of The Total Environment, 2023)

Evaluation of eight psychoactive drugs used in Chinese cities by wastewater-based epidemiology - Xue-Ting Shao; Si-Yu Liu; Yue-Tong Zhao; Bing Jiang; Jian-Guo Lin; De-Gao Wang (Science of The Total Environment, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Rational design of ordered porous nanoparticles for selective extraction of nitrobenzene compounds - Sheng Peng; Minhui Shen; Xiang Li; Yuan-Jun Tong; Jing Guo; Wei Lin; Yu-Xin Ye; Jianqiao Xu; Ningbo Zhou; Fang Zhu; Gangfeng Ouyang (Journal of Hazardous Materials, 2023)

Can hot water injection with chemical additives be an alternative to steam injection: Static and dynamic experimental evidence - Xuan Du; Tong Liu; Changfeng Xi; Bojun Wang; Zongyao Qi; You Zhou; Jiacheng Xu; Lixing Lin; Georgeta Istratescu; Tayfun Babadagli; Huazhou Andy Li (Fuel, 2023)

Atmospheric chemistry of nitrous acid and its effects on hydroxyl radical and ozone at the urban area of Beijing in early spring 2021 - Wenqian Zhang; Shengrui Tong; Deng Lin; Fangjie Li; Xinran Zhang; Lili Wang; Dongsheng Ji; Guiqian Tang; Zirui Liu; Bo Hu; Maofa Ge (Environmental Pollution, 2023)

N-type small molecule electron transport materials with D-A-D conjugated core for non-fullerene organic solar cells - Dan Zhou; Yubing Li; Hehui Zhang; Haolan Zheng; Xingxing Shen; Wen You; Lin Hu; Liangjing Han; Yongfen Tong; Lie Chen (Chemical Engineering Journal, 2023)

One-step fabrication of self-healing poly(thioctic acid) coatings on ZE21B Mg alloys for enhancing corrosion resistance, anti-bacterial/oxidation, hemocompatibility and promoting re-endothelialization - Zhao-Qi Zhang; Pei-Duo Tong; Li Wang; Zheng-Hui Qiu; Jing-An Li; Hang Li; Shao-Kang Guan; Cun-Guo Lin; Hong-Yan Wang (Chemical Engineering Journal, 2023)

CFD simulations of effects of recirculation mode and fresh air mode on vehicle cabin indoor air quality - Tong-Bou Chang; Yu-Sheng Lin; Yi-Tian Hsu (Atmospheric Environment, 2023)

An automated, fully-integrated nucleic acid analyzer based on microfluidic liquid handling robot technique - Tong-Tong Lin; Jian-Wei Wang; Qian-Nuan Shi; Hui-Feng Wang; Jian-Zhang Pan; Qun Fang (Analytica Chimica Acta, 2023)

Diffusive nitrous oxide (N2O) fluxes across the sediment-water-atmosphere interfaces in aquaculture shrimp ponds in a subtropical estuary: Implications for climate warming - Yalan Tian; Ping Yang; Hong Yang; Huimin Wang; Linhai Zhang; Chuan Tong; Derrick Y.F. Lai; Yongxin Lin; Lishan Tan; Yan Hong; Chen Tang; Kam W. Tang (Agriculture, Ecosystems & Environment, 2023)

Testing machine learning algorithms on a binary classification phenological model - Wujun Dai; Huiying Jin; Lin Zhou; Tong Liu; Yuhong Zhang; Zhiqiang Zhou; Yongshuo H. Fu; Guangze Jin (Global Ecology and Biogeography, 2023)
Aim Phenological models have become a vital tool for predicting future phenological responses to global climate change. Recently, machine learning (ML) has been used successfully to develop phenological models based on ground observations. However, fitting an observation series that has been observed for only a few years (or even a decade) can easily lead to overfitting, and it is still a great challenge to predict future phenology accurately based on a short observation series. Here, based on historical ground phenological observations, we construct an ML‐based binary classification phenological model that can be applied to temperate trees. Innovation We thoroughly describe the construction process of a species‐specific ML‐based binary classification phenological model that is suitable for phenological predictions in both spring and autumn. Through experiments, we evaluate 18 commonly used ML classification algorithms and the effects of two parameters on the prediction performance of the model. Finally, we compare the performance between the binary classification model and six widely used ecophysiological models for accuracy of spring phenological prediction. Main conclusions The median root mean square error (RMSE) of the binary classification model for the first flowering date (93 observation series) was only 2.99 days, which proves that it is a good method of phenological prediction for temperate trees. This model can effectively overcome the insufficient sample size of ground observations for specific species and provide new insights of phenological predictions for tropical and subtropical trees. The comparison of different ML algorithms showed that the median root mean square errors of the six algorithms were 3.7 days) in prediction of spring phenology. In addition, this model can help us to infer plant physiological mechanisms and drivers of phenological change and provide more accurate predictions of plant phenological responses to climate change.

Golden 2-like transcription factor contributes to the major QTL against rice black-streaked dwarf virus disease - Xuejuan Li; Feng Lin; Chenyang Li; Linlin Du; Zhiyang Liu; Wenjuan Shi; Jianying Lv; Xiaoyan Cao; Ying Lan; Yongjian Fan; Yijun Zhou; Tong Zhou (Theoretical and Applied Genetics, 2022)

Knowledge domain and hotspot trends in coal and gas outburst: a scientometric review based on CiteSpace analysis - Chao Xu; Tong Yang; Kai Wang; Lin Guo; Xiaomin Li (Environmental Science and Pollution Research, 2022)

The nutrient removal and tolerance mechanism of a heterotrophic nitrifying bacterium Pseudomonas putida strain NP5 under metal oxide nanoparticles stress - Huan-Huan Liu; Lei Yang; Lin-Kai Guo; Li-Xin Tu; Xiao-Tong Li; Jia Wang; Yong-Xiang Ren (Environmental Science and Pollution Research, 2022)

The Influence of the Rotary Speed of a Microwave Applicator on Hard-Rock Fracturing Effect - Xia-ting Feng; Shi-ping Li; Cheng-xiang Yang; Feng Lin; Tian-yang Tong; Xiang-xin Su; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2022)

Detection of the role of intestinal flora and tryptophan metabolism involved in antidepressant-like actions of crocetin based on a multi-omics approach - Susu Lin; Qiaoqiao Li; Zijin Xu; Ziwei Chen; Yi Tao; Yingpeng Tong; Ting Wang; Suhong Chen; Ping Wang (Psychopharmacology, 2022)

Multi-stage melt impregnation and magma–seawater interaction in a slow-spreading oceanic lithosphere: constraints from cumulates in the Lagkorco ophiolite (central Tibet) - Wei-Qi Zhang; Chuan-Zhou Liu; Tong Liu; Chang Zhang; Zhen-Yu Zhang; Xiao-Ni Li; Zhen Zhang; Yin-Zheng Lin (Contributions to Mineralogy and Petrology, 2022)

Genome sequence of the novel freshwater Microcystis cyanophage Mwe-Yong1112-1 - Ruqian Cai; Dengfeng Li; Wei Lin; Weinan Qin; Lingting Pan; Fei Wang; Minhua Qian; Wencai Liu; Qin Zhou; Chengxu Zhou; Yigang Tong (Archives of Virology, 2022)

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

A multi-modal brain–computer interface based on threshold discrimination and its application in wheelchair control - Enzeng Dong; Haoran Zhang; Lin Zhu; Shengzhi Du; Jigang Tong (Cognitive Neurodynamics, 2022)

Genomic analysis of a novel active prophage of Hafnia paralvei - Lingting Pan; Dengfeng Li; Wei Lin; Wencai Liu; Weinan Qin; Lihua Xu; Yigang Tong (Archives of Virology, 2022)

Gregarious larval settlement mediates the responses of new recruits of the reef coral Acropora austera to ocean warming and acidification - Lei Jiang; Yu-Yang Zhang; Cheng-Yue Liu; Lin-Tao Huang; Hao-Ya Tong; Guo-Wei Zhou; Ming-Lan Guo; Tao Yuan; Hui Huang (Frontiers in Marine Science, 2022)
Gregarious larval settlement represents an important window for chimera formation in reef corals, yet it remains largely unknown how aggregated settlement and early chimerism could modify the performance and responses of coral recruits under elevated temperature and p CO 2 . In this study, single and aggregated recruits of the broadcast spawning coral Acropora austera were exposed to contrasts of two temperatures (28 versus 30.5°C) and p CO 2 levels (~500 versus 1000 μatm) for two weeks, and algal symbiont infection success, survivorship and growth were assessed. Results showed that symbiont infection success was mainly affected by temperature and recruit type, with reduced symbiont infection at increased temperature and consistently higher infection success in chimeric recruits compared to single recruits. Furthermore, although chimeric recruits with larger areal size had significantly higher survivorship in all treatments, the polyp-specific growth rates were considerably lower in chimeric entities than individual recruits. More importantly, the recruit type significantly influenced the responses of recruit polyp-specific growth rates to elevated temperature, with chimeras exhibiting lowered skeletal lateral growth under elevated temperature. These results demonstrate the benefits and costs associated with gregarious larval settlement for juvenile corals under ocean warming and acidification, and highlight the ecological role of larval settlement behavior in mediating the responses of coral recruits to climate change stressors.

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Cyclic experiments and global buckling design of steel-angle-assembled buckling-restrained braces - Jing-Zhong Tong; En-Yuan Zhang; Yan-Lin Guo; Chao-Qun Yu (Bulletin of Earthquake Engineering, 2022)

The influences of the spatial extent selection for non-landslide samples on statistical-based landslide susceptibility modelling: a case study of Anhui Province in China - Chuhan Wang; Qigen Lin; Leibin Wang; Tong Jiang; Buda Su; Yanjun Wang; Sanjit Kumar Mondal; Jinlong Huang; Ying Wang (Natural Hazards, 2022)

Biflavonoids from the twigs and leaves of Cephalotaxus oliveri Mast. and their α -glucosidase inhibitory activity - Min Song; Tong Xiao; Qiu-Shuang Wu; Hang Fai Kwok; Ging Chan; Li-Gen Lin; Xiao-Qi Zhang; Wen-Cai Ye; Sheng-Jiang He; Qing-Wen Zhang (Natural Product Research, 2022)

Recent developments in vibrational spectral analyses for dynamically assessing and monitoring food dehydration processes - Yuqiao Ren; Xiaohui Lin; Tong Lei; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2022)

Probiotics Treatment of Leg Diseases in Broiler Chickens: a Review - Tingting Xu; Ke Yue; Chaodong Zhang; Xishuai Tong; Luxi Lin; Qinqin Cao; Shucheng Huang (Probiotics and Antimicrobial Proteins, 2022)

CiTFL1 and CiWUS Expression Provides Clues to the Mechanism of Flower Number Regulation in the Lateral Cincinni of Canna indica, a Zingiberales Species with Variable Inflorescence Architecture - Tong Zhao; Haichan Zhao; Qianxia Yu; Xueyi Tian; Canjia Lin; Jingping Liao (Journal of Plant Growth Regulation, 2022)

Clinical efficacy of melatonin as adjunctive therapy to non-surgical treatment of periodontitis: a systematic review and meta-analysis - Ru-Yue Liu; Lin Li; Zhong-Ti Zhang; Ting Wu; Shuang Lin; Xu-Tong Zhang (Inflammopharmacology, 2022)

Optimization of aquaculture sustainability through ecological intensification in China - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
As the world's leading producer of farmed aquatic food products, China faces great uncertainty concerning the further sustainable development of its aquaculture industry due to high and increasing pressure from environmental and resource constraints. To realize truly sustainable development, it is imperative to establish an evaluation system that integrates social, economic, environmental and resource criteria, and optimizes aquaculture systems through a holistic approach. Here, we used analytical hierarchy processes combined with expert judgment and objective data to assess the sustainability of 10 major aquaculture production systems (APSs) in China. Based on the evaluation results, we propose the ecological intensification of aquaculture systems (ELIAS), rationally integrating anthropogenic inputs with aquaculture ecosystem services, to improve the sustainability of APSs. The holistic evaluation system and ELIAS are fundamental and critical for the future development of aquaculture in China and globally.

Cover Image, Volume 14, Issue 3 - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
The cover image is based on the Review Article Optimization of aquaculture sustainability through ecological intensification in China by Shuang‐lin Dong et al., https://doi.org/10.1111/raq.12648 image

Community Structure of Benthic Macrofauna and the Ecological Quality of Mangrove Wetlands in Hainan, China - Ping Li; Jingli Liu; Jiankun Bai; Yifan Tong; Yuchen Meng; Xiaoping Diao; Ke Pan; Xiaoshan Zhu; Guanghui Lin (Frontiers in Marine Science, 2022)
Few studies have systematically assessed the ecological status of mangrove wetlands following the stress of anthropogenic activities in China. This study investigated the spatial and seasonal distribution of benthic macroinvertebrate communities and assessed the ecological quality of mangrove habitats on an island scale in Hainan, China (containing the third largest mangrove area of China and the highest mangrove species richness). For the benthic macrofauna community structure, a total of 102 macrobenthic taxa belonging to 50 families were identified, with Crustaceans, Molluscs, Polychaetes, and Oligochaeta having relative abundances of 52.3%, 36.1%, 10.8%, and 0.8%, respectively. Decapoda and Gastropoda dominated the benthic community abundance. Non-metric multidimensional scaling and an analysis of similarities revealed significantly different macroinvertebrate assemblages among the regions during the two seasons. The South mangroves had the lowest macrofauna species numbers, biodiversity, richness, and abundance. The macrofaunal species richness, Shannon index, Margalef index, abundance, and biomass markedly affected by region and season. As indicated by the biotic indices AMBI (AZTI’s Marine Biotic Index) and M-AMBI, more than half of the mangrove habitats on Hainan Island were slightly to heavily disturbed and had poor to moderate ecological quality. Our results recommend long-term monitoring for evaluating the quality status of mangrove wetlands and avoiding extensive land-use conversion of mangroves. Holistic approaches considering ecological characteristics and combining information on both floral and faunal functionality would contribute to the effective management and conservation of mangroves in disturbed areas.

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

First report of tobacco vein banding mosaic virus and chilli veinal mottle virus infecting Solanum muricatum in China - Ning Jiang; Xiao-tong Gai; Zhong-long Lin; Can-hua Lu; Jun-hong Ma; Zhen-yuan Xia (Journal of Plant Pathology, 2022)

Spatiotemporal characteristics and influencing factors of agricultural eco-efficiency in Jilin agricultural production zone from a low carbon perspective - Yanhua Guo; Lianjun Tong; Lin Mei (Environmental Science and Pollution Research, 2022)

Cloning and expression analysis of hif-1α and downstream genes during hypoxic stress in cobia (Rachycentron canadum) - Jian-sheng Huang; Eric Amenyogbe; Lin-tong Yang; Zhong-liang Wang; Gang Chen; Wei-zheng Wang; Jian-dong Zhang (Aquaculture International, 2022)

The effect of preoperative statin treatment on acute kidney injury in elderly patients undergoing valve replacement surgery - Bing-qi Fu; Xue-biao Wei; Zedazhong Su; Ying-wen Lin; Zu-hui Ke; Tong Tan; Ji-yan Chen; Shou-hong Wang; Dan-qing Yu (European Journal of Clinical Pharmacology, 2022)

Genome-wide analysis of BURP genes and identification of a BURP-V gene RcBURP4 in Rosa chinensis - Lufeng Fu; Zhujun Zhang; Hai Wang; Xiaojuan Zhao; Lin Su; Lifang Geng; Yizeng Lu; Boqiang Tong; Qinghua Liu; Xinqiang Jiang (Plant Cell Reports, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Induction and Genomic Analysis of a Lysogenic Phage of Hafnia paralvei - Lingting Pan; Dengfeng Li; Yigang Tong; Wei Lin; Weinan Qin; Lihua Xu; Pingping Zhan (Current Microbiology, 2022)

Hsp60/10 and sHsp families of heat shock protein genes in rainbow trout (Oncorhynchus mykiss) and their expression under heat stress - Fang Ma; Lin Tong Luo; Qianning Wang (Aquaculture International, 2022)

Development and validation of a 30-day death nomogram in patients with spontaneous cerebral hemorrhage: a retrospective cohort study - Qian Han; Mei Li; Dongpo Su; Aijun Fu; Lin Li; Tong Chen (Acta Neurologica Belgica, 2022)

Adaptations of Plutella xylostella adult females and larvae to waxy host plants - Jing-Yun Zhu; Zhong-Wen Xiang; Shi-Ze Zhang; Lin-Nan Wu; Tong-Xian Liu (Journal of Pest Science, 2022)

Characteristics of fine particulate matter (PM2.5) at Jinsha Site Museum, Chengdu, China - Jialin Deng; Luman Jiang; Wenwen Miao; Junke Zhang; Guiming Dong; Ke Liu; Juncheng Chen; Tong Peng; Yao Fu; Yunpei Zhou; Xue Huang; Mengqian Hu; et al. (Environmental Science and Pollution Research, 2022)

Evolutionary characteristics and phylogeny of cotton chloroplast tRNAs - Ning Wang; Wan-Lin Dong; Xiao-Jing Zhang; Tong Zhou; Xiao-Juan Huang; Bao-Guo Li; Jian-Ni Liu; Xiong-Feng Ma; Zhong-Hu Li (Planta, 2021)

Occurrence, source apportionment, and carcinogenic risk assessment of polycyclic aromatic hydrocarbons in urban road dusts in Shanghai - Xue-Tong Wang; Rui Fu; Ying Zhou; Cheng-Lin Wang; Guo-Fa Ren; Xiao-Li Wang; Hui Li (Environmental Science and Pollution Research, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Phylogenetic analysis of Engleromyces sinensis and identification of cytochalasin D from culture - Hao Zhou; Qiu-Tong Wang; Xin Tong; Cheng-Lin Hou (Mycological Progress, 2021)

Harvest Time Effects on Yield, Quality and Aroma of Fragrant Rice - Jisheng Zhang; Tianyi Tong; Pouwedeou Mouloumdema Potcho; Lin Li; Suihua Huang; Qinwen Yan; Xiangru Tang (Journal of Plant Growth Regulation, 2021)

Evaluation on sustainable development of forest tourism in Heilongjiang Province, China - Lin Li; Tong Liu; Subo Xu; Zhiwei Tian (Environment, Development and Sustainability, 2021)

Bioaccumulation and translocation of trace elements in soil-irrigation water-wheat in arid agricultural areas of Xin Jiang, China - Muyesaier Tudi; Huada Daniel Ruan; Yunjiang Yu; Li Wang; Binggan Wei; Shuangmei Tong; Chang Kong; Lin-sheng Yang (Ecotoxicology, 2021)

Assessment of the Nutritional Value of Cultured Sea Cucumber Apostichopus japonicus - Meng Li; Yue Gao; Yan-xia Qi; Zhi-yuan Song; Zhi-bo Li; Yan-tong Lin; Qian-cheng Zhao (Journal of Aquatic Food Product Technology, 2021)

Association between population density and infection rate suggests the importance of social distancing and travel restriction in reducing the COVID-19 pandemic - Heliang Yin; Tong Sun; Lan Yao; Yan Jiao; Li Ma; Lin Lin; J Carolyn Graff; Lotfi Aleya; Arnold Postlethwaite; Weikuan Gu; Hong Chen (Environmental Science and Pollution Research, 2021)

Why pendulum symmetry is absent from the cymose partial inflorescences of Cannaceae? Insights into the essential characteristic of cincinni - Xueyi Tian; Qianxia Yu; Canjia Lin; Tong Zhao; Pu Zou; Jingping Liao (Journal of Plant Research, 2021)

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Proteomic Response of the Brain to Hypoxic Stress in Marine Medaka Fish (Oryzias melastigma) - Keng Po Lai; Nathan Tam; Simon Yuan Wang; William Ka Fai Tse; Xiao Lin; Ting Fung Chan; Yin Tong; Jianwen Zhang; Doris Wai Ting Au; Rudolf Shiu Sun Wu; Richard Yuen Chong Kong (Frontiers in Marine Science, 2021)
Hypoxia is a serious issue that affects the marine environment, with a growing number of hypoxic “dead zones” occurring each year. Reports have indicated that hypoxia is detrimental to the reproductive function and sexual development of fish via the disruption of endocrine signaling in organs involved in the hypothalamus–pituitary–gonad axis, including the brain. While we previously reported that hypoxia induces transcriptome-wide alterations in the brain of marine medaka ( Oryzias melastigma ), whether these effects were reflected at the protein level remains unclear. Therefore, the present study used high-throughput proteomic sequencing along with bioinformatics analysis to assess the short-term and multi-generational effects of hypoxia on the brain proteome of O. melastigma . We identified 36,567 peptides and 7,599 proteins (1% false discovery rate in brain samples), with functions involved in cellular and metabolic processes such as signaling and reproductive processes as well as energy production and conversion. Furthermore, we determined that hypoxia resulted in the significant differential expressions of 33 upregulated and 69 downregulated proteins in the short-term exposure group and 24 upregulated and 52 downregulated proteins in the multi-generational exposure group. Pathway enrichment analysis of the deregulated proteins indicated that hypoxia could impair brain function by altering arachidonic acid metabolism, tight junctions, and adrenergic signaling under short-term hypoxic exposure and by altering p53 and PI3K–Akt signaling under multi-generational hypoxic exposure, which may lead to the onset of neurodegenerative disorders including Alzheimer’s disease and amyotrophic lateral sclerosis. Ingenuity pathway analysis of the deregulated proteins showed that hypoxia affected common signaling pathways in the brain (e.g., integrin, paxillin, and epithelial adherens junction signaling) under both short-term and multi-generational exposures. Hypoxia also deregulated pathways specific to short-term exposure (including integrin-linked kinase, calcium, and integrin signaling) and multi-generational exposure (including sphingosine-1-phosphate signaling, endocannabinoid neuronal synapse pathway, and endoplasmic reticulum stress pathway). Overall, our results provide additional insights into the mechanisms of hypoxia disrupting neuronal function at the protein level in marine medaka.

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

TLR8 in the Trigeminal Ganglion Contributes to the Maintenance of Trigeminal Neuropathic Pain in Mice - Lin-Xia Zhao; Ming Jiang; Xue-Qiang Bai; De-Li Cao; Xiao-Bo Wu; Jing Zhang; Jian-Shuang Guo; Tong-Tong Chen; Juan Wang; Hao Wu; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)
Trigeminal neuropathic pain (TNP) is a significant health problem but the involved mechanism has not been completely elucidated. Toll-like receptors (TLRs) have recently been demonstrated to be expressed in the dorsal root ganglion and involved in chronic pain. Here, we show that TLR8 was persistently increased in the trigeminal ganglion (TG) neurons in model of TNP induced by partial infraorbital nerve ligation (pIONL). In addition, deletion or knockdown of Tlr8 in the TG attenuated pIONL-induced mechanical allodynia, reduced the activation of ERK and p38-MAPK, and decreased the expression of pro-inflammatory cytokines in the TG. Furthermore, intra-TG injection of the TLR8 agonist VTX-2337 induced pain hypersensitivity. VTX-2337 also increased the intracellular Ca 2+ concentration, induced the activation of ERK and p38, and increased the expression of pro-inflammatory cytokines in the TG. These data indicate that TLR8 contributes to the maintenance of TNP through increasing MAPK-mediated neuroinflammation. Targeting TLR8 signaling may be effective for the treatment of TNP.

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

The effect of conservation tillage in managing climate change in arid and semiarid areas—a case study in Northwest China - Lin Dong; Tong Si; Yu-e Li; Xiao-Xia Zou (Mitigation and Adaptation Strategies for Global Change, 2021)

Neuroprotective Effect of Fractalkine on Radiation-induced Brain Injury Through Promoting the M2 Polarization of Microglia - Jiaojiao Wang; Huijiao Pan; Zhenyu Lin; Chunjin Xiong; Chunhua Wei; Huanhuan Li; Fan Tong; Xiaorong Dong (Molecular Neurobiology, 2021)
Radiation-induced brain injury (RIBI) is a serious complication in cancer patients receiving brain radiotherapy, and accumulating evidence suggests that microglial activation plays an important role in its pathogenesis. Fractalkine (FKN) is a crucial mediator responsible for the biological activity of microglia. In this study, the effect of FKN on activated microglial after irradiation and RIBI was explored and the underlying mechanisms were investigated. Our study demonstrated treatment with exogenous FKN diminished radiation-induced production of pro-inflammatory factors, such as IL1-β and TNFα, promoted transformation of microglial M1 phenotype to M2 phenotype after irradiation, and partially recovered the spatial memory of irradiated mice. Furthermore, upregulation of FKN/CX3CR1 via FKN lentivirus promoted radiation-induced microglial M2 transformation in the hippocampus and diminished the spatial memory injury of irradiated mice. Furthermore, while inhibiting the expression of CX3CR1, which exclusively expressed on microglia in the brain, the regulatory effect of FKN on microglia and cognitive ability of mice disappeared after radiation. In conclusion, the FKN could attenuate RIBI through the microglia polarization toward M2 phenotype by binding to CX3CR1 on microglia. Our study unveiled an important role of FKN/CX3CR1 in RIBI, indicating that promotion of FKN/CX3CR1 axis could be a promising strategy for the treatment of RIBI.

PCDD/Fs characteristics in flue gas and surrounding environment of iron and steel smelting industry - Mingxiu Zhan; Yufeng Ma; Tong Chen; Xiaoqing Lin; Shiying Zhang; Shuaixi Xu; Xiaodong Li; Jianhua Yan (Environmental Science and Pollution Research, 2021)

Identification of Aspergillus tubingensis causing pomegranate fruit rot in China - Mei Jun Guo; Qiu Tong Wang; Yuan Hui Cheng; Cheng Lin Hou (Australasian Plant Pathology, 2021)

Complete genome analysis of an active prophage of Vibrio alginolyticus - Weinan Qin; Dengfeng Li; Lihua Xu; Wei Lin; Yigang Tong (Archives of Virology, 2021)

Evaluation of favourable hot dry rock areas in the east of the Yishu fault zone in China - Q. Deng; A. Jiang; Z. Tong; H. Lin; Z. Gao; X. Sun; M. Nie (Australian Journal of Earth Sciences, 2021)

Ecological and health risk assessment of trace elements in surface soil in an arid region of Xin Jiang, China - Muyesaier Tudi; Huada Daniel Ruan; Binggan Wei; Li Wang; Shuangmei Tong; Chang Kong; Lin-sheng Yang (Journal of Soils and Sediments, 2021)

Effect of soil moisture on pupation behavior and inhabitation of Spodoptera frugiperda (Lepidoptera: Noctuidae) - Yan Shi; Lin-Yu Li; Sohaib Shahid; Guy Smagghe; Tong-Xian Liu (Applied Entomology and Zoology, 2021)

Inversion analysis of the shear strength parameters for a high loess slope in the limit state - Xiao-yan Lin; Lin-fan Zhang; Ze Yang; Ping Li; Tong-lu Li (Journal of Mountain Science, 2021)

Identification and Functional Characterization of a Novel Δ12 Fatty Acid Desaturase Gene from Haematococcus pluvialis - Lin Zhang; Wenbi Chen; Shuping Yang; Yuanbo Zhang; Jilin Xu; Dongjie Yang; Zuyao Wu; Tong Liu; Jiayi Cao (Journal of Ocean University of China, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Application of exogenous salicylic acid on improving high temperature resistance of Nannochloropsis oceanica - Lin Zhang; Shuping Yang; Jilin Xu; Tong Liu; Dongjie Yang; Zuyao Wu; Mengjie Shao (Aquaculture International, 2020)

Two new sesquiterpenoid glycosides from the stems of Zanthoxylum armatum DC - Ya-Lin Liu; Liang-Liang Gao; Tong-Tong Song; Tao Guo; Jun Chang (Natural Product Research, 2020)

Illumina sequencing revealed roles of microRNAs in different aluminum tolerance of two citrus species - Yang-Fei Zhou; Yan-Yu Wang; Wei-Wei Chen; Li-Song Chen; Lin-Tong Yang (Physiology and Molecular Biology of Plants, 2020)

Proteomics and phosphoproteomics revealed molecular networks of stomatal immune responses - Qiuying Pang; Tong Zhang; Aiqin Zhang; Chuwei Lin; Wenwen Kong; Sixue Chen (Planta, 2020)

A novel freshwater cyanophage vB_MelS-Me-ZS1 infecting bloom-forming cyanobacterium Microcystis elabens - Wei Lin; Dengfeng Li; Zhitong Sun; Yigang Tong; Xiaojun Yan; Chunlin Wang; Xianglilan Zhang; Guangqian Pei (Molecular Biology Reports, 2020)

Effects of exogenous selenium levels on humus characteristics in selenium-enriched soil and lead accumulation in Brassica juncea - Yanshi Wang; Shengxu Luo; Zheng Wang; Zhuang Tong; Qin Deng; Yanling Lin; Lanxin Zhang (Journal of Soils and Sediments, 2020)

Small RNA profiling reveal regulation of microRNAs in field peanut pod rot pathogen infection - Mian Wang; Chao-xin Zhang; Li-juan Pan; Tong Wang; Na Chen; Ming-na Chen; Zhen Yang; Xin-gang Guo; Shan-lin Yu; Xiao-yuan Chi (Biologia, 2020)

Association Between PSD95 Gene 3′UTR Single Nucleotide Polymorphism and Risk of Acute Ischemic Stroke in Chinese Han Population - Ying-Ying Lin; Tong-ya Yu; Hui Quan; Yu-Juan Chen; Xue-Yuan Liu; Dong-Ya Huang (Journal of Molecular Neuroscience, 2020)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

Comprehensive Investigation and Assessment of Nutrient and Heavy Metal Contamination in the Surface Water of Coastal Bohai Sea in China - Heshan Lin; Hongjun Li; Xiaolong Yang; Zizhou Xu; Yindong Tong; Xingguang Yu (Journal of Ocean University of China, 2020)

An autoanalyzer for real-time detection of benzene and volatile organic compounds in paper mills - Zhifeng Lin; Wenhao Shen; Xin Tong; Jean-Pierre Corriou (Environmental Chemistry Letters, 2020)

Study of Effects of Hard Thick Roof on Gas Migration and Field Experiment of Roof Artificially Guided Pre-splitting for Efficient Gas Control - Tong Liu; Baiquan Lin; Wei Yang; Ting Liu; Wu Xiao; Wei Zha (Natural Resources Research, 2020)

Beneficial consequences of Lupeol on middle cerebral artery-induced cerebral ischemia in the rat involves Nrf2 and P38 MAPK modulation - Zhiyuan Zhang; Chongfu Xu; Jiheng Hao; Meng Zhang; Zidong Wang; Tengkun Yin; Kai Lin; Weidong Liu; Qunlong Jiang; Zhongchen Li; Dan Wang; Zhiqi Mao; et al. (Metabolic Brain Disease, 2020)

Endometrial autophagy is essential for embryo implantation during early pregnancy - Yan Su; Juan-Juan Zhang; Jun-Lin He; Xue-Qing Liu; Xue-Mei Chen; Yu-Bin Ding; Chao Tong; Chuan Peng; Yan-Qing Geng; Ying-Xiong Wang; Ru-Fei Gao (Journal of Molecular Medicine, 2020)

Improved in-situ Determination of Sr Isotope Ratio in Silicate Samples Using LA-MC-ICP-MS and Its Wider Application for Fused Rock Powder - Lüyun Zhu; Ganglan Zhang; Yongsheng Liu; Jie Lin; Xirun Tong; Shaoyong Jiang (Journal of Earth Science, 2020)

Optimization of the OCO-2 Cloud Screening Algorithm and Evaluation against MODIS and TCCON Measurements over Land Surfaces in Europe and Japan - Sijie Chen; Shuaibo Wang; Lin Su; Changzhe Dong; Ju Ke; Zhuofan Zheng; Chonghui Cheng; Bowen Tong; Dong Liu (Advances in Atmospheric Sciences, 2020)

Contrasting the Pb (II) and Cd (II) tolerance of Enterobacter sp. via its cellular stress responses - Zhongquan Jiang; Liu Jiang; Lin Zhang; Mu Su; Da Tian; Tong Wang; Yalin Sun; Ying Nong; Shuijin Hu; Shimei Wang; Zhen Li (Environmental Microbiology, 2020)
Summary Successful application of microorganisms to heavy metal remediation depends on their resistance to toxic metals. This study contrasted the differences of tolerant mechanisms between Pb 2+ and Cd 2+ in Enterobacter sp. Microbial respiration and production of formic acid showed that Enterobacter sp. had a higher tolerant concentration of Pb (>1000 mg l −1 ) than Cd (about 200 mg l −1 ). Additionally, SEM confirmed that most of Pb and Cd nanoparticles (NPs) were adsorbed onto cell membrane. The Cd stress, even at low concentration (50 mg l −1 ), significantly enlarged the sizes of cells. The cellular size raised from 0.4 × 1.0 to 0.9 × 1.6 μm on average, inducing a platelet‐like shape. In contrast, Pb cations did not stimulate such enlargement even up to 1000 mg l −1 . Moreover, Cd NPs were adsorbed homogeneously by almost all the bacterial cells under TEM. However, only a few cells work as ‘hot spots’ on the sorption of Pb NPs. The heterogeneous sorption might result from a ‘self‐sacrifice’ mechanism, i.e., some cells at a special life stage contributed mostly to Pb sorption. This mechanism, together with the lower mobility of Pb cations, caused higher microbial tolerance and removal efficiency towards Pb 2+ . This study sheds evident contrasts of bacterial resistance to the two most common heavy metals.

α-Arbutin Protects Against Parkinson’s Disease-Associated Mitochondrial Dysfunction In Vitro and In Vivo - Yaqi Ding; Deqin Kong; Tong Zhou; Nai-di Yang; Chenqi Xin; Jiajia Xu; Qi Wang; Hang Zhang; Qiong Wu; Xiaomei Lu; Kahleong Lim; Bo Ma; et al. (NeuroMolecular Medicine, 2020)

Hostaflavanol A, a new anti-inflammatory and antioxidant activities flavanol from the flowers of Hosta plantaginea - Li Yang; Yi-min Lin; Zhong-wei He; Ting-fang Zhang; Yu Li; Xiao-tong Xie; Yi-feng Wu; Jun-wei He (Medicinal Chemistry Research, 2020)

Global buckling prevention of reduced-core-length buckling-restrained braces: theoretical and numerical investigations - Jing-Zhong Tong; Yan-Lin Guo; Wen-Hao Pan; Min-Hui Shen; Peng Zhou (Bulletin of Earthquake Engineering, 2020)

The NADPH oxidase in Volvariella volvacea and its differential expression in response to mycelial ageing and mechanical injury - Jun-Jie Yan; Zong-Jun Tong; Yuan-Yuan Liu; Zi-Yan Lin; Ying Long; Xing Han; Wei-Nan Xu; Qian-Hui Huang; Yong-Xin Tao; Bao-Gui Xie (Brazilian Journal of Microbiology, 2020)

High prevalence and viremia of human pegivirus 2 in the HIV-infected population in Honghe Prefecture, Yunnan Province - Tianyi Li; Shixing Tang; Yingying Su; Zuoyi Bao; Xiaolin Wang; Yongjian Liu; Hanping Li; Jingwan Han; Zhichao Pei; Zhengwei Wan; Hang Fan; Yigang Tong; et al. (Archives of Virology, 2020)

The bacterial RNA ligase RtcB accelerates the repair process of fragmented rRNA upon releasing the antibiotic stress - Muhammad Ramzan Manwar; Changjun Shao; Xing Shi; Jian Wang; Qiang Lin; Yigang Tong; Yu Kang; Jun Yu (Science China Life Sciences, 2020)

Non-motor Symptoms in Parkinson’s Disease Patients with Parkin Mutations: More Depression and Less Executive Dysfunction - Jie Song; Bo Shen; Yu-Jie Yang; Feng-tao Liu; Jue Zhao; Yi-Lin Tang; Chen Chen; Zheng-Tong Ding; Yu An; Jian-Jun Wu; Yi-Min Sun; Jian Wang (Journal of Molecular Neuroscience, 2020)

Simulation of the impact of the emergency control measures on the reduction of air pollutants: a case study of APEC blue - Peifeng Tong; Qianru Zhang; Huiming Lin; Xiaohu Jian; Xuejun Wang (Environmental Monitoring and Assessment, 2020)

Characterizing the spatial distribution of typical natural disaster vulnerability in China from 2010 to 2017 - Qian Wang; Qi-peng Zhang; Yang-yang Liu; Lin-jing Tong; Yan-zhen Zhang; Xiao-yu Li; Jian-long Li (Natural Hazards, 2020)

Joined fragment segmentation for fractured bones using GPU-accelerated shape-preserving erosion and dilation - Yue Zhang; Ruofeng Tong; Dan Song; Xiaobo Yan; Lanfen Lin; Jian Wu (Medical & Biological Engineering & Computing, 2020)

Echolocation call divergence in bats: a comparative analysis - Bo Luo; Leith Leiser-Miller; Sharlene E. Santana; Lin Zhang; Tong Liu; Yanhong Xiao; Ying Liu; Jiang Feng (Behavioral Ecology and Sociobiology, 2019)

A new phenolic glycoside from the Idesia polycarpa Maxim. leaves - Lei Huang; Tong Peng; Yu Li; Yunyun He; Li Wang; Shiyan Zhang; Yiran Sun; Fang Chen; Lin Tang (Natural Product Research, 2019)

An integrated strategy to identify genes responsible for sesquiterpene biosynthesis in turmeric - Jingru Sun; Guanghong Cui; Xiaohui Ma; Zhilai Zhan; Ying Ma; Zhongqiu Teng; Wei Gao; Yanan Wang; Tong Chen; Changjiangsheng Lai; Yujun Zhao; Jinfu Tang; et al. (Plant Molecular Biology, 2019)

Excess copper effects on growth, uptake of water and nutrients, carbohydrates, and PSII photochemistry revealed by OJIP transients in Citrus seedlings - Qiang Li; Huan-Huan Chen; Yi-Ping Qi; Xin Ye; Lin-Tong Yang; Zeng-Rong Huang; Li-Song Chen (Environmental Science and Pollution Research, 2019)

Analysis of the elemental spectral characteristics of single elemental capture spectrum log using Monte-Carlo simulation - Chang-Lin Lan; Xu-Wen Zhan; Hong-Liang Wu; Yi Zhang; Tong Liu; Zhou Feng; Tao Lv (Applied Geophysics, 2019)

Study on the relationship between waste classification, combustion condition and dioxin emission from waste incineration - Xiaodong Li; Yunfeng Ma; Mengmei Zhang; Mingxiu Zhan; Peiyue Wang; Xiaoqing Lin; Tong Chen; Shengyong Lu; Jianhua Yan (Waste Disposal & Sustainable Energy, 2019)

Correction to: Antidepressant-Like Action of Single Facial Injection of Botulinum Neurotoxin A is Associated with Augmented 5-HT Levels and BDNF/ERK/CREB Pathways in Mouse Brain - Yang Li; Jing Liu; Xu Liu; Cun-Jin Su; Qi-Lin Zhang; Zhi-Hong Wang; Lei-Fang Cao; Xue-Yan Guo; Ya Huang; Weifeng Luo; Tong Liu (Neuroscience Bulletin, 2019)

Antidepressant-Like Action of Single Facial Injection of Botulinum Neurotoxin A is Associated with Augmented 5-HT Levels and BDNF/ERK/CREB Pathways in Mouse Brain - Yang Li; Jing Liu; Xu Liu; Cun-Jin Su; Qi-Lin Zhang; Zhi-Hong Wang; Lei-Fang Cao; Xue-Yan Guo; Ya Huang; Weifeng Luo; Tong Liu (Neuroscience Bulletin, 2019)

Staphylococcal driveline infections are the predominant type of left ventricular assist device associated infections in Singapore - Yii Ean Teh; Choon Pin Lim; Louis Loon Yee Teo; Jia Lin Soon; Victor Tar Toong Chao; Chia Lee Neo; Joycelyn Li Li Tan; Ka Lee Kerk; David Kheng Leng Sim; Teing Ee Tan; Ban Hock Tan; Sivathasan Cumaraswamy; et al. (Infectious Diseases, 2019)

Hysteretic performance of inverted-V patterned BRB systems considering vertical pre-compression effects - Jing-Zhong Tong; Yan-Lin Guo; Wen-Hao Pan; Peng Zhou; Meng-Zheng Wang (Bulletin of Earthquake Engineering, 2019)

Dynamic changes in lakes in the Hoh Xil region before and after the 2011 outburst of Zonag Lake - Wen-hui Liu; Chang-wei Xie; Lin Zhao; Tong-hua Wu; Wu Wang; Yu-xin Zhang; Gui-qian Yang; Xiao-fan Zhu; Guang-yang Yue (Journal of Mountain Science, 2019)

Intraguild predation between Harmonia axyridis and Aphidius gifuensis: effects of starvation period, plant dimension and extraguild prey density - Xing-Lin Yu; Yi Feng; Wen-Yan Fu; Yuan-Xing Sun; Tong-Xian Liu (BioControl, 2019)

Ornithinimicrobium cavernae sp. nov., an actinobacterium isolated from a karst cave - Ling-Yu Zhang; Hong Ming; Xiao-Lin Meng; Bao-Zhu Fang; Jian-Yu Jiao; Nimaichand Salam; Xiao-Tong Zhang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2019)

Molecular cloning and functional characterization of multiple geranylgeranyl pyrophosphate synthases (ApGGPPS) from Andrographis paniculata - Jian Wang; Hui-Xin Lin; Ping Su; Tong Chen; Juan Guo; Wei Gao; Lu-Qi Huang (Plant Cell Reports, 2019)

The contribution of parent-to-offspring transmission of telomeres to the heritability of telomere length in humans - Dayana A. Delgado; Chenan Zhang; Kevin Gleason; Kathryn Demanelis; Lin S. Chen; Jianjun Gao; Shantanu Roy; Justin Shinkle; Mekala Sabarinathan; Maria Argos; Lin Tong; Alauddin Ahmed; et al. (Human Genetics, 2019)

Induction and identification of tetraploid Hedychium coronarium through thin cell layer culture - Hong-Yan Tu; Ai-Ling Zhang; Wang Xiao; Ya-Rou Lin; Jun-Hui Shi; Yong-Wei Wu; Si-Tong Wu; Chun-Hui Zhong; Shui-Xiu Mo (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Risk factors and drug resistance in early-onset neonatal group B streptococcal disease - Ying-wei Wang; Yao-qiang Du; Xiao-lin Miao; Guang-yong Ye; Yi-yun Wang; Ai-bo Xu; Yun-zhong Jing; Yu Tong; Kai Xu; Mei-qin Zheng; Dong Chen; Zhen Wang (Journal of Zhejiang University-SCIENCE B, 2018)

Multilocus phylogeny and species delimitation within the philippinensis group (Chiroptera: Rhinolophidae) - Lin Zhang; Keping Sun; Tong Liu; Hanbo Zhao; Gábor Csorba; Longru Jin; Vu Dinh Thong; Jiang Feng (Zoologica Scripta, 2018)
Rhinolophids (horseshoe bats) are a widespread and diverse family. Their high level of morphological convergence has made taxonomic identification and estimation of species diversity problematic. The Rhinolophus philippinensis group, which is characterized with huge ears and low echolocation frequency relative to body size, is a specific group among all the rhinolophid groups, but the phylogeny of this group is poorly understood. In this study, we performed integrated analyses of the morphology, acoustic and genetic data and constructed the first multilocus phylogeny for the philippinensis group using four mitochondrial genes, four autosomal introns and one Y‐linked intron in 95 specimens representing nine taxa. Phylogenies were constructed based on concatenated phylogenetic methods and a multilocus coalescence approach. The estimated phylogenies revealed the polyphyly of the philippinensis group. Except for R. philippinensis , all the other species in this group formed a monophyletic cluster, named herewith as “ R. macrotis ” species group. Phylogenies, genetic and phenotypic divergence, and species delimitation analyses supported the revised status of R. paradoxolophus as a subspecies of R. rex , R . cf . macrotis as a subspecies of R. macrotis , and R. huananus and R . cf . siamensis as junior synonyms of R. siamensis . Significant discordances were found between the mitochondrial and nuclear gene trees, suggesting incomplete lineage sorting or ancient introgression events within the philippinensis group. The macrotis group appeared to have undergone a rapid radiation approximately 2.57 million years ago during the early Pleistocene period due to palaeoclimatic oscillations. Reconstruction of the ancestral ranges suggested a wide distribution of the common ancestor for the philippinensis and macrotis groups.

The roles of the COX2/PGE2/EP axis in therapeutic resistance - Dali Tong; Qiuli Liu; Lin-ang Wang; Qiubo Xie; Jian Pang; Yiqiang Huang; Luofu Wang; Gaolei Liu; Dianzheng Zhang; Weihua Lan; Jun Jiang (Cancer and Metastasis Reviews, 2018)

Subassemblage tests and design of steel channels assembled buckling-restrained braces - Yan-Lin Guo; Jing-Zhong Tong; Xiao-An Wang; Peng Zhou (Bulletin of Earthquake Engineering, 2018)

Soil infiltration processes of different underlying surfaces in the permafrost region on the Tibetan Plateau - Guo-jie Hu; Li-ming Tian; Lin Zhao; Xiao-dong Wu; Ren Li; Tong-hua Wu; Xiao-fan Zhu; Er-ji Du; Zhi-wei Wang; Jun-ming Hao; Wang-ping Li; Song-he Wang (Hydrological Sciences Journal, 2018)

Altered Profiles of Gut Microbiota in Klebsiella pneumoniae-Induced Pyogenic Liver Abscess - Nan Chen; Zong-Xin Ling; Tong-Tong Jin; Ming Li; Sheng Zhao; Li-Shuang Zheng; Xin Xi; Lin-Lin Wang; Ying-Ying Chen; Yue-Liang Shen; Li-Ping Zhang; Shao-cong Sun (Current Microbiology, 2018)

Identifying potentially common genes between dyslipidemia and osteoporosis using novel analytical approaches - Xu Lin; Cheng Peng; Jonathan Greenbaum; Zhang-Fang Li; Ke-Hao Wu; Zeng-Xin Ao; Tong Zhang; Jie Shen; Hong-Wen Deng (Molecular Genetics and Genomics, 2018)

Phthalate exposure and high blood pressure in adults: a cross-sectional study in China - Shao-hui Zhang; Ya-xin Shen; Lin Li; Tong-tong Fan; Yan Wang; Ning Wei (Environmental Science and Pollution Research, 2018)

Dynamic changes of habitats in China’s typical national nature reserves on spatial and temporal scales - Ping Zhu; Lin Huang; Tong Xiao; Junbang Wang (Journal of Geographical Sciences, 2018)

Analysis of fecal microbiota in patients with functional constipation undergoing treatment with synbiotics - Lin Sheng Huang; Cheng Kong; Ren Yuan Gao; Xuebing Yan; Hong Jing Yu; Bin Wen; Qi Zhu; Tong Yi Shen; Zhen Liang Sun; Huan Long Qin (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

CyberConnector: a service-oriented system for automatically tailoring multisource Earth observation data to feed Earth science models - Ziheng Sun; Liping Di; Haosheng Hao; Xiaoqing Wu; Daniel Q. Tong; Chen Zhang; Cora Virgei; Hui Fang; Eugene Yu; Xicheng Tan; Peng Yue; Li Lin (Earth Science Informatics, 2018)

Screening for gene–environment (G×E) interaction using omics data from exposed individuals: an application to gene-arsenic interaction - Maria Argos; Lin Tong; Shantanu Roy; Mekala Sabarinathan; Alauddin Ahmed; Md. Tariqul Islam; Tariqul Islam; Muhammad Rakibuz-Zaman; Golam Sarwar; Hasan Shahriar; Mahfuzar Rahman; Md. Yunus; et al. (Mammalian Genome, 2018)

Regional differentiation of ecological conservation and its zonal suitability at the county level in China - Lin Huang; Yuhan Zheng; Tong Xiao (Journal of Geographical Sciences, 2018)

Major transgression during Late Cretaceous constrained by basin sediments in northern Africa: implication for global rise in sea level - Kaixuan An; Hanlin Chen; Xiubin Lin; Fang Wang; Shufeng Yang; Zhixin Wen; Zhaoming Wang; Guangya Zhang; Xiaoguang Tong (Frontiers of Earth Science, 2017)

Analysis of miRNA-seq combined with gene expression profile reveals the complexity of salinity stress response in Oryza sativa - Qingwei Wang; Tianlong Geng; Shuhua Zhu; Rui Li; Yongao Tong; Shenghua Wang; Fang Chen; Lin Tang; Yang He (Acta Physiologiae Plantarum, 2017)

Identification of heat-responsive miRNAs to reveal the miRNA-mediated regulatory network of heat stress response in Betula luminifera - Ying Pan; Mingyue Niu; Junsheng Liang; Erpei Lin; Zaikang Tong; Junhong Zhang (Trees, 2017)

Design, synthesis, antitumor evaluation, 3D-QSAR and molecular docking studies of novel 4-aminoacridone compounds - Lin Tian; Chang J. Feng; Tong X. Li; Zhao Li; Wei H. Yang; Xiang E. Han (Medicinal Chemistry Research, 2017)

Comparison of infrared canopy temperature in a rubber plantation and tropical rain forest - Qing-Hai Song; Yun Deng; Yi -Ping Zhang; Xiao-Bao Deng; You-Xing Lin; Li-Guo Zhou; Xue-Hai Fei; Li-Qing Sha; Yun-Tong Liu; Wen-Jun Zhou; Jin-Bo Gao (International Journal of Biometeorology, 2017)

Microbiome dynamics in early life stages of the scleractinian coral Acropora gemmifera in response to elevated p CO 2 - Guowei Zhou; Lin Cai; Tao Yuan; Renmao Tian; Haoya Tong; Weipeng Zhang; Lei Jiang; Minglan Guo; Sheng Liu; Pei‐Yuan Qian; Hui Huang (Environmental Microbiology, 2017)
Summary Reef‐building corals are complex holobionts, harbouring diverse microorganisms that play essential roles in maintaining coral health. However, microbiome development in early life stages of corals remains poorly understood. Here, microbiomes of Acropora gemmifera were analysed during spawning and early developmental stages, and also under different seawater partial pressure of CO 2 ( p CO 2 ) conditions, using amplicon sequencing of 16S rRNA gene for bacteria and archaea and of ITS2 for Symbiodinium . No remarkable microbiome shift was observed in adults before and after spawning. Moreover, microbiomes in eggs were highly similar to those in spawned adults, possibly suggesting a vertical transmission from parents to offspring. However, significant stage‐specific changes were found in coral microbiome during development, indicating that host development played a dominant role in shaping coral microbiome. Specifically, Cyanobacteria were particularly abundant in 6‐day‐old juveniles, but decreased largely in 31‐day‐old juveniles with a possible subclade shift in Symbiodinium dominance from C2r to D17. Larval microbiome showed changes in elevated p CO 2 , while juvenile microbiomes remained rather stable in response to higher p CO 2 . This study provides novel insights into the microbiome development during the critical life stages of coral.

Coal Permeability Evolution and Gas Migration Under Non-equilibrium State - Ting Liu; Baiquan Lin; Wei Yang; Cheng Zhai; Tong Liu (Transport in Porous Media, 2017)

First complete genome sequence of a virulent bacteriophage infecting the opportunistic pathogen Serratia rubidaea - Shaozhen Xing; Taping Ma; Xianglilan Zhang; Yong Huang; Zhiqiang Mi; Qiang Sun; Xiaoping An; Hang Fan; Shuhui Wu; Lin Wei; Yigang Tong (Archives of Virology, 2017)

Identification of manganese-toxicity-responsive genes in roots of two citrus species differing in manganese tolerance using cDNA-AFLP - Chen-Ping Zhou; Chun-Ping Li; Wei-Wei Liang; Peng Guo; Lin-Tong Yang; Li-Song Chen (Trees, 2017)

The Role of Photoreceptors in Response to Cucumber Mosaic Virus in Arabidopsis thaliana - Xue Zhou; Tong Zhu; Li-Sha Zhu; Shi-Shuai Luo; Xing-Guang Deng; Hong-hui Lin; De-Hui Xi (Journal of Plant Growth Regulation, 2017)

Evaluation of passive sampling of gaseous mercury using different sorbing materials - Huiming Lin; Wei Zhang; Chunyan Deng; Yingdong Tong; Qianggong Zhang; Xuejun Wang (Environmental Science and Pollution Research, 2017)

MicroRNA-27a Promotes Inefficient Lysosomal Clearance in the Hippocampi of Rats Following Chronic Brain Hypoperfusion - Hui Che; Yan Yan; Xiao-Hui Kang; Fei Guo; Mei-Ling Yan; Huai-Lei Liu; Xu Hou; Tong Liu; De-Kang Zong; Lin-Lin Sun; Ya-Nan Bao; Li-Hua Sun; et al. (Molecular Neurobiology, 2017)

The influence of feeding and host deprivation on egg load and reproduction of an aphid parasitoid, Aphidius gifuensis (Hymenoptera: Braconidae) - Ming-Zhen Pan; Li Wang; Chen-Yang Zhang; Lin-Xi Zhang; Tong-Xian Liu (Applied Entomology and Zoology, 2017)

Transplantation of collagen scaffold with autologous bone marrow mononuclear cells promotes functional endometrium reconstruction via downregulating ΔNp63 expression in Asherman’s syndrome - Guangfeng Zhao; Yun Cao; Xianghong Zhu; Xiaoqiu Tang; Lijun Ding; Haixiang Sun; Juan Li; Xinan Li; Chenyan Dai; Tong Ru; Hui Zhu; Jingjie Lu; et al. (Science China Life Sciences, 2017)

Effects of Porphyromonas gingivalis on Titanium Surface by Different Clinical Treatment - Nominzul Batsukh; Sheng Wei Feng; Wei Fang Lee; Sy-Jye Leu; Pei-Yo Tsai; Kuo-Ning Ho; Che Tong Lin; Ching-Hua Su; Wei-Jen Chang (Journal of Medical and Biological Engineering, 2017)

Emission and distribution of PCDD/Fs, chlorobenzenes, chlorophenols, and PAHs from stack gas of a fluidized bed and a stoker waste incinerator in China - Tianjiao Wang; Tong Chen; Xiaoqing Lin; Mingxiu Zhan; Xiaodong Li (Environmental Science and Pollution Research, 2017)

Coagulation increased the growth potential of various species bacteria of the effluent of a MBR for the treatment of domestic wastewater - Tong Yu; Guoqiang Li; Wenqi Lin; Hong-Ying Hu; Yun Lu (Environmental Science and Pollution Research, 2017)

Sedimentary record of Jurassic northward subduction of the Bangong–Nujiang Ocean: insights from detrital zircons - Tong-Tong Huang; Ji-Feng Xu; Jian-Lin Chen; Jian-bin Wu; Yun-Chuan Zeng (International Geology Review, 2017)

Iridoid glycosides from Callicarpa nudiflora Hook - Shi-Xiu Feng; Bo Yi; Min Zhang; Jing Xu; Hai Lin; Wen-Tong Xu (Natural Product Research, 2017)

Role of Hydrogen Sulfide on Autophagy in Liver Injuries Induced by Selenium Deficiency in Chickens - Wang Wenzhong; Zhang Tong; Lin Hongjin; Chang Ying; Xing Jun (Biological Trace Element Research, 2017)

The complete chloroplast genome sequence of Pinus dabeshanensis - Ren-Yan Duan; Li-Min Yang; Tong Lv; Gan-Lin Wu; Min-Yi Huang (Conservation Genetics Resources, 2016)

Multi-resolution graph-based clustering analysis for lithofacies identification from well log data: Case study of intraplatform bank gas fields, Amu Darya Basin - Yu Tian; Hong Xu; Xing-Yang Zhang; Hong-Jun Wang; Tong-Cui Guo; Liang-Jie Zhang; Xing-Lin Gong (Applied Geophysics, 2016)

Regulation and the Mechanism of Estrogen on Cav1.2 Gene in Rat-Cultured Cortical Astrocytes - Ling He; Xiao-Tong Hu; Yu-Jie Lai; Yan Long; Lu Liu; Bing-lin Zhu; Guo-Jun Chen (Journal of Molecular Neuroscience, 2016)

Low temperature destruction of PCDD/Fs over V2O5-CeO2/TiO2 catalyst with ozone - Ming-feng Yu; Xiao-qing Lin; Mi Yan; Xiao-dong Li; Tong Chen; Jian-hua Yan (Environmental Science and Pollution Research, 2016)

Proteomic profile of Citrus grandis roots under long-term boron-deficiency revealed by iTRAQ - Lin-Tong Yang; Yi-Bin Lu; Yuan Zhang; Peng Guo; Li-Song Chen (Trees, 2016)

Suppression of dioxins by S-N inhibitors in pilot-scale experiments - Ming-Xiu Zhan; Jian-Ying Fu; Tong Chen; Xiao-Qing Lin; Xiao-Dong Li; Jian-Hua Yan; Alfons Buekens (Environmental Science and Pollution Research, 2016)

Catalytic destruction of PCDD/Fs over vanadium oxide-based catalysts - Ming-feng Yu; Xiao-qing Lin; Xiao-dong Li; Mi Yan; Bayu Prabowo; Wen-wei Li; Tong Chen; Jian-hua Yan (Environmental Science and Pollution Research, 2016)

Emission and distribution of PCDD/Fs and CBzs from two co-processing RDF cement plants in China - Tong Chen; Ming-Xiu Zhan; Xiao-qing Lin; Ye-qing Li; Jiang Zhang; Xiao-Dong Li; Jian-hua Yan; Alfons Buekens (Environmental Science and Pollution Research, 2016)

Mapping the vegetation distribution of the permafrost zone on the Qinghai-Tibet Plateau - Zhi-wei Wang; Qian Wang; Lin Zhao; Xiao-dong Wu; Guang-yang Yue; De-fu Zou; Zhuo-tong Nan; Guang-yue Liu; Qiang-qiang Pang; Hong-bing Fang; Tong-hua Wu; Jian-zong Shi; et al. (Journal of Mountain Science, 2016)

New naphthopyrones from marine-derived fungus Aspergillus niger 2HL-M-8 and their in vitro antiproliferative activity - Da-Hong Li; Tong Han; Li-Ping Guan; Jiao Bai; Nan Zhao; Zhan-Lin Li; Xin Wu; Hui-Ming Hua (Natural Product Research, 2016)

Identification and Evaluation of Reliable Reference Genes in the Medicinal Fungus Shiraia bambusicola - Liang Song; Tong Li; Li Fan; Xiao-Ye Shen; Cheng-Lin Hou (Current Microbiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Quantitative phosphoproteomic analysis of early seed development in rice (Oryza sativa L.) - Jiehua Qiu; Yuxuan Hou; Xiaohong Tong; Yifeng Wang; Haiyan Lin; Qing Liu; Wen Zhang; Zhiyong Li; Babi R. Nallamilli; Jian Zhang (Plant Molecular Biology, 2016)

Association between STAT3 polymorphisms and cancer risk: a meta-analysis - Ruicheng Yan; Fusheng Lin; Chao Hu; Shilun Tong (Molecular Genetics and Genomics, 2015)

Sex difference of autosomal alleles in populations of European and African descent - Lingjun Zuo; Tong Wang; Xiandong Lin; Jijun Wang; Yunlong Tan; Xiaoping Wang; Xueqing Yu; Xingguang Luo (Genes & Genomics, 2015)

Influence of organic and inorganic flocculants on the formation of PCDD/Fs during sewage sludge incineration - Xiaoqing Lin; Xiaodong Li; Shengyong Lu; Fei Wang; Tong Chen; Jianhua Yan (Environmental Science and Pollution Research, 2015)

Dustfall Heavy Metal Pollution During Winter in North China - Qiu-lin Xiong; Wen-ji Zhao; Xiao-yu Guo; Tong-tong Shu; Fan-tao Chen; Xiao-xia Zheng; Zhao-ning Gong (Bulletin of Environmental Contamination and Toxicology, 2015)

Levels, spatial distribution, and exposure risks of decabromodiphenylethane in soils of North China - Yan Lin; Jin Ma; Xinghua Qiu; Yifan Zhao; Tong Zhu (Environmental Science and Pollution Research, 2015)

Expression and characterization of LacMP, a novel fungal laccase of Moniliophthora perniciosa FA553 - Huiping Liu; Chaofan Tong; Bing Du; Shuli Liang; Ying Lin (Biotechnology Letters, 2015)

A new species and a new combination of Terriera based on morphological and molecular data - Ting-Ting Zhang; Xin Tong; Ying-Ren Lin; Cheng-Lin Hou (Mycological Progress, 2015)

Detection of pepper mild mottle virus in pepper sauce in China - Jiejun Peng; Bingbin Shi; Hongying Zheng; Yuwen Lu; Lin Lin; Tong Jiang; Jianping Chen; Fei Yan (Archives of Virology, 2015)

Potential of utilizing jellyfish as food in culturing Pampus argenteus juveniles - Chun-sheng Liu; Si-qing Chen; Zhi-meng Zhuang; Jing-ping Yan; Chang-lin Liu; He-tong Cui (Hydrobiologia, 2015)

Physical‐biological coupling of N 2 fixation in the northwestern S outh C hina S ea coastal upwelling during summer - Run Zhang; Min Chen; Qing Yang; Yuanshao Lin; Huabin Mao; Yusheng Qiu; Jinlu Tong; E. Lv; Zhi Yang; Weifeng Yang; Jianping Cao (Limnology and Oceanography, 2015)
Here, we present the first combined results of N 2 fixation rates ( 15 N 2 assay), dissolved iron (dFe, 14 C assay) in the northwestern South China Sea (NWSCS) coastal upwelling region during summer. Surface N 2 fixation rate ranged between 0.1 nmol N L −1 d −1 and 5.6 nmol N L −1 d −1 (average 1.0 nmol N L −1 d −1 , n = 50) under nonbloom conditions. At a Trichodesmium bloom station, N 2 fixation rate was ∼ 3 orders of magnitude higher. Depth‐integrated N 2 fixation rate ranged between 7.5 μmol N m −2 d −1 and 163.1 μmol N m −2 d −1 (average 46.4 μmol N m −2 d −1 ). Our results indicate that N 2 fixation is unlikely limited by Fe availability in the NWSCS continental waters, instead, the coastal upwelling‐induced combined effects of physical and biological processes may have played a decisive role. With the upwelled cold, dFe‐rich, nutrient‐replete waters, nondiazotrophic phytoplankton growth would be preferentially enhanced while N 2 fixation was hindered due to relative deficiency of phosphate caused by massive phytoplankton utilization in the coastal upwelling. By comparison, N 2 fixation was notably elevated along with decreased PP in the offshore waters, probably due to a shift from P‐deficiency to N‐deficiency. Consistently, the contribution of N 2 fixation to PP (0.01–2.52%) also increased toward the open waters. As a significant external N source, summertime N 2 fixation is estimated to contribute a flux of 1.4 Gmol N to this area under nonbloom conditions. This study adds to the knowledge of N 2 fixation in the rarely studied subtropical coastal upwellings, and highlights the necessity of future comprehensive studies in such highly dynamic environments.

Decreasing Transmembrane Segment Length Greatly Decreases Perfringolysin O Pore Size - Qingqing Lin; Tong Wang; Huilin Li; Erwin London (The Journal of Membrane Biology, 2015)

Planococcus dechangensis sp. nov., a moderately halophilic bacterium isolated from saline and alkaline soils in Dechang Township, Zhaodong City, China - Kaibiao Wang; Lei Zhang; Jianying Li; Yuanyuan Pan; Lin Meng; Tong Xu; Cheng Zhang; Henan Liu; Shan Hong; Haipeng Huang; Juquan Jiang (Antonie van Leeuwenhoek, 2015)

Three-dimensional tensor controlled-source electromagnetic modeling based on the vector finite-element method - Ying-Cai Hu; Tong-Lin Li; Cui-Song Fan; Da-Yong Wang; Jian-Ping Li (Applied Geophysics, 2015)

Characteristics of Dew Formation and Distribution, and Its Contribution to the Surface Water Budget in a Semi-arid Region in China - Qiang Zhang; Sheng Wang; Fu-Lin Yang; Ping Yue; Tong Yao; Wen-Yu Wang (Boundary-Layer Meteorology, 2015)

Equatorward shift of the South Asian high in response to anthropogenic forcing - Xia Qu; Gang Huang; Kaiming Hu; Shang-Ping Xie; Yan Du; Xiao-Tong Zheng; Lin Liu (Theoretical and Applied Climatology, 2015)

Distribution of PCDD/Fs in the fly ash and atmospheric air of two typical hazardous waste incinerators in eastern China - Tong Chen; Ming-xiu Zhan; Xiao-qing Lin; Jian-ying Fu; Sheng-yong Lu; Xiao-dong Li (Environmental Science and Pollution Research, 2015)

Roles of rootstocks and scions in aluminum-tolerance of Citrus - Xin-Yan Liao; Lin-Tong Yang; Yi-Bin Lu; Xin Ye; Li-Song Chen (Acta Physiologiae Plantarum, 2015)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

Geographical variations in life histories of Plutella xylostella in China - Qin-Jian Pan; Lin Chen; Xiao-Li Lin; Thomas J. Ridsdill-Smith; Tong-Xian Liu (Journal of Pest Science, 2014)

Carbon and nitrogen isotopic composition of particulate organic matter and its biogeochemical implication in the Bering Sea - Feng Lin; Min Chen; Jinlu Tong; Jianping Cao; Yusheng Qiu; Minfang Zheng (Acta Oceanologica Sinica, 2014)

Cloning and identification of Group 1 mrp operon encoding a novel monovalent cation/proton antiporter system from the moderate halophile Halomonas zhaodongensis - Lin Meng; Shan Hong; Henan Liu; Haipeng Huang; Hao Sun; Tong Xu; Juquan Jiang (Extremophiles, 2014)

Proteomic changes of Citrus roots in response to long-term manganese toxicity - Xiang You; Lin-Tong Yang; Yi-Bin Lu; Huan Li; Shi-Qi Zhang; Li-Song Chen (Trees, 2014)

A more sensitive and rapid multiplex RT-PCR assay combining with magnetic nanobeads for simultaneous detection of viruses in sweet potato - Xing-Guang Deng; Feng Zhu; Ying-Juan Chen; Jian Liu; Tong Zhu; Jing-Yi Li; De-Hui Xi; Hong-Hui Lin (European Journal of Plant Pathology, 2014)

Indian Ocean variability in the CMIP5 multi-model ensemble: the zonal dipole mode - Lin Liu; Shang-Ping Xie; Xiao-Tong Zheng; Tim Li; Yan Du; Gang Huang; Wei-Dong Yu (Climate Dynamics, 2014)

Three-dimensional reconstruction method for measuring the knee valgus angle of the femur in northern Chinese adults - Tong Liu; Chen-yu Wang; Jian-lin Xiao; Lan-yu Zhu; Xue-zhou Li; Yan-guo Qin; Zhong-li Gao (Journal of Zhejiang University-SCIENCE B, 2014)

Degradation of polyurethane by bacterium isolated from soil and assessment of polyurethanolytic activity of a Pseudomonas putida strain - Yu-Huei Peng; Yang-hsin Shih; Yen-Chun Lai; Yuan-Zan Liu; Ying-Tong Liu; Nai-Chun Lin (Environmental Science and Pollution Research, 2014)

Genetic manipulation of a transcription-regulating sequence of porcine reproductive and respiratory syndrome virus reveals key nucleotides determining its activity - Haihong Zheng; Keyu Zhang; Xing-Quan Zhu; Changlong Liu; Jiaqi Lu; Fei Gao; Yan Zhou; Hao Zheng; Tao Lin; Liwei Li; Guangzhi Tong; Zuzhang Wei; et al. (Archives of Virology, 2014)

The roles of autophagy in development and stress responses in Arabidopsis thaliana - Xin Lv; Xiaojun Pu; Gongwei Qin; Tong Zhu; Honghui Lin (Apoptosis, 2014)

Gridded Field Observations of Polybrominated Diphenyl Ethers in Soils of North China - Di Liu; Jin Ma; Xinghua Qiu; Yifan Zhao; Yan Lin; Qiaoyun Yang; Zhenji Gao; Tong Zhu (Archives of Environmental Contamination and Toxicology, 2014)

Microarray gene expression analysis of Monochamus alternatus (Coleoptera: Cerambycidae) after treatment with a sublethal dose of chloramine phosphorus - Tong Lin; Linlin Luo; Chunmei Wei; Huajun Wu (Applied Entomology and Zoology, 2014)

Genome-wide analysis of the bHLH transcription factor family in Chinese cabbage (Brassica rapa ssp. pekinensis) - Xiao-Ming Song; Zhi-Nan Huang; Wei-Ke Duan; Jun Ren; Tong-Kun Liu; Ying Li; Xi-Lin Hou (Molecular Genetics and Genomics, 2014)

Nanomedicine: Tiny Particles and Machines Give Huge Gains - Sheng Tong; Eli J. Fine; Yanni Lin; Thomas J. Cradick; Gang Bao (Annals of Biomedical Engineering, 2014)

Isolation and characterization of microsatellite loci in the short-tailed pit viper Gloydius brevicaudus (Viperidae) - Li Ma; Qing-Lin Tong; Ce Chen; Ying-Dan Pan; Long-Hui Lin (Conservation Genetics Resources, 2013)

γ-Aminobutyric acid (GABA) homeostasis regulates pollen germination and polarized growth in Picea wilsonii - Yu Ling; Tong Chen; Yanping Jing; Lusheng Fan; Yinglang Wan; Jinxing Lin (Planta, 2013)

Pestalotiopsis yunnanensis sp. nov., an endophyte from Podocarpus macrophyllus (Podocarpaceae) based on morphology and ITS sequence data - Ji-Guang Wei; Cong-Kien Phan; Lin Wang; Tong Xu; Ji-Tong Luo; Xiang Sun; Liang-Dong Guo (Mycological Progress, 2013)

Characterization of a bovine viral diarrhea virus originated from cattle in Gansu Province, China - Shandian Gao; Junjun Shao; Junzheng Du; Tong Lin; Guozheng Cong; Furong Zhao; Huiyun Chang; Hong Yin (Virus Genes, 2013)

High prevalence of torque teno sus virus in China and genetic diversity of the 5’ non-coding region - Shao-Lun Zhai; Jin-Xue Long; Wen-Kang Wei; Qin-Ling Chen; Man-Lin Luo; Dian-Hong Lv; Da-Cheng Wu; Fei Gao; Shi-Shan Yuan; Guang-Zhi Tong; Zu-Zhang Wei (Archives of Virology, 2013)

From Legal Transplants to Sustainable Transition - Xin Tong; Lin Yan (Journal of Industrial Ecology, 2013)
Summary Extended producer responsibility (EPR), which assigns significant responsibility to producers to take back their end‐of‐life products to create incentives for redesign of products with lower life cycle environmental impacts, has come to a crossroad facing a trade‐off between the original innovation‐oriented regime design and the cost‐efficiency challenges in practice. This is particularly true in its implementation in non‐Organization for Economic Co‐operation and Development (OECD) countries as they are trying to transplant the “best practices” from OECD countries, for there is increasing skepticism as to whether EPR is suitable for developing countries at all. As an important producer of electronic products and destination of electronic waste (e‐waste) flows in the world, China has been expected to play a vital role in the evolution of global governance based on the idea of EPR, either to create new ways for producers to perform their end‐of‐life strategies, or to reshape the mode of production and consumption with its fast‐growing market. However, the establishment of EPR in China has been long and full of difficulties. This article reviews the status and trends in the establishment of an EPR system for waste electrical and electronic equipment (WEEE) management in China. We use the framework of a multilevel perspective of transition theory in our analysis to characterize the complex interactions among various agents in the evolution of the Chinese system from initial innovation‐oriented design to the current efficiency‐oriented version. An ongoing research framework for evaluation of the EPR program in China is outlined as the research agenda in coming years.

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Orchid fleck virus: an unclassified bipartite, negative-sense RNA plant virus - De Wei Peng; Guo Hua Zheng; Zhi Zhong Zheng; Qing Xuan Tong; Yan Lin Ming (Archives of Virology, 2013)

Thaxtomin A-deficient endophytic Streptomyces sp. enhances plant disease resistance to pathogenic Streptomyces scabies - Lan Lin; Hui Ming Ge; Tong Yan; Yan Hua Qin; Ren Xiang Tan (Planta, 2012)

Use of reverse genetics to develop a novel marker porcine reproductive and respiratory syndrome virus - Tao Lin; Xiangrui Li; Huochun Yao; Zuzhang Wei; Feifei Tan; Runxia Liu; Lichang Sun; Rong Zhang; Wenliang Li; Jiaqi Lu; Guangzhi Tong; Shishan Yuan (Virus Genes, 2012)

Mechano growth factor (MGF) promotes proliferation and inhibits differentiation of porcine satellite cells (PSCs) by down-regulation of key myogenic transcriptional factors - Li-Li Qin; Xiao-Kui Li; Jian Xu; De-Lin Mo; Xiong Tong; Zhi-Cheng Pan; Jia-Qi Li; Yao-Sheng Chen; Zhe Zhang; Chong Wang; Qiao-Ming Long (Molecular and Cellular Biochemistry, 2012)

Erratum to: Probing and tracking organelles in living plant cells - Tong Chen; Xiaohua Wang; Daniel von Wangenheim; Maozhong Zheng; Jozef Šamaj; Wanquan Ji; Jinxing Lin (Protoplasma, 2012)

Physiological impacts of magnesium-deficiency in Citrus seedlings: photosynthesis, antioxidant system and carbohydrates - Gang-Hua Yang; Lin-Tong Yang; Huan-Xin Jiang; Yan Li; Ping Wang; Li-Song Chen (Trees, 2012)

Sequencing and analysis of the complete genome of Rana grylio virus (RGV) - Xiao-Ying Lei; Tong Ou; Ruo-Lin Zhu; Qi-Ya Zhang (Archives of Virology, 2012)

Probing and tracking organelles in living plant cells - Tong Chen; Xiaohua Wang; Daniel von Wangenheim; Maozhong Zheng; Jozef Šamaj; Wanquan Ji; Jinxing Lin (Protoplasma, 2012)

XPA A23G polymorphism and susceptibility to cancer: a meta-analysis - Jun Liu; Zhen Zhang; Xiao-Lin Cao; Da-Peng Lei; Zhong-Qiu Wang; Tong Jin; Xin-Liang Pan (Molecular Biology Reports, 2012)

Impacts of glyphosate on photosynthetic behaviors in Kappaphycus alvarezii and Neosiphonia savatieri detected by JIP-test - Tong Pang; Jianguo Liu; Qian Liu; Litao Zhang; Wei Lin (Journal of Applied Phycology, 2012)

Cloning and sequence analysis of two banana bunchy top virus genomes in Hainan - Nai-Tong Yu; Yu-Liang Zhang; Tuan-Cheng Feng; Jian-Hua Wang; Mahesh Kulye; Wen-Jun Yang; Zhan-Song Lin; Zhongguo Xiong; Zhi-Xin Liu (Virus Genes, 2012)

Differential expression of genes involved in alternative glycolytic pathways, phosphorus scavenging and recycling in response to aluminum and phosphorus interactions in Citrus roots - Lin-Tong Yang; Huan-Xin Jiang; Yi-Ping Qi; Li-Song Chen (Molecular Biology Reports, 2012)

Alleviative effect of quercetin on germ cells intoxicated by 3-methyl-4-nitrophenol from diesel exhaust particles - Tong-liang Bu; Yu-dong Jia; Jin-xing Lin; Yu-ling Mi; Cai-qiao Zhang (Journal of Zhejiang University-SCIENCE B, 2012)

Three-dimensional interpretation of sparse survey line MT data: Synthetic examples - Chang-Hong Lin; Han-Dong Tan; Qing Shu; Tuo Tong; Yu-Mei Zhang (Applied Geophysics, 2012)

Strontium Ranelate Prevents Bone Loss in a Rat Model of Localized Muscle Paralysis - Zhi-Feng Sheng; Yu-Lin Ma; Dejun Tong; De-Yu Fang; Qing-Chun Liang; Li-Hong Liu; Jian Zhang; Er-Yuan Liao (Annals of Biomedical Engineering, 2012)

AURKB and MAPK involvement in the regulation of the early stages of mouse zygote development - Lin Xu; Tong Liu; Feng Han; ZhiHong Zong; GuoLi Wang; BingZhi Yu; Jie Zhang (Science China Life Sciences, 2012)

First Isolation of Candida dubliniensis from Oral Cavities of Dermatological Patients in Nanjing, China - Yi P. Ge; Guo X. He; Tong Lin; Gui X. Lu; Yong N. Shen; Wei D. Liu (Mycopathologia, 2011)

Genomic sequencing and analysis of Chilli ringspot virus, a novel potyvirus - Dian Gong; Jian-Hua Wang; Zhan-Song Lin; Shao-Yan Zhang; Yu-Liang Zhang; Nai-Tong Yu; Zhongguo Xiong; Zhi-Xin Liu (Virus Genes, 2011)

Nitric oxide activates superoxide dismutase and ascorbate peroxidase to repress the cell death induced by wounding - Chih-Ching Lin; Pei-Ju Jih; Hsin-Hung Lin; Jeng-Shane Lin; Ling-Lan Chang; Yu-Hsing Shen; Shih-Tong Jeng (Plant Molecular Biology, 2011)

Retinol, vitamins A, C, and E and breast cancer risk: a meta-analysis and meta-regression - Hu Fulan; Jiang Changxing; Wang Yi Baina; Zhang Wencui; Lin Chunqing; Wang Fan; Li Dandan; Sun Dianjun; Wang Tong; Pang Da; Zhao Yashuang (Cancer Causes & Control, 2011)

Three-dimensional conjugate gradient inversion of magnetotelluric impedance tensor data - Changhong Lin; Handong Tan; Tuo Tong (Journal of Earth Science, 2011)

Three-dimensional conjugate gradient inversion of magnetotelluric full information data - Chang-Hong Lin; Han-Dong Tan; Tuo Tong (Applied Geophysics, 2011)

β-Actin is a downstream effector of the PI3K/AKT signaling pathway in myeloma cells - Yen-Peng Ho; Chi-Wei Kuo; Yuan-Tong Hsu; Yu-Shan Huang; Li-Ping Yew; Wei-Feng Huang; Kuo-Chih Lin; Jung-Hsin Hsu (Molecular and Cellular Biochemistry, 2011)

Microarray-based identification of tomato microRNAs and time course analysis of their response to Cucumber mosaic virus infection - Qiu-lei Lang; Xiao-chuan Zhou; Xiao-lin Zhang; Rafal Drabek; Zhi-xiang Zuo; Yong-liang Ren; Tong-bin Li; Ji-shuang Chen; Xiao-lian Gao (Journal of Zhejiang University-SCIENCE B, 2011)

Activation of PPARδ promotes mitochondrial energy metabolism and decreases basal insulin secretion in palmitate-treated β-cells - Li Jiang; Jun Wan; Lin-qiu Ke; Qing-guo Lü; Nan-wei Tong (Molecular and Cellular Biochemistry, 2010)

Identification of p27/KIP1 expression level as a candidate biomarker of response to rapalogs therapy in human cancer - Guang Chen; Na Yang; Xiang Wang; Si-Yuan Zheng; Yi Chen; Lin-Jiang Tong; Yi-Xue Li; Ling-Hua Meng; Jian Ding (Journal of Molecular Medicine, 2010)

Static magnetic field exposure promotes differentiation of osteoblastic cells grown on the surface of a poly-l-lactide substrate - Sheng-Wei Feng; Yi-June Lo; Wei-Jen Chang; Che-Tong Lin; Sheng-Yang Lee; Yoshimitsu Abiko; Haw-Ming Huang (Medical & Biological Engineering & Computing, 2010)

Assessment of the bioaccessibility of polycyclic aromatic hydrocarbons in topsoils from different urban functional areas using an in vitro gastrointestinal test - Min Lu; Dongxing Yuan; Qingmei Lin; Tong Ouyang (Environmental Monitoring and Assessment, 2010)

Phylogenetic analysis and screening of antimicrobial and cytotoxic activities of moderately halophilic bacteria isolated from the Weihai Solar Saltern (China) - Lei Chen; Guangyu Wang; Tong Bu; Yunbin Zhang; Yixin Wang; Ming Liu; Xiukun Lin (World Journal of Microbiology and Biotechnology, 2010)

Allopatric divergence and phylogeographic structure of the plateau zokor ( Eospalax baileyi ), a fossorial rodent endemic to the Qinghai–Tibetan Plateau - Li‐Zhou Tang; Liu‐Yang Wang; Zhen‐Yuan Cai; Tong‐Zuo Zhang; Hai‐Xin Ci; Gong‐Hua Lin; Jian‐Ping Su; Jian‐Quan Liu (Journal of Biogeography, 2010)
Aim Most species of temperate regions are believed to have shifted to lower latitudes or elevations during the glacial periods of the Quaternary. In this study we test whether this phylogeographic assumption is also true for the plateau zokor ( Eospalax baileyi ), a fossorial rodent endemic to the climate‐sensitive Qinghai–Tibetan Plateau (QTP), which ranges in elevation from 2600 to 4600 m. Location The QTP of western China. Methods Phylogeographic analyses were conducted based on the mitochondrial cytochrome b gene sequences of 193 individuals from 20 populations over the entire range of the species. Results A total of 54 haplotypes identified in the present study clustered into four geographically correlated clades located in the interior of the QTP (clade A) and at the plateau edge (B, C and D). Molecular calibrations suggest that the interior plateau (A) and plateau‐edge (B–D) clades diverged at 1.2 Ma and that the three plateau‐edge clades diverged between 0.85 and 0.80 Ma. These estimates are concordant with diastrophism and glaciation events in the QTP. Coalescent tests rejected both the hypothesis that all current populations originated from a single refugium at a low elevation during the Last Glacial Maximum (LGM) and the hypothesis that the two lineages diverged during the LGM. The tests instead supported the hypothesis that there were four refugia during the LGM, and that the four clades diverged prior to the late Pleistocene. Main conclusions Our results suggest that Quaternary diastrophisms and glaciations repeatedly promoted allopatric divergence of the plateau zokor into geographical clades, and that these regional clades subsequently persisted at high elevations, rather than migrating to the low‐elevation plateau edge during subsequent glacial ages.

The speed of mitochondrial movement is regulated by the cytoskeleton and myosin in Picea wilsonii pollen tubes - Maozhong Zheng; Qinli Wang; Yan Teng; Xiaohua Wang; Feng Wang; Tong Chen; Jozef Šamaj; Jinxing Lin; David C. Logan (Planta, 2010)

Excretion of PFOA and PFOS in Male Rats During a Subchronic Exposure - Lin Cui; Chun-yang Liao; Qun-fang Zhou; Tong-mei Xia; Zhao-jun Yun; Gui-bin Jiang (Archives of Environmental Contamination and Toxicology, 2010)

Effects of the multiple polyadenylation signal AAUAAA on mRNA 3′-end formation and gene expression - Hsin-Hung Lin; Li-Fen Huang; Hsiao-Chien Su; Shih-Tong Jeng (Planta, 2009)

MoFLP1, encoding a novel fungal fasciclin-like protein, is involved in conidiation and pathogenicity in Magnaporthe oryzae - Tong-bao Liu; Guo-qing Chen; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2009)

Parallel rapid relaxation inversion of 3D magnetotelluric data - Changhong Lin; Handong Tan; Tuo Tong (Applied Geophysics, 2009)

Arabidopsis microtubule-associated protein AtMAP65-2 acts as a microtubule stabilizer - Hua Li; Xian Zeng; Zi-Qiang Liu; Qiu-Tao Meng; Ming Yuan; Tong-Lin Mao (Plant Molecular Biology, 2009)

Cistanche deserticola Ma cultivated as a new crop in China - Rong Xu; Jun Chen; Shi-Lin Chen; Tong-Ning Liu; Wei-Cheng Zhu; Jiang Xu (Genetic Resources and Crop Evolution, 2009)

The impact of chemical lateral boundary conditions on CMAQ predictions of tropospheric ozone over the continental United States - Youhua Tang; Pius Lee; Marina Tsidulko; Ho-Chun Huang; Jeffery T. McQueen; Geoffrey J. DiMego; Louisa K. Emmons; Robert B. Pierce; Anne M. Thompson; Hsin-Mu Lin; Daiwen Kang; Daniel Tong; et al. (Environmental Fluid Mechanics, 2009)

Three-dimensional conjugate gradient inversion of magnetotelluric sounding data - Changhong Lin; Handong Tan; Tuo Tong (Applied Geophysics, 2008)

A simple and effective method for total RNA isolation of appressoria in Magnaporthe oryzae - Tong-bao Liu; Jian-ping Lu; Xiao-hong Liu; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Vertical distribution, biomass, production and turnover of fine roots along a topographical gradient in a sandy shrubland - Gang Huang; Xue-yong Zhao; Yan-gui Su; Ha-lin Zhao; Tong-hui Zhang (Plant and Soil, 2008)

Residual Stress Patterns Affect Cell Distributions on Injection-Molded Poly-l-Lactide Substrate - Sheng-Yang Lee; How Tseng; Keng-Liang Ou; Jen-Chang Yang; Kuo-Ning Ho; Che-Tong Lin; Haw-Ming Huang (Annals of Biomedical Engineering, 2008)

Complete nucleotide sequence of a Chinese serotype Asia1 vaccine strain of foot-and-mouth disease virus - Junzheng Du; Huiyun Chang; Guozheng Cong; Junjun Shao; Tong Lin; Youjun Shang; Zaixin Liu; Xiangtao Liu; Xuepeng Cai; Qingge Xie (Virus Genes, 2007)

Static Magnetic Fields Promote Osteoblast-Like Cells Differentiation Via Increasing the Membrane Rigidity - Kang-Hsuan Chiu; Keng-Liang Ou; Sheng-Yang Lee; Che-Tong Lin; Wei-Jen Chang; Chang-Chih Chen; Haw-Ming Huang (Annals of Biomedical Engineering, 2007)

Nitroaniline Isomers Interaction with Bovine Serum Albumin and Toxicological Implications - Guanghong Xiang; Changlun Tong; Haizhuan Lin (Journal of Fluorescence, 2007)

Cloning, sequencing and expression analysis of the NAR promoter activated during hyphal stage of Magnaporthe grisea - Jian-ping Lu; Zhi-bing Duan; Tong-bao Liu; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2007)

Scaling behavior of nucleotide cluster in DNA sequences - Jun Cheng; Zi-shuang Tong; Lin-xi Zhang (Journal of Zhejiang University-SCIENCE B, 2007)

Development of microsatellite markers from tartary buckwheat - Yan-Qin Li; Tong-Lin Shi; Zong-Wen Zhang (Biotechnology Letters, 2007)

The parallel 3D magnetotelluric forward modeling algorithm - Tan Handong; Tong Tuo; Lin Changhong (Applied Geophysics, 2006)

Vibrational analysis of mandible trauma: experimental and numerical approaches - Shu-Li Lin; Sheng-Yang Lee; Long-Yi Lee; Wen-Ta Chiu; Che-Tong Lin; Haw-Ming Huang (Medical & Biological Engineering & Computing, 2006)

Absence of CYP2B6 promoter −82T>C mutation in Chinese as an additional factor for slow metabolism of drugs commonly used in infections - Ming-liang He; CK Lin; Kenneth Tong; Bingying Xu; Joseph JY Sung; Hsiang-fu Kung; Shui-shan Lee (European Journal of Clinical Pharmacology, 2006)

The impact of the storm-induced SST cooling on hurricane intensity - Tong Zhu; Da-Lin Zhang (Advances in Atmospheric Sciences, 2006)

Using Redox Potential to Detect Microbial Activities During Clavulanic Acid Biosynthesis in Streptomyces clavuligerus - Yun-Huin Lin; Sz-Chwun John Hwang; Jian Tong Gong; Jane-Yii Wu; Kuo-Cheng Chen (Biotechnology Letters, 2005)

Changes in Soil Properties After Establishment of Artemisia halodendron and Caragana microphylla on Shifting Sand Dunes in Semiarid Horqin Sandy Land, Northern China - Yong Zhong Su; Tong Hui Zhang; Yu Lin Li; Fang Wang (Environmental Management, 2005)

A Natural Compound (Ginsenoside Re) Isolated from Panax ginseng as a Novel Angiogenic Agent for Tissue Regeneration - Ya-Chun Huang; Chiung-Tong Chen; Sung-Ching Chen; Po-Hong Lai; Huang-Chien Liang; Yen Chang; Lin-Chien Yu; Hsing-Wen Sung (Pharmaceutical Research, 2005)

Evaluation of Genotoxicity of Combined Pollution by Cadmium and Atrazine - A. J. Lin; Y. G. Zhu; Y. P. Tong; C. N. Geng (Bulletin of Environmental Contamination and Toxicology, 2005)

Representative appressorium stage cDNA library of Magnaporthe grisea - Jian-ping Lu; Tong-bao Liu; Xiao-yun Yu; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2005)

Residents’ attitudes to tourism development in ancient village resorts - Li Wang; Lin Lu; Shi-rong Tong; Song Lu; Zhao Yang; Yong Wang; Dong-dong Liang (Chinese Geographical Science, 2004)

Natural Frequency Analysis of Periodontal Conditions in Human Anterior Teeth - Haw-Ming Huang; Sheng-Yang Lee; Ching-Ying Yeh; Mao-Sheng Wang; Wei-Jen Chang; Che-Tong Lin (Annals of Biomedical Engineering, 2001)

GTP-binding protein mediated phospholipase A2 activation in rat liver during the progression of sepsis - Li-Jia Tong; Lin-Wang Dong; Maw-Shung Liu (Molecular and Cellular Biochemistry, 1998)